Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Deep-water carbonate chemistry and CaCO3 burial in the North Indian Ocean since the last glaciation - Jie Tian; Rong Xiang; Sui Wan; Yi Zhong; Fuchang Zhong; Yiping Yang; Wubiao Li; Liyuan Wu; Ping Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Oleogel fabrication from Lactobacillus-stabilized emulsion templates: The role of bacterial surface properties in network stabilization mechanisms - Xiaoyi Jiang; Ping Yin; Ying Wang; Jian Ding; Fengjiao Fan; Yong Fang (Food Research International, 2026)

Research progress of carbon dioxide radical anions: Properties, generation, and environmental applications - Sheng Wang; Cheng-Xin Chen; Ping Fang; Tong Wu; Xuan-Yuan Pei; Jing Yang; Shan-Shan Yang; Jie Ding (Chemical Engineering Journal, 2026)

Engineered bacteria as ultrasound-responsive carbon monoxide vehicles for Cancer gas therapy and synergistic immunotherapy - Xiaorui Chen; Xiao Xiao; Wei Zhao; Bin Liu; Hongzhou Lian; He Ding; Piaoping Yang; Ping'an Ma; Lingjie Song; Shifang Luan; Ziyong Cheng; Jun Lin (Chemical Engineering Journal, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Estimating surface soil salinity and water–heat–salt coupling in arid oasis zones: Synergistic integration of SAR and optical-TIR data - Shuang Zhao; Jianli Ding; Jinjie Wang; Lijing Han; Haiyan Han; Ping Wang; Zhiang Lv (Soil and Tillage Research, 2026)

Full motion prediction of a free-fall lifeboat under wind loads using a combined time-domain dynamics and CFD method - Feng Xu; Zhi-Dong Wang; Hong-Jie Ling; Yang-Yue Yan; Peng Dou; Yu-Fei Ding; Ji-Ping Yang; Cai-Long Ren (Ocean Engineering, 2026)

Seismic performance-based design of shear pins in double spherical surface isolation bearings for railway bridges - Weikun He; Zexin Guo; Ping Shao; Lei Tu; Zhenghao Ding; Biao Wei; Xiaolong Jia (Engineering Structures, 2026)

Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A robot herding strategy combining CMFF and MPC for shepherding - Hongbo Liu; Ping Song; Gang Liu; Xiaoping Xin; Yuping Rong; Luyu Ding; Junyao Gao; Zhuoming Wang; Yinglong Zhang; Pengzhen Li (Computers and Electronics in Agriculture, 2026)

Construction of Brick-Wall-Like Topological Olefin-Linked Covalent Organic Frameworks via a Steric-Hindrance-Mediated Strategy for Efficient Uranium Capture - Cheng-Peng Niu; Rui Zhang; Zhi-Hai Peng; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2026)

Fe3O4@Fe SAN for peroxymonosulfate-assisted catalytic inactivation of Microcystis aeruginosa and degradation of microcystin-LR: Efficiency, mechanism and toxicity assessment - Ping Ding; Yuan Tian; Xiao Liu; Bin Wang; Zerun Zhang; Piao Wu; Guilin Liu; Pian Wu (Chemical Engineering Journal, 2026)

From bacterial template to green catalyst: Bio-fabrication of nanostructured nickel hydroxycarbonate for oxygen evolution via microbial mineralization - Feng Duan; Qichang Li; Li Xu; Haifang Wu; Ercai Pan; Wei Ding; Junhui Guo; Hang Ping; Liuyi Zhao; Hao Xie; Zhengyi Fu; Zhaoyong Zou (Chemical Engineering Journal, 2026)

Chloride ions-assisted high-efficiency natural seawater splitting enabled by noble-metal-free MnOx(OH)y/GaN nanowires - Yumeng Li; Liang Qiu; Xiantong Zheng; Lin Yao; Muhammad Salman Nasir; Zijian Huang; Ying Li; Yixin Li; Ding Wang; Wenxing Yang; Jianyang Zang; Ping Wang; et al. (Science Bulletin, 2026)

Urban plant communities shape plant–bird frugivory interaction networks through reduced connectance and increased modularity - Di Zeng; Pengfei Xiang; Guoqingzi Chen; Gengxian Hao; Jing Guo; Ping Ding; Chen Zhu; Wenjie Wang (Landscape and Urban Planning, 2026)

Enhancement of anammox coupled arsenate reduction by coexisting iron-bearing minerals - Wentao Wang; Weiyi Xiong; Qing Jiang; Long-jun Ding; Ping Wang; Jiang-Shan Li; Hui Yin; Peng Cai (Journal of Hazardous Materials, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Erratum to “Simultaneous enhanced nitrogen removal and energy recovery in sediment microbial fuel cells using pyrite as anode filler for low C/N ratio wastewater treatment” [Bioresour. Technol. 451 (2026) 134515] - Yun Zheng; An-Qi Wang; Ming-Kun Yu; Xin Sun; Han-Qi Xiang; Chao Wang; Xiao-Yu Ding; Qiu-Jun Wang; Jun Zhou; Ping Wei; Xiao-Yu Yong (Bioresource Technology, 2026)

Increasing particulate organic carbon export efficiency in Arctic River Basins: A study of emerging trends - Shiqi Liu; Ping Wang; Renjie Zhou; Jingjie Yu; Linsheng Yang; Zhiyang Li; Liudmila S. Lebedeva; Tianye Wang; Yiyang Ding (Science China Earth Sciences, 2026)

Pan-cancer characterization of the pyrimidine catabolic enzyme UPB1 identifies a tumor-suppressive prognostic biomarker in skin cutaneous melanoma - Yingli Men; Yi Shao; Yongfeng Chen; Ping Wang; Yiyang Li; Zhenzhen Yang; Ruiting Feng; Hui Wang; Yinsen Song; Cong Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Toward high-precision, low-consumption bulk analysis: advancements in extraterrestrial sample studies - Ding-Shuai Xue; Shun Guo; Yan-Hong Liu; Dan-Ping Zhang; Yong-Gang Yao; Bo Wan; Xian-Hua Li (Science Bulletin, 2026)

Migration and transformation of nanoplastics and microcystin during Chlamydomonas reinhardtii processing: From the environment to product - Chenxu Wang; Chenyu Chen; Ping Ding; Yonghua Xiong; Xiaolin Huang; Xiaoyang Li (Journal of Hazardous Materials, 2026)

Simultaneous enhanced nitrogen removal and energy recovery in sediment microbial fuel cells using pyrite as anode filler for low C/N ratio wastewater treatment - Yun Zheng; An-Qi Wang; Ming-Kun Yu; Xin Sun; Han-Qi Xiang; Chao Wang; Xiao-Yu Ding; Qiu-Jun Wang; Jun Zhou; Ping Wei; Xiao-Yu Yong (Bioresource Technology, 2026)

Independent and joint effects of ambient temperature and relative humidity on fetal distress: effect modification by air pollutants - Hua Xiao; Yi Wang; Zongli Qi; Ziwei Ye; Liping Li; Li Mao; Peng Hu; Yuefei Li; Haoyun Zhang; Yao Cheng; Hao Wang; Ping Chen; et al. (International Journal of Biometeorology, 2026)

A new amide alkaloid from the coculture liquid cultures of two grape endophytic fungi Penicillium sp. YPT103-2 and Penicillium sp. YPT104 - Yu-Qin Yang; Jin-Feng Cao; Juan-Juan Pu; Dong-Ping Li; Chuan-Mao Zhang; Zhi-Jian Wu; Jian-Hai Ding (Natural Product Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

OSL dating of fluvial and lacustrine sediment in Ranwu Lake, Southeastern Tibet - Yang Wu; Yiwei Chen; Long Huang; Ping Ding; Jifeng Zhang; Vladislav S. Isaev; Dmitrii O. Sadokov; Gangjian Wei (Quaternary Geochronology, 2026)

Stomatal width and vascular bundle anatomy govern foliar uptake and phloem transport of atmospheric Pb in wheat - Liu-Xu Feng; Xiang-Yu Li; Pei-Pei Gao; Yan Li; Gui-Li Hua; Ding-Hao Li; Li-Ping Geng; Xiao-Min Wang; Hong-J. Di; Wen-Ju Liu; Pei-Ying Xue (Journal of Hazardous Materials, 2026)

Application of rice husk biochar in foam lightweight filler: Investigating sustainable development potential of innovative subgrade materials - Erlu Wu; Pengfei Wei; Na Li; Ping Jiang; Wei Ding; Wei Wang (Journal of Environmental Chemical Engineering, 2026)

Taste plasticity and cross-habituation to distinct classes of allelochemicals in the generalist herbivore Spodoptera litura - Dong-Sheng Zhou; Hou-Ding Ou; Xiu-Qin Wang; Ping Zeng; Shi-Mei Wu; Jiu-Mei Long (Journal of Asia-Pacific Entomology, 2026)

Several small reservoir islands consistently support higher taxonomic, phylogenetic, functional, and interaction diversity than few large ones across multiple taxa - Yao Shen; Yuhao Zhao; Federico Riva; Wande Li; Chen Zhu; Xue Zhang; Ping Ding; Xingfeng Si (Biological Conservation, 2026)

Characterization of a new diterpenoid glycoside and chemotaxonomical significance of secondary metabolites from Excoecaria acerifolia - Na-Li Song; Jia-Peng Wang; Li-Ping Yang; Sheng-Qi Zhang; Xia Zhao; Le Cai; Zhong-Tao Ding (Biochemical Systematics and Ecology, 2026)

Optimal combination of iron/magnesium salts and urea can promote the degradation rate of maize straw by catalyzing the rapid de-polymerization of lignin - Han Li; Yuan fang Zhou; Sen Zhao; Si hui Yan; Ding hua Jia; Yan ping Zhang; Xiang dong Yang; Juan Li (Biocatalysis and Agricultural Biotechnology, 2026)

High-quality genome of guar (Cyamopsis tetragonoloba) provides the new insights into the biosynthesis and origination of galactomannans in Fabaceae family - Yuanhao Ding; Xinglong Zhao; Hui Yao; Shicai Huang; Xuyao Wang; Yayu Chen; Ping Li; Chengzhi Xie; Jiaquan Huang; Zhuang Yang; Haiyan Hu (Plant Cell Reports, 2026)

Proliferation of an invasive fish in a large reservoir from the downstream evidenced by whole-genome resequencing data - Tereza M. Magati; Ping Yang; Ke Yang; Dan Yu; Qingjuan Liu; Yahan Wu; Qiaoling Deng; Ruijin Ding; Huanzhang Liu (Hydrobiologia, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Pollution Characteristics and Disease Burden of PM2.5 and O₃ in Hainan Province from 2015 to 2022 - Wenci Ding; Jin Wang; Youzhi Zhao; Huikun Liu; Guangshui Na; Ping Wang (Aerosol Science and Engineering, 2026)

Rapid evaluation of the comprehensive quality of paeonol/cyclodextrin supramolecular complexes using CASSA based on near-infrared spectroscopy combined with artificial intelligence - Bo-yao Zhang; Xin-li Li; Cheng Qian; Si-min Xue; Zhi-tong Zhang; Si-yi Liu; Guo Zhang; Guo-ping Peng; Ning Ding; Yun-feng Zheng (Molecular Diversity, 2026)

Isolation and whole-genome sequencing of antibiotic-resistant bacteria revealed the reservoir for indigenous antibiotic resistance genes in the deepest ocean sediment of the Challenger Deep - Wenmian Ding; Yuepeng Wang; Yuewei Ma; Ping Chen; Ji Yang; Zhiping Song; Yuguo Wang; Wenju Zhang; Xuan Li; Yanyan Huang; Peng Nan (Marine Pollution Bulletin, 2026)

Detecting drought propagation pathways in different climatic regions of China - Zhaoqiang Zhou; Linqi Li; Yibo Ding; Yiyang Zhao; Haiyun Shi; Renjie Hou; Ping Wang; Ping Xue; Tian Wang; Peng Chen (Journal of Hydrology, 2026)

Parental DEHP exposure induces sex-specific reproductive toxicity in zebrafish and behavioral deficits in unexposed offspring - Yanan Sun; Yuqing Fan; Yao Dang; Ping Ding; Xin Li; Gang Li; Haojie Luo; Jianliang Zhao; Guocheng Hu (Environmental Pollution, 2026)

Distribution, source, and pollution risk assessment of heavy metals in the coastal sediments of the northern South China sea - Wen Yu; Yuqing Fan; Qinghua Chen; Jing Yang; Xin Li; Wei Huang; Kun Yue; Liuyi Zhang; Ping Ding; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2026)

A critical review on abiotic geologic hydrogen generation: Mechanisms and controls - Qingxia Zheng; Ruibo Wu; Ping Li; Zhe Ding; Wentao Zhang; Huiyang Mei; Weichao Zhang; Jianjun Liang; Qiaohui Fan (Earth-Science Reviews, 2026)

Rational design of one-dimensional chain-like metal-organic frameworks featuring engineered nano-pockets for highly selective and efficient uranium sequestration - Zhi Wu; Shu-Yuan Zhang; Bin Lin; An-Min Song; Fei-Yi Kong; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Construction of CoTiO3/CdS catalysts in-situ grown on recyclable chitosan hydrogel beads and their application in photocatalytic hydrogen evolution from water splitting - Meijuan Ding; Mei Li; Qingyang Yu; Ziyu Li; Jingyi Nie; Aohui Ping; Chaoqi Ding; Hongbo Li; Bing Yang; Zhiliang Jin (Journal of Environmental Chemical Engineering, 2026)

Metal mixture exposure and elevated risk of hypertensive disorders in pregnancy: Insights from a case-control study in northwestern China - Xueman Ding; Li Liu; Zhaochun Liu; Shurui Zuo; Yu Huang; Yizhong Yan; Shangzhi Xu; Ping Yao; Menghuan Xiao; Chengxian Dong; Chulin Yan; Xiaoyu Song; et al. (Journal of Environmental Sciences, 2026)

Harnessing Machine learning to quantify ecosystem services in coastal Wetlands: A case study of the Bohai economic Rim - Ting Lu; Ya Ping Wang; Jiyuan Jin; Shibing Zhu; Jianhua Gao; Hu Ding; Qinglong Wu; Fu Wang; Chao Gao (Ecosystem Services, 2026)

A flexible capacitive sensor featuring spherical-like microstructures with ultrafast response and an ultralow detection limit for miniature fast steering mirror applications - Yifan Ding; Yiqian Shao; Hang Xu; Zenghui Xiong; Jin Luo; Yao Mao; Ping-an Yang; Zhiwei Huang (Chemical Engineering Journal, 2026)

Plasma Metabolic Signature and Single-Cell Regulatory Network for Ischemic Stroke - Zhiyuan Guo; Haijun Zhang; Liwei Lv; Ping Ding; Lingyan Qi; Xiaokun Wang; Yan Chen; Yingshui Yao; Liyuan Han (Translational Stroke Research, 2026)

A tissue-to-blood mRNA classifier enables early detection of gastric cancer risk in precancerous lesions - Wenqian Ma; Honghai Guo; Tao Zheng; Mingchang Miao; Shuo Guo; Jiangao Yu; Ping’an Ding; Qun Zhao (The Science of Nature, 2026)

Multiscale Fracture Evolution in Deep Hard Rock Masses Under Strong Excavation Disturbances: Stress-Mineral Synergy Unraveled Through Integrated 3D DEM–FDM Modeling and Borehole Monitoring - Xiu-Yang Liu; Ding-Ping Xu; Quan Jiang; Shao-Jun Li; Shi-Li Qiu; Yong Xia (Rock Mechanics and Rock Engineering, 2026)

In-situ Elemental and Boron Isotopic Geochemistry of Tourmalines from Pegmatites in the Edanggang Li-Be Deposit in the Quanji Massif, NW China - Xuan Zhou; Tong Pan; Shan-Ping Li; Qing-Feng Ding (Journal of Earth Science, 2026)

An Integrated U-Net and Markov Random Field Approach for Pavement Crack Segmentation - Shi-cai Yuan; Ding-zhi Liu; Wei-ping Shi; Pan Li; Yong-qiang Li; Yong Yi (Applied Geophysics, 2026)

A Framework for Extending Rock Strength Criteria to Anisotropy - Huai-Sheng Xu; Shao-Jun Li; Ding-Ping Xu; Min-Zong Zheng; Quan Jiang; Guang-Liang Feng; Liu Liu (Rock Mechanics and Rock Engineering, 2026)

New perspectives on key bioactive molecules of lactic acid bacteria: integrating targeted screening, key gene exploration and functional evaluation - Shi Hu; Qi Wang; Jinfeng Wu; Hangjia Zhang; Jiaqi Yin; Lina Ding; Ping Li; Hang Xiao; Qing Gu; Jiarun Han (Critical Reviews in Food Science and Nutrition, 2026)

MTA-SM: Multi-machine path planning and time-window scheduling joint optimization method in hilly safflower harvesting - Liwei Yang; Ping Li; Zhongshuo Ding; Chao Sun; Fei Chen; Yijiang Zheng; Yun Ge (Computers and Electronics in Agriculture, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

System-dependent effects and mechanisms of microplastics/nanoplastics on nitrogen and phosphorus removal from wastewater treatment and N2O emission - Tong Wu; Shuai-Hang Wang; Ping Fang; Cheng-Xin Chen; Jie Ding; Ying He; Han-Jun Sun; Meng-Qi Ding; Ji-Wei Pang; Nan-Qi Ren; Shan-Shan Yang (Journal of Hazardous Materials, 2026)

Unraveling the ranitidine removal mechanism in a novel riboflavin-mediated ultraviolet/peracetic acid system: An integrated density functional theory-machine learning framework - Yizhe Ding; Jiacheng Shi; Yuqian Lin; Qiya Sun; Yuxiang Zhao; Xi Wang; Qian Ping; Lin Wang; Yongmei Li (Journal of Hazardous Materials, 2026)

Hyperbranched polyamide encapsulated ZIF-8 interlayer enabling precise regulation of polyamide nanofiltration membranes toward Li+/Mg2+ separation - Bingbing Yuan; Shengsheng Lu; Yuhang Zhang; Yuxin Ding; Xiao Chen; Lei Zhang; Jinmiao Cui; Lihong Liu; Ping Hu; Siheng Zhao; Shengchao Zhao; Kuo Chen; et al. (Desalination, 2026)

Corrigendum to “Synergistic Apoptosis-Ferroptosis: Oxaliplatin loaded amorphous iron oxide nanoparticles for High-efficiency therapy of orthotopic pancreatic cancer and CA19-9 levels decrease” [Chem. Eng. J. 464 (2023) 142690] - Yilong Li; Xinlong Wang; Binbin Ding; Cong He; Can Zhang; Jiating Li; Haonian Wang; Zhibo Li; Gang Wang; Yongwei Wang; Hua Chen; Ping’an Ma; et al. (Chemical Engineering Journal, 2026)

Microscopic mechanisms of dissolved organic matter sequestration and transformation at the mineral-water interfaces during the formation and transformation of Fe Mn (hydr)oxides - Kai Cui; Libin Wu; Zihao Wu; Yue Yang; Shiwen Hu; Xiaoyuan Zhang; Zilong Zeng; Ping Chen; Li Wang; Zecong Ding; Hao Yi (Chemical Engineering Journal, 2026)

Fluorinated dynamic imine-based porous materials with excellent hydrophobicity and closed-loop recycling - Wei Hong; Ping Yu; Haiyue Wang; Changyi You; Hongfei He; Hongying Qiu; Ruiqiang Ding; Guanxiang Ma; Bin Yu (Chemical Engineering Journal, 2026)

Nitrogen conversion and Feammox potential driven by microorganisms around the iron ore tailings pond - Yifan Jiang; Zhengbo Yue; Jin Wang; Ziyi Li; Xin Pan; Qinglong Guo; Zhiguo Li; Ping Guo; Ding Ma (Environment, Development and Sustainability, 2026)

Global, regional, and national burden of hepatocellular carcinoma and contribution of nine modifiable risk factors across 185 countries/territories in 2022 - Ping Li; Zhan Ding; Yuqi Feng; Xiangyu Ren; Yongyue Wei; Changfa Xia; Yitao Yang; Quanbo Yang; Zhe Wang; Xuehong Zhang; L.G. van der Geest; Herbert Yu; et al. (Science Bulletin, 2026)

Three new matrine-type alkaloids from Sophora alopecuroides with cytotoxic activity - Yan-Ping Qiu; He Tian; Qian Xie; Shuai Li; Bi-Qian Dong; Guan-Min Su; Ding Luo; Lin-Zhao Ye (Phytochemistry Letters, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

Process parameter optimization for greenhouse gas mitigation during green-waste composting and mechanistic insights from microbe–environment networks in treatments with contrasting outcomes - Xiaowen Li; Min Cao; Wenyuxin Huang; Hao Mei; Pan Luo; Ping Ma; Junhao Zhang; Weiqin Zhu; Miaomiao He; Ying Ding (Journal of Cleaner Production, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Research on the impact of resident behavior on energy consumption during the heating period of ultra-low energy buildings - Ru-Xi Ding; Jia-Ze Dai; Ying-Nan Zhang; Xiao-Ping Wu; Cong-Han Yu; Zhenfa Fan (Energy and Buildings, 2026)

Nano-SiO₂ modified microbial-induced carbonate precipitation: Application in altered rock fracture zone reinforcement and strengthening mechanism - He-rui Zhao; Quan Jiang; Yong Xia; Dong-qi Hou; Ding-ping Xu (Engineering Geology, 2026)

Engineering local donor-acceptor architecture in a porphyrin-based metal-organic framework for enhanced sonocatalytic immunotherapy - Yarui Hu; Sainan Liu; Jiwei Wang; Zhendong Liu; Xinyu Ma; Junhao Shao; Binbin Ding; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2026)

Investigating the Key Elements of Acid Production in Coal Mine Water Based on Meta Analysis - Tianhang Cheng; Haoran Ding; Yanchang Huang; Ping Lu (Water, Air, & Soil Pollution, 2026)

Evaluation of Muscle Stiffness in Patients with Parkinson’s Disease with Different Stages of Sarcopenia by Shear Wave Elastography - Ping Zhao; Changwei Ding; Yingchun Zhang; Jian Wu; Min Yang; Caishan Wang; Chunfeng Liu (Journal of Medical and Biological Engineering, 2026)

Wheat-associated Antagonistic Bacteria Exerts Biocontrol Activity Against Fungal Growth and Deoxynivalenol Production in Fusarium Graminearum - Ziting Ding; Wenjing Fu; Ping Zhou; Tao Gao; Zhitian Zheng (Current Microbiology, 2026)

Organic amendment strategies differentially regulate microbial carbon use efficiency: A long-term field study integrating microorganism and enzymatic stoichiometry - Weiyan Wang; Shijie Ding; Tengfei Guo; Xinpeng Xu; Ping He; Shaomin Huang (Agriculture, Ecosystems & Environment, 2026)

Molecular signature evolution of dissolved organic matter in wastewater during far-ultraviolet/peracetic acid disinfection: Integrated characterization and machine learning - Nuo Peng; Qiya Sun; Yuxiang Zhao; Yizhe Ding; Jiacheng Shi; Qian Ping; Lin Wang; Yongmei Li (Water Research, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Nickel isotopic evidence for potential deep magmatic sulfide ore bodies in orogenic settings - Peng-Yi Li; Shui-Jiong Wang; Fu-Ping Pei; Guan-Wen Yu; Bing-Qian Ding; Zi-Cheng Guan; Kai Song; Wen-Liang Xu (Geochimica et Cosmochimica Acta, 2026)

Iron-ceramsite with balanced electron transfer capacity enables simultaneous removal of refractory organics and nitrogen in coking wastewater by single-stage BAF - Hui Zhai; Ding Ma; Jin Wang; Wusong Xu; Yifan Jiang; Bixuan Sheng; Qinglong Guo; Zhiguo Li; Ping Guo; Zhengbo Yue (Chemical Engineering Journal, 2026)

Research on the resistance characteristics and model construction of aircraft tires on snow-covered runways - Qingmiao Ding; Haibin Jiang; Boyuan Ping; Yanyu Cui; Hao Zhang; Juquan Yang (Cold Regions Science and Technology, 2026)

Future changes of precipitation recycling over Northwest China by CMIP6 models - Ping Wu; Xiucang Li; Yanju Liu; Ying Xu; Yihui Ding (Atmospheric Research, 2026)

Correction: Dexmedetomidine Improves Long-term Neurological Outcomes by Promoting Oligodendrocyte Genesis and Myelination in Neonatal Rats Following Hypoxic-ischemic Brain Injury - Hang Xue; Zixuan Ding; Xiaoyan Chen; Xu Yang; Yufei Jia; Ping Zhao; Ziyi Wu (Molecular Neurobiology, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

Seismic Response of Utility Tunnels Under Oblique SV Wave Incidence in Horizontally Nonhomogeneous Sites - De-long Huang; Hui-yue Wang; Yang Ding; Hang Cen; Qiang Liu; Zhong-ling Zong; Dian-rui Mu; Ai-ping Tang (Geotechnical and Geological Engineering, 2026)

Lowering cyclosporine trough concentration threshold effectively mitigates acute graft-versus-host disease in children with severe β-Thalassemia post hematopoietic stem cell transplantation - Zhuolin Yang; Xianggui Wang; Xiaojing Wang; Wenjiao Ding; Yiyu Zhang; Qingling Gu; Wenqing Wang; Yousi Miao; Ping Xie; Min Huang; Hua Jiang; Xiaolan Mo; et al. (European Journal of Clinical Pharmacology, 2026)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Photoaging behavior and neurotoxic effects of shower gel-derived microbeads in Caenorhabditis elegans - Yulun Gu; Yajing Han; Xin Li; Ping Ding; Chaoyi Du; Xiaoxia Chen; Yongqi Jiang; Jinyu Chen; Jingwen Cui; Haibo Chen; Hui Li (Journal of Environmental Management, 2025)

Evaluation of carrying capacity of agricultural water and soil resources and targeted regional management in Northwest China - Yun Gao; Dawei Ding; Youming Zhang; Ping Li; Kaiyang Li; Tianhao Ruan; Yang Han; Chunya Ma (Journal of Environmental Management, 2025)

Construction of a novel concentrated sunlight/PDS system for efficient remediation of methyl parathion-polluted water: Synergistic photothermal activation and phosphorus fate mechanisms - Yixun Zheng; Yue Yang; Yanli Wang; Ping Chen; Zihong Xu; Zecong Ding; Zhenjun Xiao; Kai Cui; Yongpeng Zhang; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2025)

Palaeoecological reconstruction of shoreline terrestrialisation of Lake Glubokoe (Smolensk-Moscow Upland) in the late Holocene based on the results of a multi-proxy analysis - Yulia A. Pastukhova; Andrey N. Tsyganov; Natalia G. Mazei; Elena E. Severova; Dmitrii O. Sadokov; Viktor A. Chernyshov; Ekaterina V. Tkacheva; Jinyue Li; Yanwei Liu; Alexey A. Kotov; Andrey V. Kitashov; Ping Ding; et al. (Journal of Paleolimnology, 2025)

Enhanced electrocatalytic oxidation of high-salinity quaternary ammonium compound wastewater using CNTs-(Ru Ir O2)/Ti Anode - Hao-Tian Liu; Han-Qing Zhao; Yi-Rui Yang; Shuang Wu; Jia-Ping Huang; Rui-Han Yu; Hongcheng Bai; Aqiang Ding; Daijun Zhang; Peili Lu (Journal of Environmental Sciences, 2025)

N2O and NO formation and inhibition influenced by calcium (Ca) during coal char combustion - Zhi Han; Ping Liu; Yanjun Zuo; Yingchuan Zhou; Xiaoshuo Liu; Xunlei Ding; Jianming Xue; Yufeng Duan (Fuel, 2025)

High-throughput discrimination of chlorogenic acid isomers in Lonicerae Japonicae Flos by U-shaped mobility analyzer-mass spectrometer - Meng Ding; Luwei Zheng; Ao Zhou; Yuling Li; Yiming Wang; Xiaoqiang Zhang; Wenjian Sun; Wen Gao; Ping Li; Hua Yang (Food Chemistry, 2025)

Fluorescent smartphone sensing platform based on Eu3+-functionalized metal-organic framework for ultra-sensitive detection of ciprofloxacin - Tao Zhang; Zerun Zhang; Haolan Yao; Luoyao Lian; Tianhan Kai; Xiangzhu Wang; Ping Ding (Environmental Research, 2025)

An investigation of the engineering properties and environmental impact of low-temperature modified electrolytic manganese residue for karst grouting materials - Qianshen Ding; Lei Liu; Wenwei Zhang; Ping Wang; Jiangshan Li; Yong Wan (Environmental Research, 2025)

Alkali halides induced electron-deficient oxygen vacancies on polyoxometalates promoting CO2 hydrogenation - Ji Ding; Ao-Ping Wu; Huihui Zhang; Huiying Liao; Pengfei An; Sheng Dai; Zhi-Qiang Wang; Zhenshan Hou (Chemical Engineering Journal, 2025)

Sustainable design strategies of polylactic acid-based offshore composites: Synergistic effects of ceramic waste filling and inorganic/natural plant fiber toughening - Youpeng Zhang; Yi Li; Na Zhang; Ping Lu; Chong Ding; Shouhang Cui; Shuai Wang; Nuxiao Wang; Yihe Zhang (Chemical Engineering Journal, 2025)

Characterization of particle number size distribution and new particle formation in a highly-humid megacity Wuhan, central China - Haoqian Wang; Xiaoxiao Li; Jin Wu; Hao Wu; Yiran Li; Chong Liu; Ning Ma; Ping Zeng; Xuehui He; Jiapeng Ran; Huaying Song; Dandan Huang; et al. (Atmospheric Environment, 2025)

Adsorption behavior and neurotoxic synergy of thallium and polystyrene microplastics in Caenorhabditis elegans - Chaoyi Du; Ping Ding; Hongzhi Guo; Yulun Gu; Xuefang Shi; Yuyang Ni; Shiyin Zhu; Lijuan Zhang; Haibo Chen; Jianying Qi (Aquatic Toxicology, 2025)

Investigation of the South Atlantic Anomaly (SAA) by proton flux variabilities based on 6 years’ CSES data - Lu Wang; Zhenxia Zhang; Xinqiao Li; Zhenghua An; Yanbing Xu; Ping Wang; Hong Lu; Xiaoyun Zhao; Dali Zhang; Xiaohua Liang; Zhiqiang Ding; Shujie Li; et al. (Science China Earth Sciences, 2025)

Retraction Note: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2025)

CIITA was involved in regulating ACSL4-dependent ferroptosis in gastric cancer cells - Ping Zhang; Tian Wang; Na Zhu; Feifei Zhuang; Daihong Ding; Ping Wang (Molecular and Cellular Biochemistry, 2025)

Two new N -containing heterocyclic compounds from the roots of Platycodon grandiflorus - Lan Ding; Xin-Yin Cai; Ren-Nai Yang; Liang-Ping Zha; Shuang-Ying Gui; Jin-Song Liu; Ju-Tao Wang; Yang Yu (Natural Product Research, 2025)

Molecular and trace metal signatures of pristine and anthropogenically altered mangrove sediments - Zhe-Xuan Zhang; Julian P. Sachs; Yao-Ping Wang; Zhao Liang Chen; Arnaud Huguet; Ding He (Marine Pollution Bulletin, 2025)

Seismic vulnerability analysis of utility tunnel with oblique incidence of SV waves based on IDA method in horizontal non-homogeneous field - Hui-yue Wang; De-long Huang; Hai-ruo Wang; Yang Ding; Hang Cen; Zi-Yuan Huang; Ai-ping Tang; Xia-xin Tao (Soil Dynamics and Earthquake Engineering, 2025)

Effects of curcumin on jejunal morphology and intestinal integrity of broiler under heat stress - Ding-Ding Zhang; Meng-Ru Xue; Yu-Ting Liu; Hong-Jie Cui; Ding-Ping Bai (Journal of Thermal Biology, 2025)

Dual-modal aptamer/CRISPR-Cas12a biosensor with Fe-C-N@Au nanozyme for simultaneous detection of azithromycin and macrolide resistance genes and degradation of azithromycin - Guiling Liu; Zongwu Meng; Wanshu Zheng; Anqi Qiu; Yuan Tian; Zerun Zhang; Tao Zhang; Pian Wu; Ping Ding (Journal of Hazardous Materials, 2025)

Mechanistic insights into norfloxacin removal in a novel riboflavin-mediated nanoscale zero-valent iron/peracetic acid system: Synergistic radical and non-radical pathways - Lin Wang; Nuo Peng; Yuqian Lin; Yizhe Ding; Qiya Sun; Qian Ping; Yongmei Li (Journal of Hazardous Materials, 2025)

Experimental and theoretical calculation study on phosphorus removal by nZVI-loaded biochar/active clay: Synergism of chemical bonding and coordination - Tong Hao; Chen Zhao; Mingyu Shan; Yubo Ding; Kongna Wu; Xing Dai; Juan Li; Ping Zeng (Journal of Environmental Chemical Engineering, 2025)

Synergistic neurotoxicity of polystyrene nanoparticles and MEHP in zebrafish (Danio rerio) - Yiyun Liu; Qi-Ping Tang; Si-Jia Zuo; Yuan Ding; Feng-Yi Guo; Bao-Fu Zhang; Qin-Hong Zhou; Dongmei Xie; De-Sheng Pei (Environmental Pollution, 2025)

Modifying polyamide layer via coupling reactions of dendrimer and polyphenol to maximize desalination performance - Bingbing Yuan; Zhihui Zhang; Yuxin Ding; Xiao Chen; Siheng Zhao; Lihong Liu; Ping Hu; Shengchao Zhao; Kuo Chen; Juhui Jiang; Dongxiao Yang; Q. Jason Niu (Desalination, 2025)

Failure Mechanisms of Granite in Deep Underground Caverns Influenced by Rock Veins: Insights from DEM-FDM Cross-Scale Coupling and Moment Tensor Analysis - Xiu-Yang Liu; Ding-Ping Xu; Quan Jiang; Shao-Jun Li; Kang Bian; Shi-Li Qiu (Computers and Geotechnics, 2025)

Nickel complex-bridging to enhance electron transport in covalent organic frameworks for efficient photocatalytic uranium reduction - Xiao-Xing Wang; Rui Zhang; Zhi-Hai Peng; Jing-Wen Gong; En-Min Hu; Cheng-Peng Niu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

A novel CRISPR-driven Fe SANs-sensitized hydrogel biosensor for ultrasensitive detection of microcystin synthetase gene E (mcyE) and early warning of microcystin-LR - Pian Wu; Heng Dai; Jun Liu; Yuan Tian; Xiaolong Qu; Zongwu Meng; Tianhan Kai; Ping Ding (Chemical Engineering Journal, 2025)

Emerging trends in cardiovascular diseases: the impact of ferroptosis and cuproptosis on cardiomyocyte death - Peijian Chen; Ping He; Xuejing Rao; Minglu Ding; Jieting Liu; Yanhui Chu; Yang Xiao (Molecular and Cellular Biochemistry, 2025)
Cardiovascular diseases (CVDs) comprise a range of conditions affecting the heart and vasculature, encompassing ischemic heart disease (IHD), stroke, heart failure (HF), peripheral and aortic diseases, arrhythmias, and valvulopathy. Notably, the high prevalence rates of CVDs among younger populations warrant concern, emphasizing the importance of prevention and treatment. In recent years, ferroptosis, a novel form of cell death, has attracted significant research interest across various diseases. Similarly, cuproptosis, another cell death mechanism resulting from copper ion accumulation, has also been extensively studied. Cell death plays a crucial role in the development and maintenance of organisms, with both ferroptosis and cuproptosis closely associated with cell metabolism, signaling pathways, and drug resistance. Emerging evidence suggests that ferroptosis and cuproptosis are closely linked to the occurrence and progression of various diseases, including CVDs. The death of myocardial cells is pivotal in the pathophysiology of CVDs, with the roles of ferroptosis and cuproptosis in this process increasingly recognized. This article aims to summarize the molecular mechanisms and interactions of ferroptosis and cuproptosis, as well as their potential as novel targets for CVD treatment.

Island Biogeography and Life‐History Traits Stabilize Island Bird Communities - Yuhao Zhao; Di Zeng; Thomas J. Matthews; Dylan Craven; Morgan W. Tingley; Shaopeng Wang; Shao‐peng Li; Ping Ding; Xingfeng Si (Global Change Biology, 2025)
Islands are model systems for testing and developing ecological theories. Despite extensive research on island biodiversity, the importance of the biogeographic context for biodiversity–stability relationships is poorly understood. We addressed this knowledge gap by integrating the Equilibrium Theory of Island Biogeography (ETIB) with a functional perspective to explore island biodiversity–stability relationships. We conducted annual breeding bird surveys across 36 land‐bridge islands in eastern China over 13 years. Using this long‐term dataset, we quantified avian temporal community stability (and its components of population stability and population asynchrony) and tested how island biogeographic factors (i.e., island area, isolation, colonization rates, and extinction rates) and biodiversity facets (i.e., species richness, average population size, and life‐history traits) interact to influence stability. We found larger islands supported higher species richness due to colonization–extinction dynamics and habitat heterogeneity, which in turn promote both population stability and asynchrony. In addition, larger islands harbored larger and individually more stable populations over time. In contrast, island isolation had a weak net effect on stability, as its positive and negative influences through different pathways balanced each other out. Furthermore, species with ‘fast’ life‐history traits, characterized by shorter generation times, contributed more to community stability. These findings clarify multiple pathways through which biogeographic factors shape avian community dynamics on islands. Our study thus illustrates how island biotas maintain community stability and provides insights for preserving biodiversity and ecosystem functioning in fragmented or island‐like landscapes facing rapid biodiversity loss in an era of global change.

In situ addition of layered double hydroxides promotes sulfate-dependent anaerobic methane oxidation and microbial community shifts in freshwater-influenced mangroves sediments - Jijuan Ding; Fei Liu; Jing Huang; Ping Li; Junmao Zhang; Bo Wu; Longfei Shu; Zhili He; Cheng Wang (Water Research, 2025)

Tris(2-chloroethyl) phosphate alters gut microbiota and hepatic metabolism in freshwater turtles at environmentally relevant concentrations - Jin-Dian Liu; Zi-Ying Wang; Lu-Ping Lou; Wen-Qi Xie; Jia-Jun Hao; Shu-Hang Shao; Shuai Liu; Sheng-Min Wu; Guo-Hua Ding (Journal of Hazardous Materials, 2025)

Declining floral color diversity alters bee color preferences in fragmented habitats - Hongjun Xie; Peng Ren; Chen Zhu; Juan Liu; Minghao Sun; Xingfeng Si; Ping Ding (Biological Conservation, 2025)

Spatiotemporal dynamics of migratory birds reshape seed dispersal and conservation implications on fragmented islands - Wande Li; Ingo Grass; Chen Zhu; Thomas Hiller; Marit Kinga Kasten; David Becker; Sara Tassoni; Ping Ding; Xingfeng Si (Biological Conservation, 2025)

Genome-wide Identification of the MTP Gene Family in Cotton and Expression Analysis Under Multiple Metal Stresses - Yong Yang; Wenjie Lai; Ping Li; Shihan Zhou; Yutong Wu; Yuanhao Ding; Haiyan Hu (Plant Molecular Biology Reporter, 2025)

MY-1 promotes angiogenesis in the ischemic hindlimbs by regulating the stability of CDC42 via PSMD14 - Xian Ding; Yuxin Zhang; Yuting Zeng; Qianlin Li; Sijie Qiu; Ping Xiao; Xin Luo; Jiaping Chen; Qianwen Deng; Dehong Yang; Yanli Zhang; Wenjuan Yan (Angiogenesis, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

Isolation of dihydroagarofuran sesquiterpene from the fruits of Tripterygium hypoglaucum and evaluation of their anti-inflammatory activity - Shi-Li Wu; Xing Yang; Wen-Xiu Ning; Gang-Yun Wu; Xin-Yu Dai; Yu Zhang; Duo-Zhi Chen; Xiao Ding; Hong-Ping He; Wei Zhou; Xiao-Jiang Hao (Phytochemistry, 2025)

A dynamic boronic ester/hydrogen bonding enriched binder with self-healing chemistry for silicon anodes in lithium-ion batteries - Jiajing He; Wei Ding; Luyi Xiao; Junyi Zhang; Xiaole Yang; Weiwei Sun; Yong Wang; Li-Ping Lv (Chemical Engineering Journal, 2025)

Genome-wide identification and expression analysis of RWP-RK genes in Pyropia haitanensis reveals their roles in gametogenesis - Hong‑Chang Ding; Hui-Ping Ma; Long-Chen Tang; Xing‑Hong Yan (Journal of Applied Phycology, 2025)

Distribution characteristics and risk assessment of hexabromocyclododecanes in soil from e-waste dismantling areas - Jun Pan; Ping Ding; Jiaji Zhang; Chushan Huang; Lijuan Zhang; Wei Huang; Yuqing Fan; Guocheng Hu (Environmental Geochemistry and Health, 2025)

Intercropping enhances stable soil organic carbon pool through macroaggregate protection and biochemical recalcitrance interactions - Ding Wang; Wenchun Yu; Chunyan Ming; Linkang Chen; Ping Zhao; Xiaojun Shi; Zhengxiong Zhao; Maopan Fan; Guangqiang Long (Agriculture, Ecosystems & Environment, 2025)

Senescence of dental pulp stem cells: phenotypes, underlying mechanisms and regulatory molecules - Ping Zhang; Yu Cui; Zekun Li; Luyun Liu; Xinjuan Liu; Xiaoling Ding; Gang Ding (Human Cell, 2025)

Integrating nutrient balance, environmental footprints and nutrient optimization strategies for sustainable potato production system in China - Hanyou Xie; Ping He; Wencheng Ding; Xinpeng Xu; Yan Xu; Wentian He (Resources, Conservation and Recycling, 2025)

Sediment dynamic responses to a severe typhoon in a stratified continental shelf sea - Yi Zhong; Jun Du; Dehai Song; Yang Ding; Lulu Qiao; Yongzhi Wang; Xingmin Liu; Wenwen Yan; Ping Li; Guoqiang Xu (Ocean Modelling, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Corrigendum to “Effects of different soy protein concentrates on the structuring potential and extrudate quality of meat analogues via high moisture extrusion” [Food Structure, Volume 45, 2025, 100448] - Ding Xiang Chew; Alicia Hui Ping Theng; Raffael Osen; Jie Hong Chiang (Food Structure, 2025)

Effects of different soy protein concentrates on the structuring potential and extrudate quality of meat analogues via high moisture extrusion - Ding Xiang Chew; Alicia Hui Ping Theng; Raffael Osen; Jie Hong Chiang (Food Structure, 2025)

N,O-interlocked cavity-structured functionalized metal–organic frameworks for one-step efficient removal of highly toxic thorium from tailings wastewater - An-Min Song; Zhi Wu; Bin Lin; Meng-Jie Yang; Qing Yang; Shu-Yuan Zhang; Xiao-Xing Wang; Zhi-Hai Peng; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Bioinspired copper-doped covalent organic polymers with laccase-mimicking activity for on-site monitoring of thiram in fruit and vegetable samples - Ya Di Shi; Meng Ping Wang; Han Wu; Sai Jin Xiao; Zi Yang Yue; Ding Zhong Yuan; Xin Xin Shao; Feng Tao Yu; Li Zhang (Analytica Chimica Acta, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

Cepharanthine mitigates NIBV-induced pyroptosis via the MDA5/NF-κB/NLRP3 signaling pathway - Zhenni Liu; Ruoyun Tang; Mengbing Ding; Meiqin Wu; Ying Li; Cheng Huang; Qiurong Qi; Ping Liu; Xiaona Gao; Xiaoquan Guo (Veterinary Microbiology, 2025)

Pulmonary arterial hypertension: a long-standing and nonnegligible burden over three decades - Jia-Yong Qiu; Lu-Hong Qiu; Shen-Shen Huang; Bao-Chen Qiu; Chao Liu; Dong Ding; Yue-Jiao Ma; Yu-Ping Zhou; Chun-Yan Cheng; Meng-Yi Liu; Xiao-Wei Gong; Tong-Sheng Wang; et al. (Science Bulletin, 2025)

Bioactive homoisoflavonoids from the fibrous roots of Ophiopogon japonicus - Li-Ping Feng; Zhan-Guo Li; Qian Ding; Chun Luo; Xue-Ping Lu; Xiao-Hui Li (Phytochemistry Letters, 2025)

The effect and mechanisms of nano cerium dioxide (Nano-CeO2) on cardiovascular development in zebrafish (Danio rerio) - Yiyun Liu; Yan-Ling Liao; Jin-Xia Wang; Bao-Fu Zhang; Qi-Ping Tang; Yuan Ding; Si-Jia Zuo; Qin-Hong Zhou; De-Sheng Pei (Environmental Pollution, 2025)

Transgenerational thyroid hormone disruption in zebrafish induced by environmentally relevant concentrations of triclosan - Ping Ding; Jiayi Zhang; Xin Li; Pengcheng Ma; Guocheng Hu; Lijuan Zhang; Yunjiang Yu (Environmental Pollution, 2025)

Sustainable development of high-performance separation membranes based on green-solvent-processed 2D nanoarchitectured nanofiber/networks - Xiaobao Gong; Ping Gao; Yu Ji; Mingle Ding; Jianyong Yu; Shichao Zhang; Bin Ding (Chemical Engineering Journal, 2025)

Evolving Therapeutic Landscape of Intracerebral Hemorrhage: Emerging Cutting-Edge Advancements in Surgical Robots, Regenerative Medicine, and Neurorehabilitation Techniques - Danyang Chen; Zhixian Zhao; Shenglun Zhang; Shiling Chen; Xuan Wu; Jian Shi; Na Liu; Chao Pan; Yingxin Tang; Cai Meng; Xingwei Zhao; Bo Tao; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the most serious form of stroke and has limited available therapeutic options. As knowledge on ICH rapidly develops, cutting-edge techniques in the fields of surgical robots, regenerative medicine, and neurorehabilitation may revolutionize ICH treatment. However, these new advances still must be translated into clinical practice. In this review, we examined several emerging therapeutic strategies and their major challenges in managing ICH, with a particular focus on innovative therapies involving robot-assisted minimally invasive surgery, stem cell transplantation, in situ neuronal reprogramming, and brain-computer interfaces. Despite the limited expansion of the drug armamentarium for ICH over the past few decades, the judicious selection of more efficacious therapeutic modalities and the exploration of multimodal combination therapies represent opportunities to improve patient prognoses after ICH.

Mesenchymal stem/stromal cells-derived exosomes: possible therapeutic mechanism in inflammatory bowel disease - Zekun Li; Luyun Liu; Yuhui Sun; Xinjuan Liu; Ping Zhang; Yue Wang; Gang Ding (Human Cell, 2025)

Aged microplastics-induced growth inhibition via DNA damage, GH/IGF-1 and HPT axes disruption in zebrafish larvae - Qing Ge; Tong Zheng; Ping Ding; Zhenyuan Li; Xihua Lin; Xintong Li; Miao He; Guocheng Hu (Science of The Total Environment, 2025)

Water quality parameters inversion based on multispectral remote sensing - Yinshan Yu; Ping Ding; Haiyi Bian; Jinsong Wei; Hui Zhang (Journal of Water Process Engineering, 2025)

Fully recyclable flame-retardant PLA composites with balanced performance based on a phosphorus/nitrogen-containing zwitterion - Qiang Zhang; Xing Cao; Yan-Peng Ni; Li-Ping Zhang; Zhao Ding; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Multifunctional Sr/Zn-doped TiO2 micro/nanoporous coating enhances osseointegration by modulating signaling crosstalk of bone-related cells - Tian-Xia Zheng; Nuo-Ya Yang; Jiu-Peng Deng; Wei Dong; Li-Fang Feng; Yuanyuan-Ding; Jin-Ping Yang; Xin-Jia Cai; Yan Liu; Meng-Chun Qi (Chemical Engineering Journal, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

8 R -methoxy-9 R -hydroxyl-fumitremorgin C, a new diketopiperazine alkaloid from Haima cold seep-derived fungus Aspergillus fumigatus CYH-5 - Yi-Hao Che; Jun-Feng Wang; Xue-Feng Shi; Wen-Ping Ding; Zhi-Hui Xiao; Jia-Min Wu; Fa-Zuo Wang; Si Zhang (Natural Product Research, 2025)

Dynamic effects of Aeromonas sobria infection on intestinal morphology, microbiota and goblet cells of rainbow trout (Oncorhynchus mykiss) - Li-Ping Liu; Peng-Tian Kang; Feng-Yuan Ding; Dong-Hong Shao; Bao-Shan Wang; Juan Yang; Wen-Hui Gao; Wang-Dong Zhang; Wen-Hui Wang; Ji-Xing Liu (Aquaculture, 2025)

Prediction method of rock spalling risk in large underground cavern excavation based on Bayesian network: A case study from the Baihetan hydropower station, China - Guo-Feng Liu; Zhi-Qiang Liu; Ding-Ping Xu; Quan Jiang (Tunnelling and Underground Space Technology, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Dry season dominance of salinity’s impact on hydrogen isotope fractionation in Aegiceras corniculatum mangrove lipids - Yao-Ping Wang; Zhiguang Song; Jia Xia; Zhao-Wen Zhan; Alex L. Sessions; Shaelyn N. Silverman; Yuan Gao; Guopeng Li; Ding He (Geochimica et Cosmochimica Acta, 2025)

The Role of ICP Monitoring in Minimally Invasive Surgery for the Management of Intracerebral Hemorrhage - Ge Zhang; Yunjie Li; Danyang Chen; Zhuojin Wu; Chao Pan; Ping Zhang; Xingwei Zhao; Bo Tao; Han Ding; Cai Meng; Diansheng Chen; Wenjie Liu; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the second major stroke type, with high incidence, high disability rate, and high mortality. At present, there is no effective and reliable treatment for ICH. As a result, most patients have a poor prognosis. Minimally invasive surgery (MIS) is the fastest treatment method to remove hematoma, which is characterized by less trauma and easy operation. Some studies have confirmed the safety of MIS, but there are still no reports showing that it can significantly improve the functional outcome of ICH patients. Intracranial pressure (ICP) monitoring is considered to be an important part of successful treatment in traumatic brain diseases. By monitoring ICP in real time, keeping stable ICP could help patients with craniocerebral injury get a good prognosis. In the course of MIS treatment of ICH patients, keeping ICP stable may also promote patient recovery. In this review, we will take ICP monitoring as the starting point for an in-depth discussion.

Combining High-Throughput Screening and Machine Learning to Predict the Formation of Both Binary and Ternary Amorphous Solid Dispersion Formulations for Early Drug Discovery and Development - Tianshu Lu; Yiyang Wu; Ping Xiong; Hao Zhong; Yang Ding; Haifeng Li; Defang Ouyang (Pharmaceutical Research, 2025)

Dexmedetomidine Improves Long-term Neurological Outcomes by Promoting Oligodendrocyte Genesis and Myelination in Neonatal Rats Following Hypoxic-ischemic Brain Injury - Hang Xue; Zixuan Ding; Xiaoyan Chen; Xu Yang; Yufei Jia; Ping Zhao; Ziyi Wu (Molecular Neurobiology, 2025)

Embryonic 6:2 Fluorotelomer Alcohol Exposure Disrupts the Blood‒Brain Barrier by Causing Endothelial‒to‒Mesenchymal Transition in the Male Mice - Yunhui Xia; Junhan Chen; Ping Dong; Luqing Zhang; Yibing Ding; Weidong Ding; Xiaodong Han; Xiaojian Wang; Dongmei Li (Molecular Neurobiology, 2025)

Accurate determination of halogens in geological materials using an automated pyrohydrolysis system with a liquid nitrogen cold trap - Ding-Shuai Xue; Shun Guo; Yan-Hong Liu; Dan-Ping Zhang; Di Zhang; Xiao-Guang Li; Shan-Ke Liu (Analytica Chimica Acta, 2025)

RIPK3 activation of CaMKII triggers mitochondrial apoptosis in NIBV-infected renal tubular epithelial cells - Ying Li; Qiurong Qi; Yifei Chen; Mengbing Ding; Manzi Huang; Cheng Huang; Ping Liu; Xiaona Gao; Xiaoquan Guo; Zhanhong Zheng (Veterinary Microbiology, 2025)

Voagafries A–E, undescribed indole alkaloids with anti-glioma activity from Voacanga africana - Cai-Feng Ding; Ma-Long Qin; Kun-Ying Zhao; Wen Gao; Shan-Ze Yin; Xian-Guang Hu; Gui-Guang Cheng; Rong-Ping Zhang; Wei-Yan Hu (Phytochemistry, 2025)

Synergistic neurotoxicity of clothianidin and photoaged microplastics in zebrafish: Implications for neuroendocrine disruption - Ping Ding; Yajing Han; Yanan Sun; XiaoXia Chen; Qing Ge; Wei Huang; Lijuan Zhang; Adela Jing Li; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Co-benefits of a customized nutrient management approach tailored to smallholder farming for cabbage (Brassica oleracea L.) - Mengjiao Liu; Binggeng Yang; Xiya Wang; Xinpeng Xu; Wencheng Ding; Ping He; Wei Zhou (European Journal of Agronomy, 2025)

One-step open-ring strategy for constructing sandwich-like metal–organic framework with highly selective removal of thorium - Meng-Jie Yang; An-Min Song; Qing Yang; Zhi Wu; Bin Lin; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Assessing the soil moisture-vegetation mutual feedback relationship in different climatic regions of mainland China - Zhaoqiang Zhou; Ping Xue; Xin Zhou; Tian Wang; Yibo Ding; Yiyang Zhao; Peng Chen; Xiaowen Wang (CATENA, 2025)

n-Alkanes δ13C and salinity correlation in mangrove Aegiceras corniculatum leaves and surface sediments from Zhanjiang estuaries, China - Guifang Cai; Zhao-Wen Zhan; Zhiguang Song; Yao-Ping Wang; Jia Xia; Ding He (Chemical Geology, 2025)

Inhibition of odor generation during the composting process of fecal sludge from rural toilets by decomposed compost backfilling - Lin Lin; Xingfeng Yang; Yilin Shen; Ping Zhu; Shiyu Niu; Shakib Alghashm; Guoji Ding; Deli Wu; Xiaowei Li (Bioresource Technology Reports, 2025)

Application of sex-specific markers in identifying the sex of Pyropia haitanensis from different sources - Hong-Chang Ding; Hui-Ping Ma; Long-Chen Tang; Xing‑Hong Yan (Journal of Applied Phycology, 2025)

Causes of Atypical Meiyu in the Lower Yangtze River Basin in 2022: Subseasonal Perspective and Predictions - Zhiqi Zhang; Ping Liang; Yajing Liu; Yang Wu; Lingfeng Tao; Qi Chen; Yihui Ding (Journal of Meteorological Research, 2025)

Formation and characterization of artificial gynogenetic northern snakehead (Channa argus) induced by inactivated sperm of mandarin fish (Siniperca chuatsi) - Anmin Liao; Shuxin Zhang; Qiuyan Yu; Yude Wang; Huifang Tan; Ping Wu; Yue Ding; Biao Hu; Wuxia Liu; Min Tao; Chun Zhang; Qinbo Qin; et al. (Aquaculture, 2025)

Amino modifications exacerbate the developmental abnormalities of polystyrene microplastics via mitochondria-mediated apoptosis pathway in zebrafish larvae - Jiayi Zhang; Guocheng Hu; Hongzhi Guo; Wenhui Yang; Xintong Li; Yuyang Ni; Miao He; Ping Ding; Yunjiang Yu (Science of The Total Environment, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Heavy metal dynamics in riverine mangrove systems: A case study on content, migration, and enrichment in surface sediments, pore water, and plants in Zhanjiang, China - Xuemei Ma; Zhiguang Song; Yao-Ping Wang; Sibo Wang; Zhao-Wen Zhan; Ding He (Marine Environmental Research, 2025)

Influence of ground source heat exchanger operation modes on multi-borehole mid-deep ground source heat pump system performance - Zuohai Wang; Jian Ding; Mingzhi Yu; Yudong Mao; Ke Zhu; Wenke Zhang; Ping Cui; Zhaoyi Zhuang; Shiyu Zhou (Geothermics, 2025)

Prediction of hydrate formation boundaries in pure water and salt/alcohol containing systems based on prior knowledge and artificial intelligence - Shu-Kai Chen; Xiao-Fang Lv; Jian-Ping Ding; Yang Liu; Ji-Miao Duan; Hui Du; Chuan-Shuo Wang; Ming-Guo Peng; Qian-Li Ma; Shi-dong Zhou (Fuel, 2025)

Study on the condensate gas phase behavior in Nano-porous media - Ping Wang; Yuepeng Jia; Junjie Zhong; Wensong Huang; Wei Ding; Peng Lian; Xiangwen Kong; Li Liu; Zibin Zhao (Fuel, 2025)

Black goji anthocyanin-loaded emulsion film stabilized by rice protein hydrolysate complexes as pH-sensitive indicator for salmon freshness - Wei Dai; Ping Yin; Qinlu Lin; Ming Tian; Ming Wu; Jian Ding; Xiaoyi Jiang; Yong Fang (Food Packaging and Shelf Life, 2025)

Fiscal decentralization's impact on carbon emissions and its interactions with environmental regulations, economic development, and industrialization: Evidence from 288 cities in China - Zhongyao Cai; Xuhui Ding; Ziqian Zhou; Aixi Han; Siqi Yu; Xinyu Yang; Ping Jiang (Environmental Impact Assessment Review, 2025)

Chronic polyaluminum chloride perturbation shaped community assembly patterns: An overlooked mechanism of nitrogen removal inhibition - Nan-ping Wu; Qian Zhang; Hong-yu Wang; Yun-jie Zhang; Meng Li; Bin Ji; Yufei Bao; Bing Lin; Yu-wei Ding; Qi He; Jia-jing Chen (Chemical Engineering Journal, 2025)

Sevoflurane postconditioning mitigates neuronal hypoxic-ischemic injury via regulating reactive astrocytic STAT3 protein modification - Yufei Jia; Yanhong Song; Hang Xue; Xingyue Li; Yinong Zhang; Shiyue Fan; Xu Yang; Zixuan Ding; Yue Qiu; Ziyi Wu; Ping Zhao (Chemico-Biological Interactions, 2025)

Pharmacokinetics of seven major components in Aβ1-42-treated rats after oral administration of an aqueous extract of Curculiginis Rhizoma and Epimedii Folium - Junzuo Zheng; Jun Wang; Linlin Chen; Xuelian Jiang; Xuesong Zhang; Wenqi Ai; Yuman Xie; Ping Wang; Zhou Lan; Xiaoping Ding (Journal of Natural Medicines, 2025)

Microalgae biomass: A multi-product biorefinery solution for sustainable energy, environmental remediation, and industrial symbiosis - Safa Senan Mahmod; Maha Mohammad AL-Rajabi; Peer Mohamed Abdul; Gongtao Ding; Kamrul Fakir Kamarudin; Ahmad Anas Nagoor Gunny; Jian Ping Tan; Mohd Sobri Takriff (Algal Research, 2025)

Abundance of microplastics and its ecological risk assessment in coral reef regions of Peninsular Malaysia - Kok Ping Lim; Chengjun Sun; Sumiani Yusoff; Jinfeng Ding; Kar Hoe Loh; Jingxi Li; Phaik Eem Lim (Marine Pollution Bulletin, 2024)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

The influence of steep faults at various avoidance distances on the stability of hard rock caverns: Physical model experiments and DEM simulations - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Shi-jie Chen; Guang-liang Feng; Quan Jiang; Xin-hao Zhu; Shu-qian Duan (Tunnelling and Underground Space Technology, 2024)

Ecological risks caused by neonicotinoid pesticides in sediments: A case study of freshwater basins in China - Xiaoxia Chen; Pengchong Wen; Yanan Sun; Ping Ding; Haibo Chen; Hui Li; Xin Li; Limei Cai; Yunjiang Yu; Guocheng Hu (Science of The Total Environment, 2024)

Sediment dynamic responses of coastal salt marsh to wind waves and swells in a semi-open tidal flat - Shaoxin Chen; Weifang Gu; Benwei Shi; Yining Chen; Antonis Chatzipavlis; Jiawei Ding; Wenxiang Zhang; Qi Chen; Ya Ping Wang (Science of The Total Environment, 2024)

Bearing performance and failure mechanisms of HSCM piles in marine soft soil under lateral loads - Hang Cen; Jun-nan Zhao; Zhong-ling Zong; De-long Huang; Ding-wen Zhang; Hui-yue Wang; Ai-ping Tang (Ocean Engineering, 2024)

Recent development on drought propagation: A comprehensive review - Zhaoqiang Zhou; Ping Wang; Linqi Li; Qiang Fu; Yibo Ding; Peng Chen; Ping Xue; Tian Wang; Haiyun Shi (Journal of Hydrology, 2024)

Advances on a SPTC/JTC/ADR system for sub-Kelvin cooling - Zhichao Chen; Ping Liu; Yanan Li; Lei Ding; Zhenhua Jiang; Shaoshuai Liu; Yinong Wu; Wei Dai (International Journal of Refrigeration, 2024)

Groundwater resistant gene accumulation in mining-agriculture complex zones: Insights from metagenomic analysis of subterranean mineral and terrestrial agricultural interactions - Rui Wang; Ping Lu; Fangfang Chen; Yanchang Huang; Haoran Ding; Tianhang Cheng (Environmental Research, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Neuroprotection by tetramethylpyrazine and its synthesized analogues for central nervous system diseases: a review - Fan Feng; Ding-Qiao Xu; Shi-Jun Yue; Yan-Yan Chen; Yu-Ping Tang (Molecular Biology Reports, 2024)

Shear wave elastography characteristics of the gastrocnemius muscle in postural instability gait disorder vs tremor dominant Parkinson’s disease patients - Chang Wei Ding; Cai Shan Wang; Ping Zhao; Ming Lei Chen; Ying Chun Zhang; Chun Feng Liu (Acta Neurologica Belgica, 2024)

Tracking the transformation of extracellular polymeric substances during the ultraviolet/peracetic acid disinfection process: Emphasizing on molecular-level analysis and overlooked mechanisms - Yizhe Ding; Qiya Sun; Qian Ping; Lin Wang; Yongmei Li (Water Research, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Analysis of microclimate and spatial geometry correlation of squares in cold urban settlements: A study in Urumqi - Li Zhang; Ping Yuan; Yingjie Ding (Urban Climate, 2024)

Bisphenol AP inhibits mouse oocyte maturation in vitro by disrupting cytoskeleton architecture and cell cycle processes - Caiyun Wu; Zhiming Ding; Chen Yang; Cong Ma; Huilei Chen; Ping Zhou; Zuying Xu; Huifen Xiang (Toxicology and Applied Pharmacology, 2024)

Brominated flame retardants in surface sediment from Western Guangdong, South China: Occurrence, distribution and toxicity in Caenorhabditis elegans - Xiaoxia Chen; Ping Ding; Haibo Chen; Tingzhen Li; Min Zhang; Yunjiang Yu; Guocheng Hu (Journal of Environmental Sciences, 2024)

Characteristics of iron-sulfur metabolism and acid-producing microorganisms in groundwater contaminated by acid mine drainage in closed coal mines - Yanchang Huang; Ping Lu; Feng Zhang; Hao Chen; Wenliang Zhang; Linlin Lin; Hepeng Xu; Haoran Ding; Tianhang Cheng (Groundwater for Sustainable Development, 2024)

Methylmercury chloride inhibits meiotic maturation of mouse oocytes in vitro by disrupting the cytoskeleton - Zhiming Ding; Yan Sun; Caiyun Wu; Cong Ma; Hongzhen Ruan; Yingying Zhang; Yan Xu; Ping Zhou; Yunxia Cao; Zuying Xu; Huifen Xiang (Food and Chemical Toxicology, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Upgrading algae waste into 3-D bio-cathode to enhance acetate synthesis by microbial electrosynthesis - Qihao Cao; Chao Zhang; Ping Wu; Peng Ding; Haoran Sun; Sili Qing; Wenlei Zhu; Zhiyong Zheng; Yan Zhang; Hongbo Liu; He Liu (Chemical Engineering Journal, 2024)

Direct near-infrared laser ignition of CL-20 by introducing DATNBI as a bi-functional additive: Energetic photosensitizer and self-assembly stimulator - Ping Ye; Heng Ding; Bo Yang; Weimiao Wang; Xiaodong Li; Zhiqiang Qiao; Rui Li; Guangcheng Yang; Guoqing Lv (Chemical Engineering Journal, 2024)

The effect of pegmatite veins on fracture behaviors of granite in a deep large underground cavern - Yuelin Xia; Ding-Ping Xu; Quan Jiang; Jianbin Xie; Zhiguo Li (Bulletin of Engineering Geology and the Environment, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Bisphenol M inhibits mouse oocyte maturation in vitro by disrupting cytoskeleton architecture and cell cycle processes - Huilei Chen; Yang Liu; Yue Huang; Pin Zhang; Danli Du; Wenhua Yu; Caiyun Wu; Hongzhen Ruan; Ping Zhou; Zhiming Ding; Huifen Xiang (Reproductive Toxicology, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Discovery of anti-melanogenic components in persimmon (Diospyros kaki) leaf using LC-MS/MS-MN, AlphaFold2-enabled virtual screening and biological validation - Jiazheng Liu; Ting Xu; Jianjun Ding; Haoyue Wen; Jieru Meng; Qing Liu; Xiaomei Liu; Wei Zhang; Guo-Yuan Zhu; Zhi-Hong Jiang; Jin Gao; Li-Ping Bai (Food Chemistry, 2024)

Integrated biomarker-based ecological risks assessment of tadpole responses to tris(2-chloroethyl) phosphate, tris(1-chloro-2-propyl) phosphate, and their combined environmental exposure - Wen-Qi Xie; Zi-Ying Wang; Yi-Ge Xie; Jia-Jun Hao; Xin-Dan Cao; Zi-Yong Xiang; Lu-Ping Lou; Guo-Hua Ding (Environmental Pollution, 2024)

Unravelling ice growth characteristics beneath cloud tops with joint analysis of airborne Ka-band radar and Himawari observations - Shuangzhi You; Delong Zhao; Haoran Li; Wei Zhou; Yuanmou Du; Ping Tian; Jiujiang Sheng; Wei Xiao; Fei Wang; Hui He; Mengyu Huang; Deping Ding; et al. (Atmospheric Research, 2024)

Residues of veterinary drugs and heavy metal contamination in livestock and poultry meat from Hunan Province, China - Ying Yu; Jun Xiang; Zongwu Meng; Kermue Vasco Jarnda; Qi Liu; Ping Ding (Food Additives & Contaminants Part B-Surveillance, 2024)

Levels, sources, and health risk assessment of phthalate acid esters in indoor dust of various microenvironments in university - Jun Pan; Xin Li; Ping Ding; Haojie Luo; Sha Cai; Qing Ge; Liuyi Zhang; Guocheng Hu (Chemosphere, 2024)

Transcriptome profile of sex-related gene expression and effects of cyp19a1 siRNA-silencing on sex differentiation and determination in yellow perch - Ding-Kun Xie; Han-Ping Wang; Rafidah Othman; Hong Yao; Paul O'Bryant; Dean Rapp; Yi-Jiang Hong (Aquaculture, 2024)

Megastigmane glycosides from the traditional Uighur medicine Cydonia oblonga Mill. - Shan-Shan Jiao; Rui-Feng Ding; Xin Yuan; Xiao-Ping He; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Residual distribution and risk assessment of neonicotinoids in urban green space soils of the pearl river delta, South China: A socioeconomic analysis - Haojie Luo; Yanan Sun; Jun Pan; Ping Ding; Pengchong Wen; Yunjiang Yu; Limei Cai; Guocheng Hu (Journal of Hazardous Materials, 2024)

Aged polystyrene microplastics exposure affects apoptosis via inducing mitochondrial dysfunction and oxidative stress in early life of zebrafish - Ping Ding; Chongdan Xiang; Qian Yao; Xintong Li; Jiayi Zhang; Renli Yin; Lijuan Zhang; Adela Jing Li; Guocheng Hu (Journal of Environmental Management, 2024)

Visible light irradiation enhanced sulfidated zero-valent iron/peroxymonosulfate process for organic pollutant degradation - Jialu Xu; Hao Cheng; He Zhang; Chengyou Sun; Haoran Tian; Jikun Yang; Yingxin Ding; Xuan Lin; Ping Wang; Chao Huang (Environmental Research, 2024)

Source apportionment and wet scavenging ability of atmospheric black carbon during haze in Northeast China - Shuo Ding; Delong Zhao; Ping Tian; Mengyu Huang (Environmental Pollution, 2024)

Redox-active “Structural Pillar” molecular doping strategy towards High-Performance polyaniline-based flexible supercapacitors - Wei Ding; Luyi Xiao; Yong Wang; Li-Ping Lv (Chemical Engineering Journal, 2024)

Island biogeography of mixed‐species bird flocks: A gregarious nuclear species influences island area effects - Ari Martínez; Liping Zhou; Xingfeng Si; Ping Ding; Eben Goodale (Journal of Biogeography, 2024)
Aim Island biogeography theory has been extended to include various species interactions, but has yet to consider intraguild mutualisms. We compare species‐area relationships for mixed‐species flocks to those for the entire bird community and determine how ‘nuclear’ species, those important to flock formation or cohesion, which often have functional traits such as intraspecific gregariousness, influence flock species richness. We hypothesized that mixed flocks would only form on large islands where nuclear species are present. On the subset of larger islands, we expected flock species richness to rise with island area, reflecting a larger pool of species. Location Thirty‐one islands of varying area in the reservoir system of Thousand Island Lake, China. Taxon The resident forest bird community and its subcomponent of flock participants. Similar to elsewhere in southern China, the primary nuclear species was Huet's Fulvetta ( Alcippe hueti ), which averaged 20 individuals per flock, and led the flocks when present. Methods Birds were surveyed in the winter of 2017 and the autumn of 2021. Results The probability for a flock to be present, and the species richness of birds per transect, increased with island area, but the species richness of flocks did not. Flocks with Huet's Fulvetta were only found on islands larger than 30 ha. Flocks on smaller islands formed around secondary nuclear species typical of northern Chinese flocks. Main Conclusion Gregariousness as a functional trait may make nuclear species more susceptible to disappearing in small fragments, leading to flock collapse. The extreme gregariousness of fulvettas may also act to increase competition in the flocks they lead and limit the flocks' species richness. We encourage further comparisons of the species‐area curves of mixed‐species flocks and whole bird communities to better understand the influence of flocks on community assembly and species diversity.

Exendin-4, a glucagon-like peptide-1 receptor agonist, alleviates muscular dysfunction and wasting in a streptozotocin-induced diabetic mouse model compared to metformin - Ding-Cheng Chan; Yuan-Cheng Lin; Huei-Ping Tzeng; Rong-Sen Yang; Meng-Tsan Chiang; Shing-Hwa Liu (Tissue and Cell, 2024)

Inventorization and ecological risk assessment of tetrabromobisphenol A and hexabromocyclododecane in sediments from Guangdong coastal area of South China Sea - Xiaoxia Chen; Xin Li; Yuqing Fan; Guocheng Hu; Hang Xie; Xiaoyan Chen; Ping Ding; Yao Dang; Xiyuan Hu; Qinghua Chen (Science of The Total Environment, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Integrated analysis reveals the immunotoxicity mechanism of BPs on human lymphocytes - Qiujin Zhang; Mengzhen Li; Ping Wang; Xiao Lin; Keng Po Lai; Zhixiang Ding (Chemico-Biological Interactions, 2024)

Functional metabolomics characterizes the contribution of farnesoid X receptor in pyrrolizidine alkaloid-induced hepatic sinusoidal obstruction syndrome - Aizhen Xiong; Longhui Lu; Kaiyuan Jiang; Xiaoning Wang; Yan Chen; Xunjiang Wang; Wei Zhang; Yuzheng Zhuge; Wendong Huang; Lujin Li; Qi Liao; Fan Yang; et al. (Archives of Toxicology, 2024)

Foliar uptake screening: A promising strategy for identifying wheat varieties with low lead accumulation - Liu-Xu Feng; Yu-Ning Li; Li-Ping Geng; Pei-Pei Gao; Xiang-Yu Li; Ding-Hao Li; Gui-Li Hua; Quan-Li Zhao; Wen-Ju Liu; Pei-Ying Xue (Science of The Total Environment, 2024)

Electrokinetic energy conversion and desalination of an asymmetric nanopore with applied temperature gradients - Ding-Cheng Zheng; Tsung-Yen Tsou; Jyh-Ping Hsu; Hsiu-Yu Yu (Desalination, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Estimating the Mechanical Properties of Rocks and Rock Masses Based on Mineral Micromechanics Testing - Xiu-yang Liu; Ding-ping Xu; Shao-jun Li; Shu-qian Duan; Huai-sheng Xu; Quan Jiang; Shi-li Qiu (Rock Mechanics and Rock Engineering, 2024)

Exploring the Impact of Biodegradable and Nonbiodegradable Microplastic Particles on Pb Absorption in Maize - Dan QIU; Chunmiao LU; Huarong SUN; Chaohang LI; Guangqiang LONG; Ping ZHAO; Yijun LONG; Yue DING; Cuixia SU; Zhengyan PAN; Yuefang CAO; Shuran HE (Journal of Soils and Sediments, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

In-situ comprehensive investigation of deformation mechanism of the rock mass with weak interlayer zone in the Baihetan hydropower station - Jin-Shuai Zhao; Bing-Rui Chen; Quan Jiang; Ding-Ping Xu; Ben-Guo He; Shu-Qian Duan (Tunnelling and Underground Space Technology, 2024)

Intestinal microbiota via NLRP3 inflammasome dependent neuronal pyroptosis mediates anxiety-like behaviour in mice exposed to 3.5 GHz radiofrequency radiation - Gui-qiang Zhou; Xing Wang; Peng Gao; Tong-zhou Qin; Ling Guo; Zhao-wen Zhang; Zhi-fei Huang; Jia-jin Lin; Yun-tao Jing; Hao-nan Wang; Chun-ping Wang; Gui-rong Ding (Science of The Total Environment, 2024)

P53 upregulation by USP7-engaging molecular glues - Zhaoyang Li; Ziying Wang; Chao Zhong; Hang Zhang; Rui Liu; Ping An; Zhiqiang Ma; Junmei Lu; Chengfang Pan; Zhaolin Zhang; Zhiyuan Cao; Jianyi Hu; et al. (Science Bulletin, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Soft sensor enabled real-time chemical dosing control systems for wastewater treatment: From hybrid model to full-scale application - Hualei Ding; Mingyue Tang; Qing Huang; Ping Yang; Zhen Liu; Xuejun Bi; Abhilash Nair; Xiaodong Wang (Journal of Water Process Engineering, 2024)

α-Fe2O3 nanorods on CoFe-LDH@MX via interfacial interactions for Congo red removal: Experimental and mechanistic studies - Xianyong Hong; Mingxing Shi; Linrui Li; Zhoutian Ding; Zhiren Zhao; Ping Du; Mingzhu Xia; Fengyun Wang (Journal of Environmental Chemical Engineering, 2024)

Bacterial structures and their associated ARGs in Shanghai subway air, China - Lijun Zhang; Xiaojing Li; Yongping Liu; Yi Zheng; Lisha Shi; Yichen Ding; Jian Chen; Ping Xiao (Journal of Aerosol Science, 2024)

A novel olfactory biosensor based on ZIF-8@SWCNT integrated with nanosome-AuNPs/Prussian blue for sensitive detection of hexanal - Jing Liu; Yan Ping Chen; Penglin He; Ziyu Ding; Yun Guo; Songhe Cui; Chao Ma; Zhiping Xie; Sun Xia; Yin Zhang; Ye Liu; Yuan Liu (Food Chemistry, 2024)

Photoaged polystyrene microplastics result in neurotoxicity associated with neurotransmission and neurodevelopment in zebrafish larvae (Danio rerio) - Xintong Li; Tong Zheng; Jiayi Zhang; Haibo Chen; Chongdan Xiang; Yanan Sun; Yao Dang; Ping Ding; Guocheng Hu; Yunjiang Yu (Environmental Research, 2024)

The influence of the preheated PSf substrate on COF-LZU1 layer formation and the performance for salt and pharmaceutical rejection - Fan-xin Kong; Shi-yuan Zhang; Ding-wen Zhang; Ping Xia; Jin-fu Chen (Desalination, 2024)

Chitosan-based injectable hydrogel with multifunction for wound healing: A critical review - Aiqin Li; Bin Ma; Shiyao Hua; Rui Ping; Lu Ding; Bingren Tian; Xu Zhang (Carbohydrate Polymers, 2024)

Implantation of Adipose-Derived Mesenchymal Stromal Cells (ADSCs)-Lining Prosthetic Graft Promotes Vascular Regeneration in Monkeys and Pigs - Xiao Zuo; Pengfei Han; Ding Yuan; Ying Xiao; Yushi Huang; Rui Li; Xia Jiang; Li Feng; Yijun Li; Yaya Zhang; Ping Zhu; Hongge Wang; et al. (Tissue Engineering and Regenerative Medicine, 2024)
Background: Current replacement procedures for stenosis or occluded arteries using prosthetic grafts have serious limitations in clinical applications, particularly, endothelialization of the luminal surface is a long-standing unresolved problem. Method: We produced a cell-based hybrid vascular graft using a bioink engulfing adipose-derived mesenchymal stromal cells (ADSCs) and a 3D bioprinting process lining the ADSCs on the luminal surface of GORE-Tex grafts. The hybrid graft was implanted as an interposition conduit to replace a 3-cm-long segment of the infrarenal abdominal aorta in Rhesus monkeys. Results: Complete endothelium layer and smooth muscle layer were fully developed within 21 days post-implantation, along with normalized collagen deposition and crosslinking in the regenerated vasculature in all monkeys. The regenerated blood vessels showed normal functionality for the longest observation of more than 1650 days. The same procedure was also conducted in miniature pigs for the interposition replacement of a 10-cm-long right iliac artery and showed the same long-term effective and safe outcome. Conclusion: This cell-based vascular graft is ready to undergo clinical trials for human patients.

Adsorption of Cu (II) and Zn (II) in aqueous solution by modified bamboo charcoal - Huiyan Ma; Wen Xu; Ping Wang; Yi Ding; Sijie Zhou (Environmental Geochemistry and Health, 2024)

Change Characteristics and Source Apportionment of Ozone Pollution in Sanya City in 2019 - Ding Huang; Ping Wang; Fang Lu; Youzhi Zhao; Wenci Ding; Jiaxin Du (Aerosol Science and Engineering, 2024)

Excavation response and reinforcement practice of large underground caverns within high-stress hard rock masses: The case of Shuangjiangkou hydropower Station, China - Xiu-Yang Liu; Ding-Ping Xu; Quan Jiang; Xing-Dong Ma (Tunnelling and Underground Space Technology, 2024)

Dendritic copper oxide catalyst engineering weak-polarity Cu-O bond for high-efficiency nitrate electroreduction - Haiyan Ma; Jing Yan; Junjie Xu; Ping Chen; Jiaou Qi; Yue Ding; Shaowei Zhang; Lilin Lu (Journal of Hazardous Materials, 2024)

Investigation into the potential mechanism of Bacillus amyloliquefaciens in the fermentation of broad bean paste by metabolomics and transcriptomics - Hongbin Lin; Shiqi Liao; Zesu Zhou; Ziting Yan; Jianhua Zhao; Yue Xiang; Min Xu; Jie Zhao; Ping Liu; Wengwu Ding; Yu Rao; Jie Tang (Food Research International, 2024)

Straw management adopted by large farms sustains grain yield but mitigates greenhouse gas emissions - Zhenzhen Li; Yong Lin; Zheng-Rong Kan; Sana ur Rehman; Atta Mohi Ud Din; Feng-Min Li; Shixiang Zhang; Ping Wu; Yingfu Ding; Chensheng Xu; Congying Rao; Huaxin Dai; et al. (Field Crops Research, 2024)

Combined neurotoxicity of aged microplastics and thiamethoxam in the early developmental stages of zebrafish (Danio rerio) - Yanan Sun; Ping Ding; Jiayi Zhang; Kexin Sun; Xintong Li; Qing Ge; Yao Dang; Yunjiang Yu; Guocheng Hu (Environmental Pollution, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

A novel brain targeting MnOx-based MI-3 nanoplatform for immunogenic cell death initiated high-efficiency antitumor immunity against orthotopic glioblastoma - Xuejie Wang; Zhanfeng Wang; Ping'an Ma; Sainan Liu; Meifang Wang; Ping Chen; Binbin Ding; Jun Lin (Chemical Engineering Journal, 2024)

A New Perspective on the Semi-quantitative Meso-structural Failure Mechanism of Deep Weak Interlayer Zone Under Different Stress Paths - Shu-Qian Duan; Po Gao; Ding-Ping Xu; Bei Cao; Guo-feng Liu; Quan Jiang; Shi-Li Qiu; Jie-Cheng Xiong (Rock Mechanics and Rock Engineering, 2024)

Analysis on the causes of massive stranding of Yellow Sea green tide on Lianyungang and Rizhao coasts in 2022 - Lingjuan Wu; Juan Huang; Yi Ding; Guiyan Liu; Shuai Huang; Song Gao; Chao Yuan; Jiangling Xu; Ping Wu; Rui Huang; Ruobing Wen; Jie Mei (Journal of Oceanology and Limnology, 2024)

Application of artificial intelligence in (waste)water disinfection: Emphasizing the regulation of disinfection by-products formation and residues prediction - Yizhe Ding; Qiya Sun; Yuqian Lin; Qian Ping; Nuo Peng; Lin Wang; Yongmei Li (Water Research, 2024)

New diketopiperazine alkaloids from the Haima cold seep-derived fungus Toxicocladosporium sp. CYH-18 - Yi-Hao Che; Jun-Feng Wang; Wen-Ping Ding; Zhi-Hui Xiao; Xue-Feng Shi; Jia-Min Wu; Fa-Zuo Wang; Si Zhang (Phytochemistry Letters, 2024)

Application of iron tailings in the coagulation of landfill leachate by bipolar membrane electrodialysis - Yanchao Jin; Guodong Wang; Zheng Li; Chun-Yan Lin; Li-Ping Li; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Journal of Cleaner Production, 2024)

Nickel phosphide cocatalyst and carbon defects simultaneously boosting the photocatalytic hydrogen production over carbon nitride - ChuChang Mao; Qinghua Qu; Fada Li; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Ping Zhang; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

The 2022 Extreme Heatwave in Shanghai, Lower Reaches of the Yangtze River Valley: Combined Influences of Multiscale Variabilities - Ping Liang; Zhiqi Zhang; Yihui Ding; Zeng-Zhen Hu; Qi Chen (Advances in Atmospheric Sciences, 2024)

Island biogeography of soundscapes: Island area shapes spatial patterns of avian acoustic diversity - Peng Han; Yuhao Zhao; Yi Kang; Ping Ding; Xingfeng Si (Journal of Biogeography, 2024)
Aim The equilibrium theory of island biogeography predicts the positive species–area relationship and the negative species–isolation relationship, resulting in higher species richness on large and close islands. Unlike species richness, soundscape diversity integrates sound from various sources (e.g. biophony, geophony and anthrophony). However, how soundscape diversity varies with island area and isolation still needs to be tested. Here, we explored the island biogeography of bird soundscapes and the determinants of island attributes in shaping bird diversity and soundscape diversity. Location Thousand Island Lake, Zhejiang, China. Taxon Birds. Methods We recorded avian soundscapes by audio recorders and censused bird diversity by line transects on 20 land‐bridge islands. We calculated four acoustic indices (acoustic complexity index, bioacoustic index, acoustic evenness index and acoustic entropy index) to assess acoustic richness, evenness and heterogeneity to explore the soundscape diversity of birds. We used multiple linear regressions, spatial autoregressions and piecewise structural equation models to examine the relationships between bird richness and acoustic diversity, and island attributes. Results We found positive diversity–area relationships for avian soundscapes. Larger islands had more vocal species and higher habitat diversity, which led to an increment in the richness and unevenness of avian soundscapes on large islands. Acoustic evenness decreased with increasing isolation (distance to the mainland). Main Conclusions Soundscapes on large islands are more diverse than those on small islands. Rich acoustic assemblages and heterogeneous habitats promote increased soundscape diversity on islands. Conversely, the lack of vocal contributors, resulting in a decrement in the communication of acoustic signals, can create a lower soundscape diversity on small and remote islands. Our study emphasizes the necessity of examining both species and habitat diversity in island biogeography for better understanding the underlying mechanisms determining biological soundscapes on islands.

Spatiotemporal evolution and influencing factors of surface urban heat island footprint across different-sized cities - Hongchao Xu; Chunlin Li; Yuanman Hu; Hao Wang; Ding Wen; Zhenxing Li; Xiaoying Ping; Qiuyue Wang; Qi Li (Urban Climate, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Puerarin alleviates hyperosmotic stress-induced oxidative stress, inflammation, apoptosis and barrier damage of human corneal epithelial cells by targeting SIRT1/NLRP3 signaling - Yue Dong; Yin-Yin Ding; Wei-Ping Gao (Toxicology in Vitro, 2024)

Understanding District Heating Networks Vulnerability: A Comprehensive Analytical Approach with Controllability Consideration - Ding Mao; Peng Wang; Yi-Ping Fang; Long Ni (Sustainable Cities and Society, 2024)

Photoaging enhances combined toxicity of microplastics and tetrabromobisphenol A by inducing intestinal damage and oxidative stress in Caenorhabditis elegans - Haibo Chen; Xiaoxia Chen; Ping Ding; Yulun Gu; Yongqi Jiang; Xintong Li; Guocheng Hu; Liangzhong Li; Chen Wang; Jun Yu; Hui Li (Science of The Total Environment, 2024)

Metabolomics analysis to interpret changes in physiological and metabolic responses to chronic heat stress in Pekin ducks - Xiangyi-Yi Zeng; Arshad Javid; Gang Tian; Ke-Ying Zhang; Shi-Ping Bai; Xue-Mei Ding; Jian-Ping Wang; Li Lv; Yue Xuan; Shan-Shan Li; Qiu-Feng Zeng (Science of The Total Environment, 2024)

Age and sedimentology of a Late Pleistocene dammed paleolake in the middle Yarlung Tsangpo River, southern Tibetan Plateau - Huiying Wang; Ping Wang; Gang Hu; Bo Xu; Renmao Yuan; Lingfan Shi; Ziyue Ding (Quaternary International, 2024)

Seismic data, cross-section balancing, and hydrocarbon prospectivity of the western Sulaiman fold belt, northwest Pakistan - Saif-ur-Rehman K. Jadoon; Lin Ding; Ishtiaq A.K. Jadoon; Jabir Nazir; Fan Ping (Marine and Petroleum Geology, 2024)

Environmentally persistent free radicals on photoaged microplastics from disposable plastic cups induce the oxidative stress-associated toxicity - Hanlin Cao; Ping Ding; Xintong Li; Chushan Huang; Xin Li; Xiaoxia Chen; Lijuan Zhang; Jianying Qi (Journal of Hazardous Materials, 2024)

Revealing the formation mechanisms of key flavors in fermented broad bean paste - Yue Xiang; Binbin Zhou; Chunyan Jiang; Zhirui Tang; Ping Liu; Wenwu Ding; Hongbin Lin; Jie Tang (Food Research International, 2024)

Effect of egg white protein on the protein structure of highland barley noodles during processing - Xiangli Ding; Zhen-Yang Quan; Wen-Ping Chang; Lun Li; Jian-Ya Qian (Food Chemistry, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Effects of mixed normative feedback strategies on residents' energy conservation in shared spaces - Jiaolan Zhu; Jie Li; Ping Liu; Yongtao Shang; Zhikun Ding; Md Morshed Alam (Energy and Buildings, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Rapidly recyclable, monomer recovery and flame-retardant bio-based polyimine networks - Hongliang Ding; Jue Wang; Ping Yu; Hongfei He; Haiyue Wang; Wei Zhang; Liancong Wang; Yun Lei; Bin Yu (Chemical Engineering Journal, 2024)

Rutin, Puerarin and Silymarin Regulated Aluminum-Induced Imbalance of Neurotransmitters and Metal Elements in Brain of Rats - Jiasi Yu; Yun Ding; Dan Wu; Ping Liu (Biological Trace Element Research, 2024)

Generalist and topologically central avian frugivores promote plant invasion unequally across land‐bridge islands - Chen Zhu; Bo Dalsgaard; Wande Li; Fernando Gonçalves; Maximilian G. R. Vollstädt; Peng Ren; Xue Zhang; Junjie Shao; Ping Ding; Xingfeng Si (Ecology, 2024)
Seed dispersal by frugivorous birds facilitates plant invasions, but it is poorly known how invasive plants integrate into native communities in fragmented landscapes. We surveyed plant–frugivore interactions, including an invasive plant ( Phytolacca americana ), on 22 artificial land‐bridge islands (fragmented forests) in the Thousand Island Lake, China. Focusing on frugivory interactions that may lead to seed dispersal, we built ecological networks of studied islands both at the local island (community) and at landscape (metacommunity) levels. On islands with P. americana , we found that P. americana impacted local avian frugivory networks more on islands with species‐poor plant communities and on isolated islands. Moreover, as P. americana interacted mainly with local core birds (generalists), this indicates reduced seed dispersal of native plants on invaded islands. At the landscape level, P. americana had established strong interactions with generalist birds that largely maintain seed‐dispersal functions across islands, as revealed by their topologically central roles both in the regional plant–bird trophic network and in the spatial metanetwork. This indicates that generalist frugivorous birds may have facilitated the dispersal of P. americana across islands, making P. americana well integrated into the plant–frugivore mutualistic metacommunity. Taken together, our study demonstrates that the impact of plant invasion is context‐dependent and that generalist native frugivores with high dispersal potential may accelerate plant invasion in fragmented landscapes. These findings highlight the importance of taking the functional roles of animal mutualists and habitat fragmentation into account when managing plant invasions and their impact on native communities.

A new strategy for enhanced electrochemically activation of persulfate on B and Co co-modified carbon felt in flow-through system for efficient organic pollutants degradation - Jiahao Liu; Liping Xing; Jiaxin Lan; Lean Zhou; Ziyi Ding; Jing Xia; Ping Wang; Jingju Cai; Jian Zhu (Chemosphere, 2024)

Rare and abundant bacterial communities in poplar rhizosphere soils respond differently to genetic effects - Kun Yan; De Shan Lu; Chang Jun Ding; Yan Wang; Yong Ren Tian; Xiao Hua Su; Yu Feng Dong; Yan Ping Wang (Science of The Total Environment, 2024)

Environmentally persistent free radicals on photoaged nanopolystyrene induce neurotoxicity by affecting dopamine, glutamate, serotonin and GABA in Caenorhabditis elegans - Hui Li; Yulun Gu; Yongqi Jiang; Ping Ding; Xiaoxia Chen; Chao Chen; Ruolin Pan; Chongli Shi; Susu Wang; Haibo Chen (Science of The Total Environment, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Adipose Tissue Exosome circ_sxc Mediates the Modulatory of Adiposomes on Brain Aging by Inhibiting Brain dme-miR-87-3p - Qiufang Li; Lingxiao Wang; Chao Tang; Xiaoya Wang; Zhengwen Yu; Xu Ping; Meng Ding; Lan Zheng (Molecular Neurobiology, 2024)

Topological and functional vulnerability analysis and mitigation for single-source heating networks based on tree models - Ding Mao; Peng Wang; Yi-Ping Fang; Long Ni (Sustainable Cities and Society, 2023)

Characteristics of atmospheric black carbon and its wet scavenging in Nanning, South China - Shuo Ding; Dantong Liu; Delong Zhao; Ping Tian; Mengyu Huang; Deping Ding (Science of The Total Environment, 2023)

First evidence of microplastic ingestion by crescent perch (Terapon jarbua) in Malaysia - Kok Ping Lim; Jinfeng Ding; Kar Hoe Loh; Chengjun Sun; Sumiani Yusoff; Shyama Sundari Devi Chanthran; Phaik Eem Lim (Regional Studies in Marine Science, 2023)

Quantifying synergistic effects of artificial and environmental variables on potato nutrient use efficiency in China - Yingxia Liu; Yinsheng Sheng; Xinpeng Xu; Jinchuan Ma; Wencheng Ding; Ping He; Junwei Ma (Journal of Cleaner Production, 2023)

In situ synthesis of bi-functional NH2-Ti2C3Tx@COF Schottky heterojunction through interfacial electron effects for enhancing U(VI) photoreduction - You-Gan Wang; Wei Jiang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Long non-coding RNA HOX transcript antisense intergenic RNA depletion protects against alcoholic hepatitis through the microRNA-148a-3p/sphingosine 1-phosphate receptor 1 axis - Dan Chen; Ping Lu; Tianfeng Sun; Aliang Ding (Cell and Tissue Research, 2023)

Projecting spatiotemporal dynamics of severe fever with thrombocytopenia syndrome in the mainland of China - Fang‐Yu Ding; Hong‐Han Ge; Tian Ma; Qian Wang; Meng‐Meng Hao; Hao Li; Xiao‐Ai Zhang; Richard James Maude; Li‐Ping Wang; Dong Jiang; Li‐Qun Fang; Wei Liu (Global Change Biology, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with increasing incidence and geographic extent. The extent to which global climate change affects the incidence of SFTS disease remains obscure. We use an integrated multi‐model, multi‐scenario framework to assess the impact of global climate change on SFTS disease in China. The spatial distribution of habitat suitability for the tick Haemaphysalis longicornis was predicted by applying a boosted regression tree model under four alternative climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) for the periods 2030–2039, 2050–2059, and 2080–2089. We incorporate the SFTS cases in the mainland of China from 2010 to 2019 with environmental variables and the projected distribution of H. longicornis into a generalized additive model to explore the current and future spatiotemporal dynamics of SFTS. Our results demonstrate an expanded geographic distribution of H. longicornis toward Northern and Northwestern China, showing a more pronounced change under the RCP8.5 scenario. In contrast, the environmental suitability of H. longicornis is predicted to be reduced in Central and Eastern China. The SFTS incidence in three time periods (2030–2039, 2050–2059, and 2080–2089) is predicted to be increased as compared to the 2010s in the context of various RCPs. A heterogeneous trend across provinces, however, was observed, when an increased incidence in Liaoning and Shandong provinces, while decreased incidence in Henan province is predicted. Notably, we predict possible outbreaks in Xinjiang and Yunnan in the future, where only sporadic cases have been reported previously. These findings highlight the need for tick control and population awareness of SFTS in endemic regions, and enhanced monitoring in potential risk areas.

Investigation of the correlation between carbohydrate metabolization and pediocin sensitivity - Shanna Liu; Boqun Ding; Na Wang; Pingping Zhang; Ping Xiao (Biologia, 2023)

Relationship of individual and mixed urinary metals exposure with liver function in the China National Human Biomonitoring (CNHBM) of Zhejiang Province - Ping Cheng; Yi Tao; Jinfeng Hu; Hongxin Wang; Ruifang Zhao; Shenghua Mei; Yin Yang; Fugen Ye; Zhijian Chen; Hao Ding; Mingluan Xing; Peiwei Xu; et al. (Chemosphere, 2023)

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

Advantages of residual phenol in coal chemical wastewater as a co-metabolic substrate for naphthalene degradation by microbial electrolysis cell - Peng Ding; Ping Wu; Qihao Cao; Hongbo Liu; Chongjun Chen; Min-Hua Cui; He Liu (Science of The Total Environment, 2023)

Balancing potato yield, soil nutrient supply, and nitrous oxide emissions: An analysis of nitrogen application trade-offs - Linyirui Ning; Xinpeng Xu; Shaojun Qiu; Qiuliang Lei; Yitao Zhang; Jiafa Luo; Wencheng Ding; Shicheng Zhao; Ping He; Wei Zhou (Science of The Total Environment, 2023)

Medium-sized anammox granules achieve the optimal synergism between AnAOB and HDB via nitrite cycle - Da Kang; Xinyu Wan; Meng Zhang; Shuang Ding; Ping Zheng; Yongzhen Peng (Journal of Cleaner Production, 2023)

Amino acids as in-situ electron donors drive medium chain fatty acids production from sludge acidogenic fermentation liquid by electro-fermentation enhancement - Ping Wu; Peng Ding; Qi-hao Cao; Chao Zhang; Bo Fu; Hong-bo Liu; Chong-jun Chen; He Liu (Chemical Engineering Journal, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Ketamine counteracts sevoflurane-induced depressive-like behavior and synaptic plasticity impairments through the adenosine A2A receptor/ERK pathway in rats - Weiwei Yu; Ziyi Wu; Xingyue Li; Mengmeng Ding; Ying Xu; Ping Zhao (Molecular Neurobiology, 2023)

A novel “Turn-on” fluorometric assays triggered reaction for β-glucosidase activity based on quercetin derived silicon nanoparticles and its potential use for cell imaging - Yves Iradukunda; Jing-Yan Kang; Xiao-bo Zhao; Stanislas Nsanzamahoro; Xiao-Kang Fu; Jia Liu; Yu-Zhu Ding; Wei Ha; Yan-Ping Shi (Analytica Chimica Acta, 2023)

A new sesquiterpenoid from the aconitum -derived fungus Aspergillus fumigatus M1 - Hao Ding; Jia-Peng Wang; Si-Ping Deng; Jun-Li Gan; Bing-Xian Li; Ling-Ling Yao; Sheng-Qi Zhang; Le Cai; Zhong-Tao Ding (Natural Product Research, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Construction of zwitterionic 3D hydrogen-bonded networks: Exploring the upper-limit of thermal stability in ternary CHN-based energetic materials - Zhe Wang; Qi Lai; Ning Ding; Ping Yin; Siping Pang; Jean'ne M. Shreeve (Chemical Engineering Journal, 2023)

Widespread arboreal foraging behavior in ground-dwelling birds and the urgency of life-history studies - Wande Li; Chen Zhu; Ingo Grass; Peng Han; Yao Shen; Ping Ding; Xingfeng Si (Biological Conservation, 2023)

Formation and evolution mechanisms of a destructive-wind-producing thunderstorm in Shanghai - Yanan Liu; Fan Ping; Chenchen Ding; Xiaochen Zhang (Atmospheric Research, 2023)

Effects of dietary berberine on growth performance, lipid metabolism, antioxidant capacity and lipometabolism-related genes expression of AMPK signaling pathway in juvenile black carp (Mylopharyngodon piceus) fed high-fat diets - Jian-Hua Ming; Ting Wang; Ting-Hui Wang; Jin-Yun Ye; Yi-Xiang Zhang; Xia Yang; Xian-Ping Shao; Zhong-Ying Ding (Fish Physiology and Biochemistry, 2023)

Construction of covalent organic framework nanozymes with photo-enhanced hydrolase activities for colorimetric sensing of organophosphorus nerve agents - Sai-Jin Xiao; Ming-Yue Yuan; Ya-Di Shi; Meng-Ping Wang; Hui-Han Li; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Association of urinary bisphenols with thyroid function in the general population: a cross-sectional study of an industrial park in China - Yang Hu; Shiming Lai; Ying Li; Xiaodong Wu; Mingluan Xing; Xueqing Li; Dandan Xu; Yuan Chen; Jie Xiang; Ping Cheng; Xiaofeng Wang; Zhijian Chen; et al. (Environmental Science and Pollution Research, 2023)

Microbial colonization of microplastics in wastewater accelerates the aging process associated with oxidative stress and the insulin/IGF1 signaling pathway - Haibo Chen; Mengfan Chen; Yulun Gu; Yongqi Jiang; Ping Ding; Chen Wang; Ruolin Pan; Chongli Shi; Hui Li (Environmental Pollution, 2023)

Does urban scale borrowing aggravate carbon and air pollution emissions? - Zhongyao Cai; Xuhui Ding; Huaxing Lin; Ziqian Zhou; Xinyu Yang; Ping Jiang (Environmental Impact Assessment Review, 2023)

Ultrafast self-assembled supramolecular nanoparticles for enhanced chemodynamic therapy and ferroptosis through lactic acid metabolism regulation - Qi Meng; Jia Tan; Weifang Tong; Changxiao Chen; Zhendong Liu; Sainan Liu; Meifang Wang; Ziyong Cheng; Binbin Ding; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2023)

Influence of salinity on hydrogen isotope fractionation of n-alkanes in mangrove leaves and surface sediments: A comparison across various geomorphological settings - Yao-Ping Wang; Tao Luo; Jingyi Chen; Zhao-Wen Zhan; Zhiguang Song; Lantian Xing; Ding He (Chemical Geology, 2023)

Resveratrol triggers the ER stress-mediated intrinsic apoptosis of neuroblastoma cells coupled with suppression of Rho-dependent migration and consequently prolongs mouse survival - Ding-Ping Sun; Jui-Tai Chen; Shun-Tai Yang; Tso-Hsiao Chen; Shing-Hwa Liu; Ruei-Ming Chen (Chemico-Biological Interactions, 2023)

PM2.5/PM10-bound PAHs in Hotan city: Concentrations, sources, and contribution to ·OH - Xiaohui Zhang; Dilinuer Talifu; Xiang Ding; Xinming Wang; Kejun Li; Bowen Liu; Qilong Zhao; Ping Luo; Xiaoxia Xie (Atmospheric Environment, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Recent advances in investigating odor-taste interactions: Psychophysics, neuroscience, and microfluidic techniques - Yan Ping Chen; Ziyu Ding; Yashu Yu; Penglin He; Ya Zhou; Yuan Liu; Xi Feng (Trends in Food Science & Technology, 2023)

Quantitative evaluation for the sources and aging processes of organic aerosols in urban Guangzhou: Insights from a comprehensive method of dual‑carbon isotopes and macro tracers - Fan Jiang; Junwen Liu; Zhineng Cheng; Ping Ding; Sanyuan Zhu; Xin Yuan; Wei Chen; Zhisheng Zhang; Zheng Zong; Chongguo Tian; Weiwei Hu; Junyu Zheng; et al. (Science of The Total Environment, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

Removal of chemical oxygen demand and ammonia nitrogen from high salinity tungsten smelting wastewater by one-step electrochemical oxidation: From bench-scale test, pilot-scale test, to industrial test - Xiangsong Meng; Ping Zeng; Shangyong Lin; Huanjun Bao; Meirong Wu; Lei Yang; Gaogui Jing; Haisheng Han; Chenyang Zhang; Xiaoyun Jiang; Songlin Wang; Wei Ding; et al. (Journal of Environmental Management, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

A Secure Localization Scheme for UASNs Based on Anchor Node Self-Adaptive Adjustment - Ping Ding; Ziyu Zhou; Jinglan Ma; Guozhen Xing; Zhigang Jin; Ye Chen (Journal of Marine Science and Engineering, 2023)
The UASNs are widely used in underwater communications and monitoring, and many applications require accurate information regarding the position of nodes. However, intentional attacks against devices or information transmission may exist in the network, and the localization process is periodic, so it is necessary to quickly address attacks and optimize the network structure. This paper proposed an anchor node self-adaptive adjustment localization scheme (ASAL), in which the anchor node can adjust the state and depth of its participation. Two filters were used to adjust the states of referable nodes. The first filter was based on the distance difference of reverse information transmission after direct localization based on anchor nodes. The second was based on the error of the anchor node’s reverse localization after network localization was completed. In addition, a depth-adjustment mechanism of anchor nodes was proposed to optimize the network structure, the virtual force vector was introduced to describe the cost of depth adjustment, and the whale optimization algorithm was used to converge to the depth with the minimum total cost. The simulation results showed that the scheme can ensure localization accuracy and coverage in attack scenarios and reduce localization energy consumption.

Benfotiamine attenuates the high-carbohydrate diet-induced mitochondrial redox imbalance in fish Megalobrama amblycephala by activating SIRT3 - Ling Zhang; Ya-Ping Ge; Yang-Yang Huang; Wei-Liang Chen; Wen-Bin Liu; Ding-Dong Zhang; Xiang-Fei Li (Aquaculture, 2023)

Photoaged microplastics induce neurotoxicity via oxidative stress and abnormal neurotransmission in zebrafish larvae (Danio rerio) - Ping Ding; Chongdan Xiang; Xintong Li; Haibo Chen; Xiaoxia Shi; Xin Li; Chushan Huang; Yunjiang Yu; Jianying Qi; Adela Jing Li; Lijuan Zhang; Guocheng Hu (Science of The Total Environment, 2023)

Association of urinary exposure to multiple metal(loid)s with kidney function from a national cross-sectional study - Yunjiang Yu; Wenjie Meng; Hongxuan Kuang; Xichao Chen; Xiaohui Zhu; Lebing Wang; Haiping Tan; Yujie Xu; Ping Ding; Mingdeng Xiang; Guocheng Hu; Yang Zhou; et al. (Science of The Total Environment, 2023)

Thermal preconditioning can reduce the incidence of intraoperatively acquired pressure injuries - Ping Hou; Huiping Xue; Shuwen Chang; Ping Xie; Yajie Chen; Yanwei Wang; Daiji Miura; Jianglin Fan; Jingyan Liang; Akio Kitayama; Fang Fang; Haijuan Yuan; et al. (Journal of Thermal Biology, 2023)

Antifungal effects of trans-anethole, the main constituent of Illicium verum fruit volatiles, on Aspergillus flavus in stored wheat - Jun-Dong Lei; Shuai-Bing Zhang; Wen-Zheng Ding; Yang-Yong Lv; Huan-Chen Zhai; Shan Wei; Ping-An Ma; Yuan-Sen Hu (Food Control, 2023)

Heavy metals in fish, rice, and human hair and health risk assessment in Wuhan city, central China - Muhammad Ubaid Ali; Chuan Wang; Yuan Li; Ruolan Li; Shaochen Yang; Li Ding; Lin Feng; Bo Wang; Ping Li; Ming Hung Wong (Environmental Pollution, 2023)

Calibration analysis of calculation formulas for shear capacities of corroded RC beams - Chao Jiang; Hao Ding; Xiang-Lin Gu; Wei-Ping Zhang (Engineering Structures, 2023)

Rationally designing imidazole-based coordination polymers with high adsorption capacity for removing iodine - Xin Gao; Qing-Hua Hu; Yu-Zhen Shi; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Acid-sensing ion channel 1a exacerbates renal ischemia–reperfusion injury through the NF-κB/NLRP3 inflammasome pathway - Yan Yang; Shi Jin; Jian Zhang; Weize Chen; Yufei Lu; Jun Chen; Zhixin Yan; Bo Shen; Yichun Ning; Yiqin Shi; Jing Chen; Jialin Wang; et al. (Journal of Molecular Medicine, 2023)
Ischemia-reperfusion injury (IRI) is the main cause of acute kidney injury (AKI), and there is no effective therapy. Microenvironmental acidification is generally observed in ischemic tissues. Acid-sensing ion channel 1a (ASIC1a) can be activated by a decrease in extracellular pH which mediates neuronal IRI. Our previous study demonstrated that, ASIC1a inhibition alleviates renal IRI. However, the underlying mechanisms have not been fully elucidated. In this study, we determined that renal tubule-specific deletion of ASIC1a in mice (ASIC1a fl/fl /CDH16 cre ) attenuated renal IRI, and reduced the expression of NLRP3, ASC, cleaved-caspase-1, GSDMD-N, and IL-1β. Consistent with these in vivo results, inhibition of ASIC1a by the specific inhibitor PcTx-1 protected HK-2 cells from hypoxia/reoxygenation (H/R) injury, and suppressed H/R-induced NLRP3 inflammasome activation. Mechanistically, the activation of ASIC1a by either IRI or H/R induced the phosphorylation of NF-κB p65, which translocates to the nucleus and promotes the transcription of NLRP3 and pro-IL-1β. Blocking NF-κB by treatment with BAY 11-7082 validated the roles of H/R and acidosis in NLRP3 inflammasome activation. This further confirmed that ASIC1a promotes NLRP3 inflammasome activation, which requires the NF-κB pathway. In conclusion, our study suggests that ASIC1a contributes to renal IRI by affecting the NF-κB/NLRP3 inflammasome pathway. Therefore, ASIC1a may be a potential therapeutic target for AKI. Key messages Knockout of ASIC1a attenuated renal ischemia-reperfusion injury. ASIC1a promoted the NF-κB pathway and NLRP3 inflammasome activation. Inhibition of the NF-κB mitigated the NLRP3 inflammasome activation induced by ASIC1a.

Interactions between micaceous minerals weathering and cesium adsorption - Wei Wang; Leiping Shi; Hanyu Wu; Zhe Ding; Jianjun Liang; Ping Li; Qiaohui Fan (Water Research, 2023)

SOV sensitizes gastric cancer cells to radiation by suppressing radiation-induced autophagy in vitro and in vivo - Wen Wang; Xiao-gan Jiang; Ya-ping Bai; Heng Li; Ling-xi Gao; Teng Zhang; Fang-yi Dong; Wen-ping Ding; Yan Zhang (Tissue and Cell, 2023)

Simultaneous removal of antibiotics and antibiotic resistance genes in wastewater by a novel nonthermal plasma/peracetic acid combination system: Synergistic performance and mechanism - Ai Zhang; Xinyuan Jiang; Yongqiang Ding; Nan Jiang; Qian Ping; Lin Wang; Yanan Liu (Journal of Hazardous Materials, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Fabrication of Cu0-composited CuFe2O4 magnetic nanoparticles on diatomite support for efficient degradation of tetracycline hydrochloride by a Fenton-like system - Shuai Deng; Zhi Guo; Yi-Han Chen; Kang-Ping Cui; Zhao-Gang Ding; Bei Wang; Rohan Weerasooriya; Xing Chen (Journal of Environmental Chemical Engineering, 2023)

Failure mode-based calculation method for bearing capacities of corroded RC columns under eccentric compression - Chao Jiang; Hao Ding; Xiang-Lin Gu; Wei-Ping Zhang (Engineering Structures, 2023)

A new coumarin derivative from the roots of Peucedanum praeruptorum Dunn - Fang-You Chen; Lin-Feng Tu; Ding-Ping Liu; Yong-Ming Luo (Biochemical Systematics and Ecology, 2023)

A global analysis of avian island diversity–area relationships in the Anthropocene - Thomas J. Matthews; Joseph P. Wayman; Robert J. Whittaker; Pedro Cardoso; Julian P. Hume; Ferran Sayol; Konstantinos Proios; Thomas E. Martin; Benjamin Baiser; Paulo A. V. Borges; Yasuhiro Kubota; Luiz dos Anjos; et al. (Ecology Letters, 2023)
Research on island species–area relationships (ISAR) has expanded to incorporate functional (IFDAR) and phylogenetic (IPDAR) diversity. However, relative to the ISAR, we know little about IFDARs and IPDARs, and lack synthetic global analyses of variation in form of these three categories of island diversity–area relationship (IDAR). Here, we undertake the first comparative evaluation of IDARs at the global scale using 51 avian archipelagic data sets representing true and habitat islands. Using null models, we explore how richness‐corrected functional and phylogenetic diversity scale with island area. We also provide the largest global assessment of the impacts of species introductions and extinctions on the IDAR. Results show that increasing richness with area is the primary driver of the (non‐richness corrected) IPDAR and IFDAR for many data sets. However, for several archipelagos, richness‐corrected functional and phylogenetic diversity changes linearly with island area, suggesting that the dominant community assembly processes shift along the island area gradient. We also find that archipelagos with the steepest ISARs exhibit the biggest differences in slope between IDARs, indicating increased functional and phylogenetic redundancy on larger islands in these archipelagos. In several cases introduced species seem to have ‘re‐calibrated’ the IDARs such that they resemble the historic period prior to recent extinctions.

Late Carboniferous extension-related magmatism in the southwestern Alxa block of NW China: geochronology, geochemistry, and tectonic implications - Zeng-Zhen Wang; Xuan-Hua Chen; Wei-Cui Ding; Bing Li; Yi-Ping Zhang; Zhao-Gang Shao; Sheng-Lin Xu (International Geology Review, 2023)

Bisphenol A substitutes and childhood obesity at 7 years: a cross-sectional study in Shandong, China - Minyan Chen; Cheng Lv; Shanyu Zhang; Lap Ah Tse; Xinyu Hong; Xi Liu; Yu Ding; Ping Xiao; Ying Tian; Yu Gao (Environmental Science and Pollution Research, 2023)

UV-aged microplastics induces neurotoxicity by affecting the neurotransmission in larval zebrafish - Chongdan Xiang; Haibo Chen; Xiaolin Liu; Yao Dang; Xin Li; Yunjiang Yu; Bei Li; Xintong Li; Yanan Sun; Ping Ding; Guocheng Hu (Chemosphere, 2023)

Ciprofloxacin degradation performances and mechanisms by the heterogeneous electro-Fenton with flocculated fermentation biochar - Yanchao Jin; Peiwen Huang; Xiongjian Chen; Li-Ping Li; Chun-Yan Lin; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Environmental Pollution, 2023)

Synergistic Apoptosis-Ferroptosis: Oxaliplatin loaded amorphous iron oxide nanoparticles for High-efficiency therapy of orthotopic pancreatic cancer and CA19-9 levels decrease - Yilong Li; Xinlong Wang; Binbin Ding; Cong He; Can Zhang; Jiating Li; Haonian Wang; Zhibo Li; Gang Wang; Yongwei Wang; Hua Chen; Ping'an Ma; et al. (Chemical Engineering Journal, 2023)

Multi-scale structure characterization of ozone oxidized waxy rice starch - Jing Li; Meng Du; Zia-ud Din; Ping Xu; Lei Chen; Xi Chen; Yuehui Wang; Yang Cao; Kun Zhuang; Jie Cai; Qingyun Lyu; Xianhui Chang; et al. (Carbohydrate Polymers, 2023)

An Insight into the Mechanical and Fracture Characterization of Minerals and Mineral Interfaces in Granite Using Nanoindentation and Micro X-Ray Computed Tomography - Xiu-yang Liu; Ding-ping Xu; Shao-jun Li; Shi-li Qiu; Quan Jiang (Rock Mechanics and Rock Engineering, 2023)

Effects of polyethylene and biodegradable microplastics on photosynthesis, antioxidant defense systems, and arsenic accumulation in maize (Zea mays L.) seedlings grown in arsenic-contaminated soils - Huarong Sun; Yilan Shi; Ping Zhao; Guangqiang Long; Chaohang Li; Jiajing Wang; Dan Qiu; Chunmiao Lu; Yue Ding; Lin Liu; Shuran He (Science of The Total Environment, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Artificial intelligence-aided preparation of perovskite SrFexZr1-xO3-δ catalysts for ozonation degradation of organic pollutant concentrated water after membrane treatment - Xu Wang; Yanan Zhang; Cheng Zhang; Huangzhao Wei; Haibo Jin; Zhao Mu; Xiaofei Chen; Xinru Chen; Ping Wang; Xiaoyan Guo; Fuchen Ding; Xiaowei Liu; et al. (Chemosphere, 2023)

The environmental significance and low-oxygen indicator potential of benthic foraminiferal assemblages in surface sediments off the Changjiang River (Yangtze River) Estuary, China - Jieqiong Yuan; Xuan Ding; Ke Cao; Xin Pan; Ping Yin (Marine Geology, 2023)

Taurine and deferiprone against Al-linked apoptosis in rat hippocampus - Yanan Zhang; Tingmin Guo; Yun Ding; Xin Wang; Ping Liu (Journal of Trace Elements in Medicine and Biology, 2023)

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Studies on a novel method for the determination of nitrosamines in food by HPLC-UV-FLD coupling with terbium-doped carbon dots - Zhiqin Ding; Mengdie Cai; Weimin Gan; Ping Yuan; Lijun Wei; Xianglei Cheng (Food Chemistry, 2023)

Screening and identification of tyrosinase inhibitors in edible plant materials by on-line UPLC-enzyme reactor coupled with UHPLC-FTMS - Xiao Fang; Lei Dai; Tian-Ming Ding; Yao Zhu; Jun-Feng Zan; Lin-Lin Chen; Xiao-Ping Ding; Jun-Feng Liu (Food Chemistry, 2023)

The effect of volatile compounds of Syzygium aromaticum flower buds against Aspergillus flavus growth on wheat grain at postharvest stage - Yu-Liang Qin; Shuai-Bing Zhang; Wen-Zheng Ding; Yang-Yong Lv; Huan-Chen Zhai; Shan Wei; Ping-An Ma; Yuan-Sen Hu (Food Control, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Erratum to: Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Source characterization of volatile organic compounds in urban Beijing and its links to secondary organic aerosol formation - Quan Liu; Jiujiang Sheng; Yangzhou Wu; Zhiqiang Ma; Junying Sun; Ping Tian; Delong Zhao; Xia Li; Kang Hu; Siyuan Li; Xiaojing Shen; Yangmei Zhang; et al. (Science of The Total Environment, 2023)

Bibliometric overview of research progress, challenges, and prospects of rural domestic sewage: Treatment techniques, resource recovery, and ecological risk - Le Zhong; Jie Ding; Tong Wu; Yi-lin Zhao; Ji Wei Pang; Ji-Ping Jiang; Jun-Qiu Jiang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Journal of Water Process Engineering, 2023)

Synthesis of cationic polymer decorated with halogen for highly efficient trapping 99TcO4-/ReO4- - You-Gan Wang; Qing-Hua Hu; Juan Huang; Wei Jiang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Performance and mechanism of sodium citrate pretreatment to promote waste activated sludge disintegration and short-chain fatty acid production during anaerobic fermentation - Wenxue Ding; Qian Fang; Wuyang Zhou; Qiqi Ping; Yanyu Xiao; Zhihui Wang (Journal of Environmental Chemical Engineering, 2023)

Experimental and kinetic study on JP-10/air autoignition and the effect of NO2 at high temperatures - Lei Shi; Ping Xu; Rui Wang; Weixin Tang; Tao Ding; Rongpei Jiang; Changhua Zhang (Fuel, 2023)

Combining of C, N and specific Hg stable isotopes to track bioaccumulation of monomethylmercury in coastal and freshwater seafood - Shaochen Yang; Ping Li; Jinling Liu; Muhammad Ubaid Ali; Li Ding; Bo Wang (Food Chemistry, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Can the advisory system Nutrient Expert® balance productivity, profitability and sustainability for rice production systems in China? - Zhuo Xu; Ping He; Xinyou Yin; Qiuhong Huang; Wencheng Ding; Xinpeng Xu; Paul C. Struik (Agricultural Systems, 2023)

Earth Summit Mission 2022: Scientific Expedition and Research on Mt. Qomolangma Helps Reveal the Synergy between Westerly Winds and Monsoon and the Resulting Climatic and Environmental Effects - Yaoming Ma; Weiqiang Ma; Huaguang Dai; Lei Zhang; Fanglin Sun; Jinqiang Zhang; Nan Yao; Jianan He; Zhixuan Bai; Yuejian Xuan; Yunshuai Zhang; Yuan Yuan; et al. (Advances in Atmospheric Sciences, 2023)

Photoreduction behavior of Cr(VI) on oxidized carbon nanoparticles: From photocatalytic efficiency to oxygenated groups - Zhe Ding; Wentao Zhang; Jianjun Liang; Shirong Qiang; Wei Wang; Ping Li; Qiaohui Fan (Chemosphere, 2023)

Protolith origin of eclogites from the North Qaidam UHP metamorphic Belt, NW China: Implications for the breakup of the Rodinia supercontinent - Xiao-Dong Wang; Lin Ding; Deng Zeng; Ya-Hui Yue; Ling-Ping Yang; Zhe-Jun Wang; Lu-An Xiao; Chao Wang (Precambrian Research, 2023)

Synergizing potato productivity and environmental performance with Nutrient Expert recommendation approach in northern China - Lingling Jiang; Shaojun Qiu; Wencheng Ding; Xinpeng Xu; Ping He (Journal of Cleaner Production, 2023)

Ultrastructural evidence of four types of lipofuscins in the melanomacrophagic centers in hepatocytes of zebrafish (Denio rerio) - Noor Samad Gandahi; Jameel Ahmed Gandahi; Sheng Yang; Chunhua Liang; Botao Ding; Ping Yang; Qiusheng Chen (Fish & Shellfish Immunology, 2023)

Characteristics of ice-nucleating particles in Beijing during spring: A comparison study of measurements between the suburban and a nearby mountain area - Yaqiong Hu; Ping Tian; Mengyu Huang; Kai Bi; Julia Schneider; Nsikanabasi Silas Umo; Nikolas Ullmerich; Kristina Höhler; Xiaoqin Jing; Huiwen Xue; Deping Ding; Yongchun Liu; et al. (Atmospheric Environment, 2023)

Impact of early winter North Atlantic Oscillation on the dramatic alternation of seesaw haze intensity between late winter months in the North China Plain - Jing Wang; Yanju Liu; Yang Yang; Ping Wu; Jianbo Yang; Ping Liang; Chengyu Song; Shiyue Zhang; Yihui Ding (Atmospheric Research, 2023)

Modulation of sea surface temperature over the North Atlantic and Indian‐Pacific warm pool on interdecadal change of summer precipitation over northwest China - Ping Wu; Yanju Liu; Yihui Ding; Xiucang Li; Jing Wang (International Journal of Climatology, 2022)
Under the background of global warming, the summer precipitation over northwest China (NW) has experienced a significant interdecadal shift since the early 1990s, followed by a great increase in precipitation. This increase was mainly due to the anomalous water vapour input from the eastern boundary, whose transport has gradually become the main moisture transport belt affecting summer precipitation over NW in the past 30 years. Further research indicates that the anomalous easterly water vapour transport mainly originates from the Arctic and North Pacific Oceans. The interdecadal increase in precipitation and changes in water vapour transport pathways are related to the interdecadal warming of the North Atlantic (NA) and Indian‐Pacific warm pool (IPWP) in the mid‐1980s. The IPWP warming potentially weakens the land–sea thermal gradient, dampens the meridional circulation in East Asia, and thereby significantly reduces the southerly water vapour transport of the Asian summer monsoon, and generates anomalous northeasterly water vapour transport from high latitudes over East Asia. Moreover, the warmer sea surface temperature (SST) over the IPWP and NA can induce an anomalous teleconnection wave train, with anomalous anticyclones over Lake Baikal and the Aleutian Islands, and an anomalous cyclone over Japan. This type of teleconnection wave train contributes to anomalous northerly winds over eastern China and easterly winds over NW. The above‐mentioned anomalous circulation favours moisture transport from both the Arctic and North Pacific toward the NW, resulting in an increase in summer precipitation associated with the anomalous regional ascending motion.

An alkali-resistant metal–organic framework as halogen bond donor for efficient and selective removing of ReO4−/TcO4− - Qing-Hua Hu; Yu-Zhen Shi; Xin Gao; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Science and Pollution Research, 2022)

A water-soluble polysaccharide from Eucommia folium: the structural characterization and anti-tumor activity in vivo - Zhi-Qian Yan; Su-Yun Ding; Pei Chen; Hui-Ping Liu; Meng-Li Chang; Shu-Yuan Shi (Glycoconjugate Journal, 2022)

The Microphysical Characteristics of Wintertime Cold Clouds in North China - Xuexu Wu; Minghuai Wang; Delong Zhao; Daniel Rosenfeld; Yannian Zhu; Yuanmou Du; Wei Zhou; Ping Tian; Jiujiang Sheng; Fei Wang; Deping Ding (Advances in Atmospheric Sciences, 2022)

Synergistic impacts of westerlies and monsoon on interdecadal variations of late spring precipitation over the southeastern extension of the Tibetan Plateau - Jing Wang; Yanju Liu; Chengyu Song; Yihui Ding; Qiaoping Li; Ping Wu; Ying Xu; Xiangde Xu (International Journal of Climatology, 2022)
Based on multiple long‐term observational and reanalysis datasets, this study investigated the characteristics and physical mechanisms of the interdecadal variations in late spring (i.e., May) precipitation (LSP) over the southeastern extension of the Tibetan Plateau (SETP) since 1900. It was revealed that by and large, LSP over the SETP experienced interdecadal decrease during the period preceding 1927, 1962–1988, and 2004 onwards, but saw an increase during the periods of 1928–1961 and 1989–2003. The atmospheric circulations responsible for interdecadal variations in LSP over the SETP were also analysed. These analyses identified significant synergistic impacts of decreased mid‐latitude upstream westerlies and increased low‐latitude monsoonal southerlies over the Central North Bay of Bengal (CNBOB) on interdecadal variations in precipitation, suggesting striking interactions between extratropical eastward cold air and tropical northward warm/humid air. Further observational and modelling evidence suggested that Atlantic Multidecadal Oscillation (AMO) was likely to be a salient oceanic driver for the interdecadal synergy between upstream westerlies and CNBOB monsoonal southerlies. The elevated sea surface temperature anomalies associated with the warm phase of the AMO could spark favourable local atmospheric anomalies, forcing an upper‐tropospheric, planetary‐scale teleconnection emanating from the east of the North Atlantic sector, which may serve as an effective bridge linking the remote AMO signal and the synergy between westerlies and monsoonal southerlies around the SETP on interdecadal timescales. Our findings provided new insights into the understanding of the synergistic roles of westerlies and monsoons in the modulation of interdecadal LSP over the SETP, prior to the peak Asian summer monsoon season.

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

Numerical and Experimental Study on the Bragg Reflection of Water Waves by Multiple Vertical Thin Plates - Wei-Wei Ding; Wan-Zhen Yue; Song-Wei Sheng; Jing-Ping Wu; Zao-Jian Zou (Journal of Marine Science and Engineering, 2022)
The Bragg reflection of water waves by multiple vertical thin plates is investigated numerically and experimentally. The problem of surface gravity wave interaction with multiple vertical thin plates is formulated mathematically under the assumption of linear water wave theory. Numerical results of the reflection and transmission coefficients are obtained based on the dual boundary element method and compared with the results in the literature. The characteristics of Bragg reflection are represented by the occurring condition, the primary reflection coefficient and the effective bandwidth. The effects of the number, the immerged depth and the spacing of the plates on the characteristics of Bragg reflection are further analyzed systematically. Model experiments are conducted and the experimental results are used to compare with the numerical results of Bragg reflection. This study can provide guidance on the design of multiple vertical thin plates as effective breakwaters by taking advantage of Bragg reflection.

Visual Monitoring of Disintegration of Solid Oral Dosage Forms in Simulated Gastric Fluids Using Low-Field NMR Imaging - Qianyu Ye; Meilai Ding; Ping Zhang; Peng Wu; Yong Wang; Cordelia Selomulya; Xiao Dong Chen (AAPS PharmSciTech, 2022)

Fine-mapping and association analysis of candidate genes for papilla number in sea cucumber, Apostichopus japonicus - Xinghai Zhu; Ping Ni; Marc Sturrock; Yangfan Wang; Jun Ding; Yaqing Chang; Jingjie Hu; Zhenmin Bao (Marine Life Science & Technology, 2022)
The papilla number is one of the most economically important traits of sea cucumber in the China marketing trade. However, the genetic basis for papilla number diversity in holothurians is still scarce. In the present study, we conducted genome-wide association studies (GWAS) for the trait papilla number of sea cucumbers utilizing a set of 400,186 high-quality SNPs derived from 200 sea cucumbers. Two significant trait-associated SNPs that passed Bonferroni correction ( P < 1.25E−7) were located in the intergenic region near PATS1 and the genic region of EIF4G , which were reported to play a pivotal role in cell growth and proliferation. The fine-mapping regions around the top two lead SNPs provided precise causative loci/genes related to papilla formation and cellular activity, including PPP2R3C , GBP1 , and BCAS3 . Potential SNPs with P < 1E−4 were acquired for the following GO and KEGG enrichment analysis. Moreover, the two lead SNPs were verified in another population of sea cucumber, and the expressive detection of three potential candidate genes PATS1 , PPP2R3C , and EIF4G that near or cover the two lead SNPs was conducted in papilla tissue of TG (Top papilla number group) and BG (Bottom papilla number group) by qRT-PCR. We found the significantly higher expression profile of PATS1 (3.34-fold), PPP2R3C (4.90-fold), and EIF4G (4.23-fold) in TG, implying their potential function in papilla polymorphism. The present results provide valuable information to decipher the phenotype differences of the papilla trait and will provide a scientific basis for selective breeding in sea cucumbers.

Discovery of potential anti-SARS-CoV-2 drugs based on large-scale screening in vitro and effect evaluation in vivo - Haoran Peng; Cuiling Ding; Liangliang Jiang; Wanda Tang; Yan Liu; Lanjuan Zhao; Zhigang Yi; Hao Ren; Chong Li; Yanhua He; Xu Zheng; Hailin Tang; et al. (Science China Life Sciences, 2022)

The Effects of Toxic Metals in Chinese Traditional Glutinous Wine From Industrial and Commercial Areas: Spatial and Potential Health Risk - Guofeng Ren; Liangji Ma; Ping Ding; Jing Jin; Xiandan Yang; Zhao Ju; Ruixue Huang (Exposure and Health, 2022)

Preliminary study of genome-wide association identifies novel susceptibility genes for serum mineral elements in the Chinese Han population - Duojian Guo; Yu Zhou; Xingwei Wei; Shanshan Zhang; Tianbo Jin; Yutian Zhang; Mei Lin; Xiaoli Zhou; Yufei Xie; Chanyi He; Qi Lin; Ping He; et al. (Biological Trace Element Research, 2022)

Three-Dimensional Urban Thermal Effect across a Large City Cluster during an Extreme Heat Wave: Observational Analysis - Yue Ma; Ping Liang; Sue Grimmond; Xuchao Yang; Jun Lyu; Yihui Ding (Journal of Meteorological Research, 2022)

SLOSS ‐based inferences in a fragmented landscape depend on fragment area and species–area slope - Jinliang Liu; Zachary G. MacDonald; Xingfeng Si; Lingbing Wu; Di Zeng; Guang Hu; Ping Ding; Mingjian Yu (Journal of Biogeography, 2022)
Aims Whether a Single Large Or Several Small (SLOSS) habitat patches contain more species is central to the debate about how habitat fragmentation threatens species diversity. However, the geographical and biogeographical variables that affect emergent SLOSS patterns remain poorly understood. Here, we quantified SLOSS‐based diversity patterns of woody plant, bird and spider assemblages in a subtropical archipelago of land bridge islands. Location Thousand Island Lake, Zhejiang Province, China. Taxon Woody plants, birds and spiders. Methods We analysed species accumulation curves and species–area relationships (SARs) to quantify SLOSS‐based patterns of all, common and rare species for each taxon across different groupings of islands. Differences in the number of species between a single large island and sets of several small islands were measured in these analyses using a Saturation index (SI) and SLOSS index. Generalized additive models were used to assess the relationships between SI and SLOSS index values and the maximum area of islands included in the analysis, the slope of SARs (i.e. z ‐score) and the degree of nestedness. Results SI values increased with the maximum area of islands for three taxa, while SLOSS index values only increased with the maximum island area for woody plants. SI values increased as z ‐scores of woody plants decreased, and showed a quadratic relationship for birds and spiders. SLOSS index values decreased as z ‐scores of three taxa increased. The degree of nestedness and SI values or SLOSS index values were weakly correlated with all, rare and common species in the three taxa. Main conclusions SLOSS‐based inferences of fragmentation effects are contingent on variation in the maximum area of patches included in analyses and the slope of SARs in fragmentated landscapes. Whether conservation efforts should prioritize a single large or several small patches depends on the geographical (e.g. maximum fragment area) and biogeographical (e.g. slope of SAR) attributes of a fragmentated landscape.

A landscape‐level analysis of bird taxonomic, functional and phylogenetic β‐diversity in habitat island systems - Chi Zeng; Wande Li; Ping Ding; Yu Peng; Lingbing Wu; Xingfeng Si (Journal of Biogeography, 2022)
Aim How β‐diversity patterns are shaped by landscape‐level processes remains unclear across habitat island systems. Here we assessed landscape‐level bird β‐diversity in habitat island systems and aimed to (1) evaluate the relative contribution of turnover (β SIM ) and nestedness‐resultant (β SNE ) components to multisite β‐diversity (β SOR ) from taxonomic, functional and phylogenetic dimensions; (2) examine the influence of climate factors and system characteristics in shaping landscape‐level patterns of β‐diversity measures; and (3) study how β‐diversity patterns of bird communities vary with the spatial extents of island systems. Location Global. Taxon Birds. Methods We compiled bird data in 22 habitat island systems from literature and classified these island systems into small and large spatial scales. We partitioned β SOR into β SIM and β SNE from three dimensions for each system and calculated standardized functional and phylogenetic β‐diversity measures. We assessed the effects of climate factors and system characteristics on observed and standardized β‐diversity measures by multiple linear models for both small and large systems. Results We found that the dominant role of β SIM to β SOR in habitat island systems was pervasive. However, the best explanatory variables were not consistent across systems, which depended on the β‐diversity components, diversity dimensions and spatial extent of habitat island systems. In general, climate factors acted as the main drivers of bird communities across small and large systems, whereas system characteristics played minor roles. Main conclusions Spatial turnover dominated overall bird β‐diversity in most habitat island systems. Our results imply the roles of niche‐based assembly processes through the interplay among differential functional traits and phylogenetic distances of species, climate factors and system characteristics as well as spatial extent in driving bird communities across multiple habitat island systems at a landscape level. This study offers a better understanding of the processes underlying macroecological patterns of isolated biological communities across habitat island systems.

MiR-1260b protects against LPS-induced degenerative changes in nucleus pulposus cells through targeting TCF7L2 - Shijie Chen; Guixia Shi; Jin Zeng; Ping Huang Li; Yi Peng; Zhiyu Ding; Hong Qing Cao; Ruping Zheng; Weiguo Wang (Human Cell, 2022)

Phylogenetic and functional clustering illustrate the roles of adaptive radiation and dispersal filtering in jointly shaping late‐Quaternary mammal assemblages on oceanic islands - Xingfeng Si; Marc W. Cadotte; T. Jonathan Davies; Alexandre Antonelli; Ping Ding; Jens‐Christian Svenning; Søren Faurby (Ecology Letters, 2022)
Islands frequently harbour unique assemblages of species, yet their ecological roles and differences are largely ignored in island biogeography studies. Here, we examine eco‐evolutionary processes structuring mammal assemblages on oceanic islands worldwide, including all extant and extinct late‐Quaternary mammal species. We find island mammal assemblages tend to be phylogenetically clustered (share more recent evolutionary histories), with clustering increasing with island area and isolation. We also observe that mammal assemblages often tend to be functionally clustered (share similar traits), but the strength of clustering is weak and generally independent from island area or isolation. These findings indicate the important roles of in situ speciation and dispersal filtering in shaping island mammal assemblages under pre‐anthropogenic conditions, notably through adaptive radiation of a few clades (e.g. bats, with generally high dispersal abilities). Our study demonstrates that considering the functional and phylogenetic axes of diversity can better reveal the eco‐evolutionary processes of island community assembly.

Simultaneous determination of praziquantel and its main metabolites in the tissues of black goats and their residue depletion - Tong-Yan Ding; Xiao-Gui Shu; Ren-Ping Xiong; Jing-Li Qiu; Lu Li; Li-Min He (Food Additives & Contaminants: Part A, 2022)

MOG antibody-associated disease presenting with tumefactive lesions and closed-ring enhancement - Yin-Xi Zhang; Yang Zheng; Meng-Ting Cai; Qiang Du; Mei-Ping Ding (Acta Neurologica Belgica, 2022)

Is Zooplankton Body Size an Indicator of Water Quality in (Sub)tropical Reservoirs in China? - Li Wang; Jun Chen; Haojie Su; Xufa Ma; Zhixu Wu; Hong Shen; Jia Yu; Jiarui Liu; Yao Wu; Guangyi Ding; Ping Xie (Ecosystems, 2022)

A bi-scale assessing framework for aesthetic ecosystem services of villages in a world heritage site - Yin-ping Ding; Zhi-lin Liu; Yuan-mei Jiao; Qiu-e Xu; Kan-feng Zhang; Cheng-jing Liu; Fan Chen (Journal of Mountain Science, 2022)

Oxidative degradation/mineralization of dimethyl phthalate (DMP) from plastic industrial wastewater using ferrate(VI)/TiO2 under ultraviolet irradiation - Ping Wang; Yi Ding; Liting Zhu; Yunhao Zhang; Sijie Zhou; Linbei Xie; Ao Li (Environmental Science and Pollution Research, 2022)

Effects of shading and micro‐spray of canopy on photosynthetic characteristics, quality and yield of drip‐irrigated grapes * - Ming Zheng; Yungang Bai; Jianghui Zhang; Hongbo Liu; Junshe Cai; Shijian Bai; Bangxin Ding; Ping Ding (Irrigation and Drainage, 2022)
Grapes are prone to midday depression of photosynthesis (MDP) under the action of high temperature and strong light, which can reduce the accumulation of organic matter, resulting in a decline in yield and quality. In this study, the grapes in Shanshan County, Xinjiang, China, were taken as an example to implement shading and micro‐spray measures. Shading degrees of 0, 15 and 30% were combined with micro‐spray flow rates of 20, 30 and 40 L h −1 . Nine treatments and one control treatment (the control treatment is without shading and mist spraying) were designed through a combination of the shading and micro‐spray conditions. The photosynthetic prediction model of the multivariate nonlinear model was constructed and had high simulation accuracy. The decline of air temperature at the top of the canopy increased as the degree of shading and the amount of micro‐spray increased; MDP could be eliminated under the combined conditions of shading and micro‐spray. The mean daily net CO 2 assimilation rate (An) increased by more than 0.53 μmol m −2 s −1 . The combination of shading and micro‐spray conditions significantly increased fruit size and promoted greenness. The WP1 (15% and 40 L h −1 ) treatment had the highest mean daily An and the largest fruit volume. The vitamin C (VC) content of WP1 treatment was the highest, 4.13 mg kg −1 , which was 1.2 times that of the control (CK) treatment. The yield of the WP1 treatment was the highest, which was 19.7% higher than that of the CK treatment. Thus, the WP1 treatment was the optimal treatment for promoting the An of grape leaves and improving the fruit quality of grapes. This research could provide a reference for improving the photosynthesis, fruit quality and yield of grapes and alleviating the photosynthetic MDP of crops.

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Integration of metabolomics and transcriptomics revealed the biosynthetic mechanism of anti-parasitic compounds in Salinivibrio proteolyticus strain YCSC6 - Guangxun Du; Lingyun Qu; Ping Gao; Wenhao Huang; Chenghua Li; Dewen Ding (Journal of Oceanology and Limnology, 2022)

Genetic improvement of grain quality traits in indica inbred rice cultivars developed in South China during 1956–2020 - Xin-Qiao Zhou; Da-Gang Chen; Jie Guo; Ping-Li Chen; Li-Jun Li; Ke Chen; You-Ding Chen; Chuan-Guang Liu; Ze-Min Zhang (Euphytica, 2022)

Antioxidant terpenoids from the red alga Laurencia tristicha - Juan Zhang; Lun-Yong Shi; Lan-Ping Ding; Hong Liang; Peng-Fei Tu; Qing-Ying Zhang (Natural Product Research, 2021)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

Mercury uptake by Paspalum distichum L. in relation to the mercury distribution pattern in rhizosphere soil - Su Xu; Ping Gong; Wen Ding; Shengchun Wu; Xinwei Yu; Peng Liang (Environmental Science and Pollution Research, 2021)

Heterojunction photocatalysts for degradation of the tetracycline antibiotic: a review - Xinghou He; Tianhan Kai; Ping Ding (Environmental Chemistry Letters, 2021)

Influences of environmental factors on the modern 14C reservoir effects in Qinghai-Tibet Plateau lakes - Ding-ding Du; Zhi-wen Li; Hai-ping Hu; Yong-hui Bai; Wen Li; Muhammad Saleem Mughal; Hai-Yan Qian (Journal of Mountain Science, 2021)

The Extreme Mei-yu Season in 2020: Role of the Madden-Julian Oscillation and the Cooperative Influence of the Pacific and Indian Oceans - Ping Liang; Zeng-Zhen Hu; Yihui Ding; Qiwen Qian (Advances in Atmospheric Sciences, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Ecological carrying capacity of alpine grassland in the Qinghai–Tibet Plateau based on the structural dynamics method - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jiang Ding (Environment, Development and Sustainability, 2021)

Characterization of red sand dust pollution control performance via static and dynamic laboratorial experiments when applying polymer stabilizers - Xuhan Ding; Zhenmin Luo; Guang Xu; Ping Chang (Environmental Science and Pollution Research, 2021)

Variations in rare earth elements with environmental factors in lake surface sediments from 17 lakes in western China - Ding-ding Du; Liu-qin Chen; Yong-hui Bai; Hai-ping Hu (Journal of Mountain Science, 2021)

Understanding the failure mechanism of a large underground cavern in steeply dipping layered rock mass using an enhanced ubiquitous-joint model - Yang-Yi Zhou; Ding-Ping Xu; Ke Liu; Dong-Fang Chen (Bulletin of Engineering Geology and the Environment, 2021)

Vitexnegheteroin M, a new phenolic glycoside from Vitex negundo var. heterophylla - Ye Huang; Guo-Yu Ding; Ping Hu (Natural Product Research, 2021)

Nitrogen fertilization overweighs intercropping in promotion of dissolved organic carbon concentration and complexity in potato-cropped soil - Ding Wang; Ping Zhao; Rui Xiang; Shuran He; Yanli Zhou; Xinhua Yin; Guangqiang Long (Plant and Soil, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

Lithological and environmental controls on large tafoni along conglomerate cliffs in subtropic humid Danxiashan UNESCO Global Geopark - Xin Chen; Liu-qin Chen; Yan-hong Zhang; Ding-ding Du; Hai-ping Hu; Dong-xing Liu; Wen-zhuo Li (Journal of Mountain Science, 2021)

Improving generation of H2O2 and •OH at copper hexacyanocobaltate/graphene/ITO composite electrode for degradation of levofloxacin in photo-electro-Fenton process - Xiao-Yuan Lv; Guan-Ping Jin; Ding-Kun Yuan; Yan-Feng Ding; Peng-Xing Long (Environmental Science and Pollution Research, 2021)

Regenerable, anti-biofouling covalent organic frameworks for monitoring and extraction of uranium from seawater - Yi-Di Wu; Wei-Rong Cui; Cheng-Rong Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Chemistry Letters, 2021)

An Insight into the Excavation-Induced Stress Paths on Mechanical Response of Weak Interlayer Zone in Underground Cavern Under High Geostress - Shu-Qian Duan; Quan Jiang; Guo-Feng Liu; Jie-Cheng Xiong; Po Gao; Ding-Ping Xu; Ming-Yu Li (Rock Mechanics and Rock Engineering, 2021)

First report of cucumber mosaic virus infecting Morinda officinalis in China - Chong Feng; Ti-Jiang Shan; Li Yang; Miao-Miao Cai; De-Po Yang; Zhi-Min Zhao; Ping Ding (Journal of Plant Pathology, 2021)

Geographic information system–based health risk assessment of rural drinking water in Central China: a case study of You County, Hunan - Danqi Wang; Xu Chen; Jialiang Zhang; Yanqin Zhong; Ran Liu; Ping Ding (Environmental Monitoring and Assessment, 2021)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

Comparative performance assessment of landslide susceptibility models with presence-only, presence-absence, and pseudo-absence data - Dong-mei Zhao; Yuan-mei Jiao; Jin-liang Wang; Yin-ping Ding; Zhi-lin Liu; Cheng-jing Liu; Ying-mei Qiu; Juan Zhang; Qiu-e Xu; Chang-run Wu (Journal of Mountain Science, 2020)

Institutional reform and irrigation water pricing in China * - Wenjin Ni; Ping Dang; Kunlun Ding (Irrigation and Drainage, 2020)
The management of irrigation schemes in China mainly adopts a management mode of combining professional management by irrigation scheme administration (an irrigation scheme management agency) and self‐independent management by farmers (a water users’ association). This paper summarizes the basic situation of the management system of irrigation schemes and water pricing of irrigation in China, the challenges faced, the progress of reform and the results obtained. Analyses are also given on the reform of professional management organizations of irrigation schemes, the development and roles of water users’ associations, and government support and policy safeguarding measures for the reform. An irrigation water fee is an important source of funds for the operation and maintenance of irrigation schemes. At present, the overall irrigation water price is far lower than the operation and maintenance cost of irrigation schemes, and the collection rate of water fees is relatively low. The comprehensive reform of irrigation water pricing and its progress are presented in this paper. © 2020 John Wiley & Sons, Ltd.

Island area, not isolation, drives taxonomic, phylogenetic and functional diversity of ants on land‐bridge islands - Yuhao Zhao; Robert R. Dunn; Haonan Zhou; Xingfeng Si; Ping Ding (Journal of Biogeography, 2020)
Aim To explore the impact of island area and isolation on multiple dimensions of ant biodiversity (taxonomic, phylogenetic and functional diversity) and the underlying processes of community assembly on islands. Location Thousand Island Lake, Zhejiang, China, created by dam construction in 1959. Taxon Ants. Methods We sampled ants on 33 islands, built a species‐level phylogenetic tree and measured five morphological traits of all species collected to estimate taxonomic, phylogenetic and functional diversity. We used multiple linear regression models and null models to examine the relationships between diversity metrics and island variables (area and isolation). Results We recorded 97 ant species on the study islands. We verified positive diversity–area relationships for species richness, phylogenetic diversity and functional diversity. However, although functional and phylogenetic community structure were indistinguishable from random communities, phylogenetic structure tended to be clustered, whereas functional structure tended to be overdispersed. Additionally, we found the structure of ant communities shifted from phylogenetic and functional clustering on smaller islands to phylogenetic and functional overdispersion on larger islands. Main conclusions Our results support the hypothesis that environmental filtering is the dominant process structuring ant communities on smaller islands, and that competitive exclusion becomes more important on larger islands. Thus, island area acts as an important filter even though ant community structure on the study islands was indistinguishable from random communities. Moreover, our results show that environmental filtering influences phylogenetic community structure of ants, whereas competitive exclusion influences functional community structure of ants. These findings highlight the need to examine both phylogenetic and functional diversity in order to understand the mechanisms that govern the assembly of natural communities on islands.

Impacts of climate anomalies on the interannual and interdecadal variability of autumn and winter haze in North China: A review - Jing Wang; Yanju Liu; Yihui Ding; Ping Wu; Zhiwei Zhu; Ying Xu; Qiaoping Li; Yingxian Zhang; Jinhai He; Julian X. L. Wang; Li Qi (International Journal of Climatology, 2020)
From the perspectives of remote sensing and climatic factors like surface meteorological parameters, large‐scale atmospheric circulations, and external forcing factors (EFFs), the authors synthesize and review spatiotemporal variations of PM 2.5 over North China and how climate anomalies affect autumn and winter haze variability in North China according to recent studies. This review focuses on both interannual and interdecadal timescales. It is shown that circulations play an important role in influencing haze variability. Atmospheric circulations, which would be modulated by EFFs like sea surface temperature, sea ice, and snowpack, can affect the climate variability in haze over North China via modulation of surface‐layer parameters that are closely connected with the haze phenomenon. Therefore, EFFs are deemed significant factors impacting the climate variability of haze over North China, serving as paramount precursory signals for haze prediction. Furthermore, this paper suggests potential future research directions for haze variability studies in North China on the basis of summarizing and concluding the associated processes/mechanisms on how climatic factors affect haze variability, which could provide reference for treating and forecasting in situ hazy conditions.

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

Duration of SARS-CoV-2 viral shedding during COVID-19 infection - Guo-Qing Qian; Xue-Qin Chen; Ding-Feng Lv; Ada Hoi Yan Ma; Li-Ping Wang; Nai-Bin Yang; Xiao-Min Chen (Infectious Diseases, 2020)

Applying modified biochar with nZVI/nFe3O4 to immobilize Pb in contaminated soil - Peirou Li; Jiang Yu; Zhuoxi Huangfu; Jiahua Chang; Chengwei Zhong; Ping Ding (Environmental Science and Pollution Research, 2020)

Association between population migration and epidemic control of Coronavirus disease 2019 - Yu Ding; Sihui Luo; Xueying Zheng; Ping Ling; Tong Yue; Zhirong Liu; Jianping Weng (Science China Life Sciences, 2020)

Characteristics of dispersion curves for Love channel waves in transversely isotropic media - Guang-Zhong Ji; Ping-Song Zhang; Li-Quan Guo; Si-Tong Yang; Ren-Wei Ding (Applied Geophysics, 2020)

An Injectable Nanocomposite Hydrogel for Potential Application of Vascularization and Tissue Repair - Yilei Ding; An-sha Zhao; Tianmei Liu; Ya-nan Wang; Yuan Gao; Jing-an Li; Ping Yang (Annals of Biomedical Engineering, 2020)

Biodegradation of microcystin-RR and nutrient pollutants using Sphingopyxis sp. YF1 immobilized activated carbon fibers-sodium alginate - Guofeng Ren; Xinghou He; Pian Wu; Yayuan He; Yong Zhang; Shibiao Tang; Xinli Song; Yafei He; Yuandan Wei; Ping Ding; Fei Yang (Environmental Science and Pollution Research, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

Molecular characterization of the Krüppel-homolog 1 and its role in ovarian development in Sogatella furcifera (Hemiptera: Delphacidae) - Kui Hu; Ping Tian; Lu Yang; Yan Tang; Lin Qiu; Hualiang He; Wenbing Ding; Youzhi Li (Molecular Biology Reports, 2020)

A Meta-analysis of the Association Between SLC6A3 Gene Polymorphisms and Schizophrenia - Feng-ling Xu; Mei Ding; Xue Wu; Yong-ping Liu; Xi Xia; Jun Yao; Bao-jie Wang (Journal of Molecular Neuroscience, 2020)

Front Cover - Wei Wang; Jie Wang; Francis M. P. Choi; Ping Ding; Xiao‐xu Li; Guo‐dong Han; Meng‐wen Ding; Minquan Guo; Xiong‐wei Huang; Wei‐xiang Duan; Zhi‐yuan Cheng; Zhi‐yuan Chen; et al. (Global Ecology and Biogeography, 2020)

Global warming and artificial shorelines reshape seashore biogeography - Wei Wang; Jie Wang; Francis M. P. Choi; Ping Ding; Xiao‐xu Li; Guo‐dong Han; Meng‐wen Ding; Minquan Guo; Xiong‐wei Huang; Wei‐xiang Duan; Zhi‐yuan Cheng; Zhi‐yuan Chen; et al. (Global Ecology and Biogeography, 2020)
Aim Rapid anthropogenic warming coupled with changes in land use is altering the distributions of species, with consequences for ecosystem functioning and services. It is crucial to evaluate species range shifts based on understanding of the interaction of temperature with non‐climatic factors such as habitat availability and dispersal potential. Here, we aim to investigate roles of environmental temperature, habitat availability and population connectivity on the distributions of hard‐shore intertidal animals. We further examine potential roles of extensive artificial seawall construction in enabling poleward expansion of species in China, thus reshaping coastal biogeography. Location Chinese coast. Time period 2013–2017. Major taxa studied Intertidal invertebrates. Methods We took an integrative approach encompassing distributional ecology, thermal physiology, molecular genetics, heat budget modelling and larval dispersal to elucidate how interacting multiple drivers, including temperature, habitat availability and larval dispersal, determine distributions of hard‐shore invertebrates, focusing on what sets their range edges at a boundary between biogeographic provinces. Results Our results untangle the complex interactions of global climate change with the impacts of regional scale coastal development. Temperature, larval transport and habitat availability are the major proximate factors controlling the range limits of coastal marine species. The artificial shorelines provide suitable habitats for hard‐shore species on the Yangtze River Delta, and minimum temperature in winter is an important factor setting the new northern range limit of these hard‐shore species along the Chinese coast. Main conclusions In the face of global warming and global sprawl of marine hard infrastructure, species distributions, community structures and biogeographic patterns are experiencing dramatic changes. The combined influence of multiple human stressors including climate change and artificial shorelines can be evaluated by using a multidisciplinary framework, including ecological distribution, physiological sensitivity of species to these stressors, and the role of dispersal in maintaining population connectivity.

Complete Genome Sequence of Strain YCSC6, a Marine Bacterium Isolated from Saturated Saltpan with Activity Against Uronema marinum - Guang Xun Du; Ling Yun Qu; Kun Shang; Ping Gao; De Wen Ding; Cheng Jun Sun (Current Microbiology, 2020)

A high throughput method for screening deep-seeding tolerance in sorghum - Guihua Zou; Lengbo Zhou; Guowei Zhai; Yanqing Ding; Ping Lu; Heqin Liu; Xueqiang Zhen; Xiuhui Liu; Liyi Zhang; Zhanguo Xin; Heyun Chen (Genetic Resources and Crop Evolution, 2019)

Thermus caldilimi sp. nov., a thermophilic bacterium isolated from a geothermal area - Meng-Meng Li; Wen-Dong Xian; Xiao-Tong Zhang; Yi-Rui Yin; En-Min Zhou; Yi-Ping Ding; Lan Liu; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

The characteristics of moisture recycling and its impact on regional precipitation against the background of climate warming over Northwest China - Ping Wu; Yihui Ding; Yanju Liu; Xiucang Li (International Journal of Climatology, 2019)
From 1961 to 2015, annual and seasonal precipitation have shown a significant increase over Northwest China (NW). The change of precipitation is a combination result of the changing recycling precipitation (P w ) contributed by local evapotranspiration (ET) and changing precipitation contributed by advection moisture (P o ). In this paper, we calculated the ET based on the observation data of meteorological stations and the complementary relationship model. Then used an improved precipitation recycling model to analyse influential factors on the variation of precipitation over the NW from aspects of ET and advection moisture. The annual precipitation recycling ratio ( ρ ) fluctuates between 4% and 10% and shows an increasing trend at a rate of 0.3% /10a with a significance level of 0.01. ET, which is the internal supplier of the precipitable water, and advection moisture, which is the outside supplier of the precipitable water, both have displayed significantly increasing trends over the NW. The advection moisture contributes precipitation much more than ET, no matter in the annual scale or seasonal scales. In view of the spatial distribution, P w shows an increasing trend over the whole NW, but distinctly opposite spatial patterns of P o are found between the western area of NW (WNW) and the eastern area of NW (ENW). Such differences caused the precipitation is characterized by a wetting trend in WNW but a drying trend in ENW.

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Genome-wide association analysis of salt tolerance QTLs with SNP markers in maize (Zea mays L.) - Yonghong Xie; Yan Feng; Qi Chen; Feike Zhao; Shuijuan Zhou; Ying Ding; Xianliang Song; Ping Li; Baohua Wang (Genes & Genomics, 2019)

Interseismic Coupling in the Central Nepalese Himalaya: Spatial Correlation with the 2015 Mw 7.9 Gorkha Earthquake - Shuiping Li; Qi Wang; Gang Chen; Ping He; Kaihua Ding; Yunguo Chen; Rong Zou (Pure and Applied Geophysics, 2019)

Spatial Distribution of Organophosphorus and Brominated Flame Retardants in Surface Water, Sediment, Groundwater, and Wild Fish in Chengdu, China - Lin Hou; Jingyan Jiang; Zhiwei Gan; YuanYuan Dai; Ping Yang; Yan Yan; Sanglan Ding; Shijun Su; Xiaoming Bao (Archives of Environmental Contamination and Toxicology, 2019)

Genomic copy number variation of the CHKB gene alters gene expression and affects growth traits of Chinese domestic yak (Bos grunniens) breeds - Habtamu Abera Goshu; Min Chu; Wu Xiaoyun; Bao Pengjia; Ding Xue Zhi; Ping Yan (Molecular Genetics and Genomics, 2019)

LINC00511 knockdown prevents cervical cancer cell proliferation and reduces resistance to paclitaxel - Ben-Di Mao; Ping Xu; Yan Zhong; Wei-Wei Ding; Qing-Zhi Meng (Journal of Biosciences, 2019)

The distribution of plants and seed dispersers in response to habitat fragmentation in an artificial island archipelago - Jiajia Liu; Ferry Slik; David A. Coomes; Richard T. Corlett; Yanping Wang; Maxwell Wilson; Guang Hu; Ping Ding; Mingjian Yu (Journal of Biogeography, 2019)
Aim Small, old‐growth forest fragments generally have more small‐seeded plants than large patches, due to the disappearance of large seed dispersing vertebrates. This pattern may differ for secondary forest fragments where differential migration ability rather than persistence of seed dispersers may be driving plant community assembly. In this study, we investigated the effect of habitat fragmentation on seed dispersers and plant community structure in regenerating forests. Location The Thousand Island Lake, China. Taxon Plants, birds and mammals. Methods We compiled diversity and abundance data for birds and mammals on islands in the Thousand Island Lake, China. We also surveyed the secondary plant communities and measured seed dispersal traits. Results Community‐weighted mean seed size of woody plants decreased with island size. This pattern was related to compositional difference of the dispersers. We found that mammal diversity and abundance was only weakly or not related to island size; whereas bird diversity and abundance increased strongly with island size. Density of bird‐dispersed plants was significantly positively related with island size. Since birds tend to disperse smaller seeds than mammals, the trend in seed size may have been a consequence of the shift in relative abundance of the two disperser guilds. Main Conclusions Differential responses of seed dispersers to habitat fragmentation may lead to pervasive shifts in the plant community structure of regenerating forest fragments. Our study highlights the importance of keeping large continuous forests in order to retain mammals and their dispersal capabilities.

The antitoxin MqsA homologue in Pseudomonas fluorescens 2P24 has a rewired regulatory circuit through evolution - Yong Wang; Si‐Ping Zhang; Meng‐Yuan Zhang; Megan L. Kempher; Ding‐Ding Guo; Jian‐Ting Han; Xuanyu Tao; Yi Wu; Li‐Qun Zhang; Yong‐Xing He (Environmental Microbiology, 2019)
Summary The mqsRA operon encodes a toxin–antitoxin pair that was characterized to participate in biofilm and persister cell formation in Escherichia coli . Notably, the antitoxin MqsA possesses a C‐terminal DNA‐binding domain that recognizes the [5’‐AACCT(N) 2‐4 AGGTT‐3′] motif and acts as a transcriptional regulator controlling multiple genes including the general stress response regulator RpoS. However, it is unknown how the transcriptional circuits of MqsA homologues have changed in bacteria over evolutionary time. Here, we found mqsA in Pseudomonas fluorescens ( PfmqsA ) is acquired through horizontal gene transfer and binds to a slightly different motif [5′‐TACCCT(N) 3 AGGGTA‐3′], which exists upstream of the PfmqsRA operon. Interestingly, an adjacent GntR‐type transcriptional regulator, which was termed AgtR, is under negative control of PfMqsA. It was further demonstrated that PfMqsA reduces production of biofilm components through AgtR, which directly regulates the pga and fap operons involved in the synthesis of extracellular polymeric substances. Moreover, through quantitative proteomics analysis, we showed AgtR is a highly pleiotropic regulator that influences up to 252 genes related to diverse processes including chemotaxis, oxidative phosphorylation and carbon and nitrogen metabolism. Taken together, our findings suggest the rewired regulatory circuit of PfMqsA influences diverse physiological aspects of P. fluorescens 2P24 via the newly characterized AgtR.

Crop diversity facilitates soil aggregation in relation to soil microbial community composition driven by intercropping - Xiu-li Tian; Cheng-bao Wang; Xing-guo Bao; Ping Wang; Xiao-fei Li; Si-cun Yang; Guo-chun Ding; Peter Christie; Long Li (Plant and Soil, 2019)

Dynamics of maize straw residue 13C incorporation into aggregates of a Mollisol as affected by long-term fertilization - Ming Li; Yang Wang; Fan Ding; Yingde Xu; Ping Zhu; Xueli Ding; Jingkuan Wang (Journal of Soils and Sediments, 2019)

Evolution of pore-size distribution of intact loess and remolded loess due to consolidation - Jia-Ding Wang; Ping Li; Yan Ma; Sai K. Vanapalli (Journal of Soils and Sediments, 2019)

Ambient air pollution and the risk of stillbirth: a population-based prospective birth cohort study in the coastal area of China - Hongyan Zang; Han Cheng; Wenya Song; Mei Yang; Ping Han; Chunxiao Chen; Rui Ding (Environmental Science and Pollution Research, 2019)

The complete mitochondrial genome of Sanhe horse (Equus caballus) - Jie Pei; Min Chu; Pengjia Bao; Zhongcheng Sha; Xuezhi Ding; Ping Yan; Xian Guo (Conservation Genetics Resources, 2019)

Role of permafrost in resilience of social-ecological system and its spatio-temporal dynamics in the source regions of Yangtze and Yellow Rivers - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jian Ding (Journal of Mountain Science, 2019)

Epidemiological and aetiological characteristics of hand, foot and mouth disease cases 2011–2017 in Yixing, China - Yue Xiao; Jiangang Zhou; Huajun Zhang; Chao Ding; Ping Shi (Infectious Diseases, 2018)

RETRACTED ARTICLE: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2018)

Interhemispheric functional connectivity for Alzheimer’s disease and amnestic mild cognitive impairment based on the triple network model - Zheng-luan Liao; Yun-fei Tan; Ya-ju Qiu; Jun-peng Zhu; Yan Chen; Si-si Lin; Ming-hao Wu; Yan-ping Mao; Jiao-jiao Hu; Zhong-xiang Ding; En-yan Yu (Journal of Zhejiang University-SCIENCE B, 2018)

The complete mitochondrial genome of Shigaste humped cattle (Bos taurus) - Xian Guo; Jie Pei; Lin Xiong; Pengjia Bao; Yanbin Zhu; Basang Wangdui; Xiaoyun Wu; Min Chu; Ping Yan; Xuezhi Ding (Conservation Genetics Resources, 2018)

Thermus sediminis sp. nov., a thiosulfate-oxidizing and arsenate-reducing organism isolated from Little Hot Creek in the Long Valley Caldera, California - En-Min Zhou; Wen-Dong Xian; Chrisabelle C. Mefferd; Scott C. Thomas; Arinola L. Adegboruwa; Nathan Williams; Senthil K. Murugapiran; Jeremy A. Dodsworth; Rakesh Ganji; Meng-Meng Li; Yi-Ping Ding; Lan Liu; et al. (Extremophiles, 2018)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

Divergence in larval diapause induction between the rice and water-oat populations of the striped stem borer, Chilo suppressalis (Walker) (Lepidoptera: Crambidae) - Yuan Zhou; Dan Sun; Wei-Li Quan; Nan Ding; Wen Liu; Wei-Hua Ma; Xiao-Ping Wang (Environmental Science and Pollution Research, 2018)

Activation of histamine H4 receptor suppresses the proliferation and invasion of esophageal squamous cell carcinoma via both metabolism and non-metabolism signaling pathways - Gong-Hao He; Jia-Qi Ding; Xin Zhang; Wen-Mang Xu; Xiao-Qian Lin; Mei-Jin Huang; Ju Feng; Ping Wang; Wen-Ke Cai (Journal of Molecular Medicine, 2018)

The complete mitochondrial genome of Zhangmu cattle (Bos taurus) - Xian Guo; Pengjia Bao; Lin Xiong; Yanbin Zhu; Basang Wangdui; Xiaoyun Wu; Xuezhi Ding; Jie Pei; Ping Yan (Conservation Genetics Resources, 2018)

Complete mitochondrial genome of Anxi cattle (Bos taurus) - Xian Guo; Xuezhi Ding; Xiaoyun Wu; Pengjia Bao; Lin Xiong; Ping Yan; Jie Pei (Conservation Genetics Resources, 2018)

Paleoenvironmental implications of the calcium isotope characteristics in the MD81349 from the Nintyeast Ridge in the Indian Ocean - Feng Wang; Nianqiao Fang; Chaoyong Hu; Sarah Goldsmith; Yonghang Xu; Xuan Ding; Aijun Wang; Ping Chen; Rui Bao (Acta Oceanologica Sinica, 2018)

The importance of accounting for imperfect detection when estimating functional and phylogenetic community structure - Xingfeng Si; Marc W. Cadotte; Yuhao Zhao; Haonan Zhou; Di Zeng; Jiaqi Li; Tinghao Jin; Peng Ren; Yanping Wang; Ping Ding; Morgan W. Tingley (Ecology, 2018)
Incorporating imperfect detection when estimating species richness has become commonplace in the past decade. However, the question of how imperfect detection of species affects estimates of functional and phylogenetic community structure remains untested. We used long‐term counts of breeding bird species that were detected at least once on islands in a land‐bridge island system, and employed multi‐species occupancy models to assess the effects of imperfect detection of species on estimates of bird diversity and community structure by incorporating species traits and phylogenies. Our results showed that taxonomic, functional, and phylogenetic diversity were all underestimated significantly as a result of species’ imperfect detection, with taxonomic diversity showing the greatest bias. The functional and phylogenetic structure calculated from observed communities were both more clustered than those from the detection‐corrected communities due to missed distinct species. The discrepancy between observed and estimated diversity differed according to the measure of biodiversity employed. Our study demonstrates the importance of accounting for species’ imperfect detection in biodiversity studies, especially for functional and phylogenetic community ecology, and when attempting to infer community assembly processes. With datasets that allow for detection‐corrected community structure, we can better estimate diversity and infer the underlying mechanisms that structure community assembly, and thus make reliable management decisions for the conservation of biodiversity.

Effects of Rhizoma Alismatis extract on biochemical indices and adipose gene expression in oleic acid-induced hepatocyte injury in Jian carp (Cyprinus carpio var. Jian) - Jinliang Du; Rui Jia; Li-ping Cao; Weidong Ding; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2018)

Detrital apatite fission track constraints on Cenozoic tectonic evolution of the northeastern Qinghai-Tibet Plateau, China: Evidence from Cenozoic strata in Lulehe section, Northern Qaidam Basin - Ding-ding Du; Cheng-jun Zhang; Muhammad Saleem Mughal; Xiao-yu Wang; Dembele Blaise; Jun-ping Gao; Yuan Ma; Xin-rong Luo (Journal of Mountain Science, 2018)

Characterization of the complete mitochondrial genome of Kunlun Mountain type wild yak (Bos mutus) - Xiaoyun Wu; Min Chu; Xuezhi Ding; Xian Guo; Hongbo Wang; Pengjia Bao; Chunnian Liang; Ping Yan (Conservation Genetics Resources, 2018)

When the species–time–area relationship meets island biogeography: Diversity patterns of avian communities over time and space in a subtropical archipelago - Xiao Song; Robert D. Holt; Xingfeng Si; Mary C. Christman; Ping Ding (Journal of Biogeography, 2018)
Aim The species–area ( SAR ) and species–time relationships ( STR ) are of vital importance in community ecology. Previous studies suggest that a unified, general species–time–area relationship ( STAR ) may hold, with non‐independent scaling of richness across space and time. Most STAR studies to date have considered species accumulation curves in relatively homogeneous habitats. Here, we test the generality of the STAR in an island system and assess how factors other than area influence species richness, accumulation and turnover through time. Location Thousand Island Lake, China. Methods We surveyed bird communities on 36 islands using line transects, and calculated annual species richness of breeding birds from 2007 to 2015. We built island STAR models at island (island STAR ; ISTAR ) and transect levels (local community–time–area relationship; LCTAR ). We employed partial correlations and multiple regressions to examine potential influences of island attributes other than area (i.e. isolation, edge effect and habitat richness) on slopes of STR s. Results ISTAR and LCTAR models explained 88.8% and 83.1% of total variance, respectively, and both models have a negative space–time interaction. Richness scales comparably in space and time, for both whole‐island and transect‐level analyses. The partial correlation analysis showed that distance to mainland and perimeter‐to‐area ratio are significantly positively correlated with the time scalar ( w ), and habitat richness and w are negatively correlated. Multiple regression models identify perimeter‐to‐area ratio as particularly influential. Main conclusions The STAR pattern generalized to an island system where species turnover is high, indicating an interdependency of time and space in determining species richness. Islands have attributes other than area that influence patterns of species accumulation and turnover through time. Ecologists should consider the interdependence of space and time when characterizing species richness patterns.

Do seasonal species assemblages differ in their biogeography? Evidence from the spatial structure of bird communities on land‐bridge islands - Chuanwu Chen; Marcel Holyoak; Xingfeng Si; Yanping Wang; Ping Ding (Journal of Biogeography, 2018)
Aim We tested the effects of season and migratory status (residents‐versus‐seasonal migrants) on island biogeography of bird assemblages through partitioning beta diversity into richness and turnover components and community nestedness metrics. We predicted that total beta diversity, the richness component of beta diversity and community nestedness will be lower for bird assemblages in winter than in summer, and lowest of all for winter visitors. These predictions were derived from published ideas about resource availability, movement and habitat choice in birds in different seasons. Location Thousand Island Lake, China. Methods Bird species were sampled using line transects on 36 islands during five breeding and winter seasons (2009−2014). Birds were grouped into assemblages of winter residents, winter visitors and summer residents. Associations between beta diversity partitioning, island area, isolation and habitat richness were tested using partial Mantel correlations. We complemented these tests with measures of nestedness and null model approaches. Results Contrary to expectation, beta diversity, nestedness and difference of beta diversity or its components from null models were higher for winter residents than either summer resident or winter visitor assemblages. As predicted, winter visitors showed little association with habitat richness, and beta diversity was rarely different from null communities. Summer residents had the highest correlations of beta diversity components with habitat richness, but showed the lowest level of total beta diversity, a low richness component and were anti‐nested (less nested than random). Main conclusions Substantial differences were found in the biogeography of winter‐versus‐summer residents, and seasonal visitor (migratory)‐versus‐resident bird assemblages, which match expectations derived from bird biology and population ecology. Summer residents highlighted the role of habitat‐related niche differences, whereas winter residents showed area‐related selective extinction. By contrast, winter visitors appeared to be more randomly distributed.

A new arbutin derivative from the leaves of Vaccinium dunalianum wight - Na Li; Wei-Lin Zeng; Xu-Lu Luo; Chong-Ren Yang; Ying-Jun Zhang; Yong Ding; Ping Zhao (Natural Product Research, 2018)

The GABRB3 Polymorphism and its Association with Schizophrenia - Yi Liu; Xue-fei Sun; Mei Ding; Yong-ping Liu; Xi-cen Zhang; Hao Pang; Jia-xin Xing; Jin-feng Xuan; Xi Xia; Bao-jie Wang; Jun Yao (Journal of Molecular Neuroscience, 2018)

ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Mfn2-Mediated Preservation of Mitochondrial Function Contributes to the Protective Effects of BHAPI in Response to Ischemia - Xiao-Li Chen; Guo-Ping Zhang; Sheng-Long Guo; Jia-Qi Ding; Jia-Ji Lin; Qian Yang; Zhu-Yi Li (Journal of Molecular Neuroscience, 2017)

Dispersal modality determines the relative partitioning of beta diversity in spider assemblages on subtropical land‐bridge islands - Lingbing Wu; Xingfeng Si; Raphael K. Didham; Dapeng Ge; Ping Ding (Journal of Biogeography, 2017)
Aim To identify geographical drivers determining the relative partitioning of species replacement and richness difference or nestedness‐resultant components of beta diversity in spider groups with differing dispersal modalities. Location Thousand Island Lake, China. Methods We sampled spider assemblages on 31 land‐bridge islands for two years. Each species was classified into a dispersal group based on ballooning propensity (frequent, occasional or non‐ballooners). Two frameworks were used to separate beta diversity (β cc or β jac ) of each group into either species replacement (β ‐3 ) and richness difference (β rich ) components, or turnover (β jtu ) and nestedness‐resultant (β jne ) components. Mantel and partial Mantel tests were performed to determine correlations between pairwise dissimilarities and difference in island area, difference in distance to mainland and inter‐island distance for each group. Results The multiple‐island dissimilarity of spiders was primarily driven by turnover. Beta diversity (β cc or β jac ) was positively associated with difference in island area in frequent ballooners, and negatively associated with difference in island area in occasional ballooners. Difference in island area had positive effects on β jne for all groups, but negative effects on β ‐3 and β jtu for occasional or non‐ballooners. β rich was positively associated with difference in island area in frequent and non‐ballooners. We did not find any significant isolation effects for these three measures of dissimilarity. Main conclusions The dominant process of extinction resulted in a high contribution of turnover to the multiple‐island dissimilarity of spiders. Specifically, frequent ballooners contributed less turnover to multiple‐island dissimilarity than occasional and non‐ballooners. The most likely explanation for this is that frequent ballooners were potentially able to colonize all islands, whereas occasional and non‐ballooners were constrained by water barriers and were unable to occupy most islands. Contrasting dissimilarities among dispersal groups of spiders demonstrates the importance of beta diversity partitioning, and the mechanistic insight gained on trait‐dependence in community assembly.

Impacts of electron donor and acceptor on the performance of electrotrophic denitrification - Aqiang Ding; Ping Zheng; Meng Zhang; Qianqian Zhang (Environmental Science and Pollution Research, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Complete mitochondrial genome of Qingyang donkey (Equus asinus) - Xian Guo; Pengjia Bao; Jie Pei; Xuezhi Ding; Chunnian Liang; Ping Yan; Dengxue Lu (Conservation Genetics Resources, 2017)

The complete mitochondrial genome of Chakouyi horse (Equus caballus) - Xian Guo; Min Chu; Xuezhi Ding; Jie Pei; Ping Yan (Conservation Genetics Resources, 2017)

Carboniferous Alaskan-type complex along the Sino–Mongolian boundary, southern margin of the Central Asian Orogenic Belt - Yuruo Shi; Linlin Li; Alfred Kröner; Jing Ding; Wei Zhang; Zengbao Huang; Ping Jian (Acta Geochimica, 2017)

Analysis of Dynamic Fracture Compliance Based on Poroelastic Theory. Part I: Model Formulation and Analytical Expressions - Ding Wang; Shou-Li Qu; Ping-Bo Ding; Qun Zhao (Pure and Applied Geophysics, 2017)

Work stress, family stress and asthma: a cross-sectional study among women in China - Adrian Loerbroks; Hui Ding; Wei Han; Hong Wang; Jiang-Ping Wu; Liu Yang; Peter Angerer; Jian Li (International Archives of Occupational and Environmental Health, 2017)

Koninginins R-S from the endophytic fungus Trichoderma koningiopsis - Ming Hu; Qi-Ling Li; Ya-Bin Yang; Kai Liu; Cui-Ping Miao; Li-Xing Zhao; Zhong-Tao Ding (Natural Product Research, 2017)

Isoquercetin Ameliorates Cerebral Impairment in Focal Ischemia Through Anti-Oxidative, Anti-Inflammatory, and Anti-Apoptotic Effects in Primary Culture of Rat Hippocampal Neurons and Hippocampal CA1 Region of Rats - Cai-Ping Wang; Yun-Wei Shi; Miao Tang; Xiao-Chuan Zhang; Yun Gu; Xin-Miao Liang; Zhi-Wei Wang; Fei Ding (Molecular Neurobiology, 2017)

Novel compound heterozygous mutations in ZAP70 in a Chinese patient with leaky severe combined immunodeficiency disorder - Qing Liu; Yan-Ping Wang; Qiao Liu; Qin Zhao; Xue-Mei Chen; Xiu-Hong Xue; Li-Na Zhou; Yuan Ding; Xue-Mei Tang; Xiao-Dong Zhao; Zhi-Yong Zhang (Immunogenetics, 2017)

Atmospheric circulation and dynamic mechanism for persistent haze events in the Beijing–Tianjin–Hebei region - Ping Wu; Yihui Ding; Yanju Liu (Advances in Atmospheric Sciences, 2017)

Source analysis of organic matter in swine wastewater after anaerobic digestion with EEM-PARAFAC - Zhuo Zeng; Ping Zheng; Aqiang Ding; Meng Zhang; Ghulam Abbas; Wei Li (Environmental Science and Pollution Research, 2017)

Observed deformation characteristics of a deep excavation for the spring area in Jinan, China - Ding-wen Zhang; Ji-cheng Shu; Jian-ping Sun (Journal of Mountain Science, 2017)

The long-term variation of extreme heavy precipitation and its link to urbanization effects in Shanghai during 1916–2014 - Ping Liang; Yihui Ding (Advances in Atmospheric Sciences, 2017)

A novel culture platform for fast proliferation of human annulus fibrosus cells - Li Xiao; Mengmeng Ding; Osama Saadoon; Eric Vess; Andrew Fernandez; Ping Zhao; Li Jin; Xudong Li (Cell and Tissue Research, 2017)

Use of liposomal doxorubicin for adjuvant chemotherapy of breast cancer in clinical practice - Ming Zhao; Xian-feng Ding; Jian-yu Shen; Xi-ping Zhang; Xiao-wen Ding; Bin Xu (Journal of Zhejiang University-SCIENCE B, 2017)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

On empty islands and the small‐island effect - Yanping Wang; Virginie Millien; Ping Ding (Global Ecology and Biogeography, 2016)
Aim The small‐island effect (SIE) has become a widely accepted part of the theoretical framework of island biogeography. A major criticism of SIE studies is the exclusion of empty islands from analyses. However, the generality and underlying factors determining the role of empty islands in generating SIEs remain obscure because few published datasets include islands with no species. The aim of this study was thus to evaluate the prevalence and underlying factors determining the role of empty islands in generating SIEs. Location Global. Methods We compiled 278 datasets that included empty islands. For each dataset, we compared the fit of a logarithmic model with two breakpoint models separately for all the islands and for datasets excluding empty islands to determine the role of empty islands in generating SIEs. We then employed multinomial logistic regressions and an information‐theoretic approach to determine which combination of island characteristics was important in determining the role of empty islands in generating SIEs. Results Among 211 datasets with adequate fits, the exclusion of empty islands changed the evidence for an SIE in 68 cases (32.2%). SIEs were quite prevalent, both for all the islands (104 cases, 49.3%) and for datasets excluding empty islands (73 cases, 34.6%). Our results were not consistent with the hypothesis that excluding empty islands would increase the evidence for an SIE. Model selection and relative variable importance indicated that the number of empty islands, the minimum area of empty islands and area ratio were important variables that determined the role of empty islands in generating SIEs. Main conclusions Our study demonstrates that the effect of empty islands in generating SIEs is quite prevalent. The exclusion of empty islands is thus an important methodological shortcoming for the detection of SIEs. We conclude that, for the robust detection of SIEs, empty islands should not be excluded in future studies.

Experimental Investigation of the Mechanical Behavior of Bedded Rocks and Its Implication for High Sidewall Caverns - Yang-Yi Zhou; Xia-Ting Feng; Ding-Ping Xu; Qi-Xiang Fan (Rock Mechanics and Rock Engineering, 2016)

Genetic Diversity Analysis of Sugarcane Germplasm Based on Fluorescence-Labeled Simple Sequence Repeat Markers and a Capillary Electrophoresis-based Genotyping Platform - Qian You; Yong-Bao Pan; Li-Ping Xu; Shi-Wu Gao; Qin-Nan Wang; Ya-Chun Su; Yong-Qing Yang; Qi-Bin Wu; Ding-Gang Zhou; You-Xiong Que (Sugar Tech, 2016)

Cholangiocarcinoma-derived exosomes inhibit the antitumor activity of cytokine-induced killer cells by down-regulating the secretion of tumor necrosis factor-α and perforin - Jiong-huang Chen; Jian-yang Xiang; Guo-ping Ding; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

Seasonal variation of pheophorbide a and flavonoid in different organs of two Carpinus species and its correlation with immunosuppressive activity - Qianqian Sheng; Xianying Fang; Zunling Zhu; Wei Xiao; Zhenzhong Wang; Gang Ding; Linguo Zhao; Yujian Li; Ping Yu; Zhibin Ding; Qinru Sun (In Vitro Cellular & Developmental Biology - Animal, 2016)

A new phenolic compound with antioxidant activity from the branches and leaves of Pyrus pashia - Zhen-Jie Li; Xi Zheng; Chun-Ping Wan; Le Cai; Ying Li; Lin Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Controls of seed quantity and quality on seedling recruitment of smith fir along altitudinal gradient in southeastern Tibetan Plateau - Jing-sheng Wang; Ji-guang Feng; Bao-xiong Chen; Pei-li Shi; Jun-long Zhang; Jiang-ping Fang; Zhi-kai Wang; Shuai-chen Yao; Lu-bin Ding (Journal of Mountain Science, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

Adverse effect of DEHP exposure on the serum insulin level of Balb/c mice - Jing Wang; Jinquan Li; Kashif Rafiq Zahid; Kun Wang; Yan Qian; Ping Ma; Shumao Ding; Xu Yang; Xianliang Wang (Molecular & Cellular Toxicology, 2016)

Impacts of snow disaster on meat production and adaptation: an empirical analysis in the yellow river source region - Yi-ping Fang; Chen Zhao; Yong-jian Ding; Da-he Qin; Jia-li Huang (Sustainability Science, 2016)

Polymorphisms in VEGF-A are associated with COPD risk in the Chinese population from Hainan province - YIPENG DING; HUAN NIU; YIZHOU LI; PING HE; QUANNI LI; YANHONG OUYANG; MIN LI; ZHIGAO HU; YOUQING ZHONG; PEI SUN; TIANBO JIN (Journal of Genetics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

A theoretical analysis of the bearing performance of vertically loaded large-diameter pipe pile groups - Xuanming Ding; Ting Zhang; Ping Li; Ke Cheng (Journal of Ocean University of China, 2016)

Polychlorinated biphenyls and organochlorine pesticides in atmospheric particulate matter of Northern China: distribution, sources, and risk assessment - Shuangshuang Ding; Faqin Dong; Bin Wang; Shu Chen; Liufei Zhang; Mengjun Chen; Mei Gao; Ping He (Environmental Science and Pollution Research, 2015)

Rice grassy stunt virus nonstructural protein p5 serves as a viral suppressor of RNA silencing and interacts with nonstructural protein p3 - Chao Zhang; Xiao-juan Liu; Kang-cheng Wu; Lu-Ping Zheng; Zuo-mei Ding; Fei Li; Peng Zou; Liang Yang; Jian-guo Wu; Zu-jian Wu (Archives of Virology, 2015)

HPLC simultaneous determination of arbutin, chlorogenic acid and 6′- O -caffeoylarbutin in different parts of Vaccinium dunalianum Wight - Xu-Lu Luo; Na Li; Min Xu; Hong-Tao Zhu; Peng He; Yong Ding; Ping Zhao; Ying-Jun Zhang (Natural Product Research, 2015)

Kinetic changes of regulatory B10 cells in collagen-induced arthritis could be regulated by cytokines IFN-γ and TGF-β1 - Zhaohui Zheng; Tao Liu; Xueyi Li; Jin Ding; Yuan Feng; Jinlin Miao; Xing Luo; Zhenbiao Wu; Ping Zhu (Inflammation Research, 2015)

N2O emissions from banana plantations in tropical China as affected by the application rates of urea and a urease/nitrification inhibitor - Tongbin Zhu; Junhua Zhang; Ping Huang; Long Suo; Cong Wang; Weixin Ding; Lei Meng; Kexin Zhou; Zhewei Hu (Biology and Fertility of Soils, 2015)

Preparation of malathion MIP-SPE and its application in environmental analysis - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Lei Shi; Ming Xing; Ping Guo; Yuan Ding; Hong Yang (Environmental Monitoring and Assessment, 2015)

Remobilizing deleted piggyBac vector post-integration for transgene stability in silkworm - Feng Wang; Riyuan Wang; Yuancheng Wang; Hanfu Xu; Lin Yuan; Huan Ding; Sanyuan Ma; You Zhou; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2015)

Seasonal suspended particles distribution patterns in Western South Yellow Sea based on Acoustic Doppler Current Profiler observation - Jianchao Li; Guangxue Li; Jishang Xu; Lulu Qiao; Ping Dong; Dong Ding; Shidong Liu; Pingkuo Sun (Journal of Ocean University of China, 2015)

Prefrontal dysfunction and a monkey model of schizophrenia - Ping Mao; Ding Cui; Xu-Dong Zhao; Yuan-Ye Ma (Neuroscience Bulletin, 2015)

Genetic polymorphisms of CYP2D6*10 and the effectiveness of combined tamoxifen citrate and testosterone undecanoate treatment in infertile men with idiopathic oligozoospermia - Kai-fa Tang; Yi-li Zhao; Shang-shu Ding; Qi-fei Wu; Xing-yang Wang; Jia-qi Shi; Fa Sun; Jun-ping Xing (Journal of Zhejiang University-SCIENCE B, 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Effects of continuous passage on immunomodulatory properties of human adipose-derived stem cells - Xiyou Wang; Cuilong Liu; Shaodan Li; Yong Xu; Ping Chen; Yi Liu; Qiang Ding; Wasilijiang Wahapu; Baofa Hong; Minghui Yang (Cell and Tissue Banking, 2015)

Increase of Zinc Finger Protein 179 in Response to CCAAT/Enhancer Binding Protein Delta Conferring an Antiapoptotic Effect in Astrocytes of Alzheimer’s Disease - Shao-Ming Wang; Yi-Chao Lee; Chiung-Yuan Ko; Ming-Derg Lai; Ding-Yen Lin; Ping-Chieh Pao; Jhih-Ying Chi; Yu-Wei Hsiao; Tsung-Lin Liu; Ju-Ming Wang (Molecular Neurobiology, 2015)

Identification of QTLs associated with salt or alkaline tolerance at the seedling stage in rice under salt or alkaline stress - Jing-long Liang; Ying-ping Qu; Chun-gang Yang; Xiao-ding Ma; Gui-lan Cao; Zheng-wu Zhao; San-yuan Zhang; Tao Zhang; Long-zhi Han (Euphytica, 2015)

Effect of salt treatment on growth, isoenzymes and metabolites of Andrographis paniculata (Burm. f.) Nees - Yan-hua Shao; Jun-li Gao; Xiang-wei Wu; Qian Li; Jian-gang Wang; Ping Ding; Xiao-ping Lai (Acta Physiologiae Plantarum, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Study on the Preparation of Nifedipine-Loaded Oral Copolymer Micelles and its Pharmacokinetics in Rats - Yue-Hui Yang; Ping-Tian Ding (Cell Biochemistry and Biophysics, 2015)

Removal and Recovery of U(VI) from Low Concentration Radioactive Wastewater by Ethylenediamine-Modified Biomass of Aspergillus niger - De Xin Ding; Xin Xin; Le Li; Nan Hu; Guang Yue Li; Yong Dong Wang; Ping Kun Fu (Water, Air, & Soil Pollution, 2014)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Turnover of breeding bird communities on islands in an inundated lake - Xingfeng Si; Stuart L. Pimm; Gareth J. Russell; Ping Ding (Journal of Biogeography, 2014)
Aim MacArthur and Wilson's theory of island biogeography proposes that the rate at which species colonize an island depends on the island's isolation (distance effect), whereas the local extinction rate depends on its area (area effect). Alternative hypotheses recognize that area can affect the colonization rate (target effect) and that isolation can affect the extinction rate (rescue effect) and, moreover, that these relationships may dominate. We quantify these relationships and associated turnover rates and incidence using long‐term counts of breeding bird communities on islands in an inundated lake. Location Thousand Island Lake, China. Methods We assessed the occupancy and behaviour of breeding birds on 37 islands from 2007 to 2012. We estimated the effects of area, isolation and other biogeographical parameters on the frequencies of colonization and extinction events using multivariate logistic regression. We then extended these results to derived properties such as species turnover rates and incidence. Results Extinction rates decreased and colonization rates increased on larger islands. Isolation had no significant effect on colonization or extinction rates. Islands had high species turnover overall, and turnover rates followed the same pattern as extinction rates with different areas and isolations. Pool turnover, which controls for the number of species in the pool, was higher on large islands. Species richness also increased with area. Our study of bird communities supported area and target effects, but not distance and rescue effects. Main conclusions Island area was a better predictor of colonization and extinction than isolation, probably because of the relatively small scale ( c . 580 km 2 ) and homogeneous vegetation structure of our research system, and the strong dispersal ability of birds. We conclude that the differences between our observations and theoretical predictions, or results from other studies that measured colonization and extinction directly, are consistent with the particular biogeography of these islands.

Influence of transgenic rice expressing a fused Cry1Ab/1Ac protein on frogs in paddy fields - Jia-Mei Wang; Xiu-Ping Chen; Yu-Yong Liang; Hao-Jun Zhu; Jia-Tong Ding; Yu-Fa Peng (Ecotoxicology, 2014)

The Adhesion AND Growth of Both the Human Primary Gingival Epithelial Cells and Streptococcus Mutans on Micro-Arc Oxidized Titanium - Jiangning Lv; Hongwei Li; Ying Mu; ShuMin Wang; Jing Sun; Jun Jiang; Ping Ding; Baolin Liu (Cell Biochemistry and Biophysics, 2014)

Association between CLPTM1L polymorphisms (rs402710 and rs401681) and lung cancer susceptibility: evidence from 27 case–control studies - De-ping Zhao; Chen-lu Yang; Xiao Zhou; Jia-an Ding; Ge-ning Jiang (Molecular Genetics and Genomics, 2014)

Interdecadal variability of the East Asian winter monsoon and its possible links to global climate change - Yihui Ding; Yanju Liu; Sujie Liang; Xiaoqing Ma; Yingxian Zhang; Dong Si; Ping Liang; Yafang Song; Jin Zhang (Journal of Meteorological Research, 2014)

Neuroprotective effect of schizandrin A on oxygen and glucose deprivation/reperfusion-induced cell injury in primary culture of rat cortical neurons - Cai-Ping Wang; Gui-Cai Li; Yun-Wei Shi; Xiao-Chuan Zhang; Jian-Long Li; Zhi-Wei Wang; Fei Ding; Xin-Miao Liang (Journal of Physiology and Biochemistry, 2014)

Isolation and expression of CsFAD7 and CsFAD8, two genes encoding ω-3 fatty acid desaturase from Camellia sinensis - Qing-Ping Ma; En You; Jing Wang; Yu Wang; Zhao-Tang Ding (Acta Physiologiae Plantarum, 2014)

Differential role of Rac in the basolateral amygdala and cornu ammonis 1 in the reconsolidation of auditory and contextual Pavlovian fear memory in rats - Ping Wu; Zeng-Bo Ding; Shi-Qiu Meng; Hao-Wei Shen; Shi-Chao Sun; Yi-Xiao Luo; Jian-Feng Liu; Lin Lu; Wei-Li Zhu; Jie Shi (Psychopharmacology, 2014)

Clodronate-superparamagnetic iron oxide-containing liposomes attenuate renal injury in rats with severe acute pancreatitis - Sheng-chun Dang; Yan-hua Zeng; Ping-jiang Wang; Bao-ding Chen; Rong-fang Chen; Arun Kumar Singh; Pankaj Kumar; Shu Feng; Lei Cui; Hao Wang; Jian-xin Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

The Role of ABA in the Maturation and Postharvest Life of a Nonclimacteric Sweet Cherry Fruit - Hao Luo; ShengJie Dai; Jie Ren; CaiXia Zhang; Ying Ding; Zhuang Li; Yufei Sun; Kai Ji; Yanping Wang; Qian Li; Pei Chen; Chaorui Duan; et al. (Journal of Plant Growth Regulation, 2014)

Fluid Flow-Induced Calcium Response in Osteoclasts: Signaling Pathways - Ping Li; Chenglin Liu; Man Hu; Mian Long; Ding Zhang; Bo Huo (Annals of Biomedical Engineering, 2014)

Inactivation kinetics of formaldehyde on N-acetyl-β-d-glucosaminidase from Nile tilapia (Oreochromis niloticus) - Wei-Ni Zhang; Ding-Ping Bai; Xin-Yu Lin; Qing-Xi Chen; Xiao-Hong Huang; Yi-Fan Huang (Fish Physiology and Biochemistry, 2014)

Photosynthetic activity and efficiency of Bothriochloa ischaemum and Lespedeza davurica in mixtures across growth periods under water stress - Wei-Zhou Xu; Xi-Ping Deng; Bing-Cheng Xu; Zhi-Juan Gao; Wen-Li Ding (Acta Physiologiae Plantarum, 2014)

Estrogen receptor α gene PvuII polymorphism and coronary artery disease: a meta-analysis of 21 studies - Jie Ding; Hui Xu; Xiang Yin; Fu-rong Zhang; Xiao-ping Pan; Yi-an Gu; Jun-zhu Chen; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2014)

Host plant richness explains diversity of ectomycorrhizal fungi: Response to the comment of Tedersoo et al . (2014) - Cheng Gao; Nan‐Nan Shi; Yue‐Xing Liu; Yong Zheng; Qiong Ding; Xiang‐Cheng Mi; Ke‐Ping Ma; Tesfaye Wubet; François Buscot; Liang‐Dong Guo (Molecular Ecology, 2014)
Exploring the relationships between the biodiversity of groups of interacting organisms yields insight into ecosystem stability and function (Hooper et al . ; Wardle ). We demonstrated positive relationships between host plant richness and ectomycorrhizal ( EM ) fungal diversity both in a field study in subtropical China (Gutianshan) and in a meta‐analysis of temperate and tropical studies (Gao et al . ). However, based on re‐evaluation of our data sets, Tedersoo et al . ( ) argue that the observed positive correlation between EM fungal richness and EM plant richness at Gutianshan and also in our metastudies was based mainly from (i) a sampling design with inconsistent species pool and (ii) poor data compilation for the meta‐analysis. Accordingly, we checked our data sets and repeated the analysis performed by Tedersoo et al . ( ). In contrast to Tedersoo et al . ( ), our re‐analysis still confirms a positive effect of plant richness on EM fungal diversity in Gutianshan, temperate and tropical ecosystems, respectively.

Analysis of the promoter region of the RuBisCO gene of Arthrospira (Spirulina) platensis - Peizhen Li; Liang Zhao; Xiaomin Xu; Chenyang Xu; Chunlei Jin; Yi Xu; Jiaopeng Zhou; Ying Zhang; Kangfu Lei; Jun Ying; Ping Ren; Lei Yang; et al. (Journal of Applied Phycology, 2014)

High-efficiency system for construction and evaluation of customized TALENs for silkworm genome editing - Feng Wang; Sanyuan Ma; Hanfu Xu; Jianping Duan; Yuancheng Wang; Huan Ding; Yuanyuan Liu; Xiaogang Wang; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2013)

An experimental study on the shear strength behaviour of an interlayered shear weakness zone - Ding-Ping Xu; Xia-Ting Feng; Yu-Jun Cui (Bulletin of Engineering Geology and the Environment, 2013)

Overweight and Obesity Associated With Increased Total Serum Calcium Level: Comparison of Cross-sectional Data in the Health Screening for Teaching Faculty - Xiao-hua Ren; Ying-shui Yao; Lian-ping He; Yue-long Jin; Wei-wei Chang; Jie Li; Yan Chen; Xiu-li Song; Hui Tang; Ling-ling Ding; Dao-xia Guo; Chao-ping Li (Biological Trace Element Research, 2013)

Polymorphic microsatellite loci in Chinese piebald odorous frog (Odorrana schmackeri) - YU WANG; PING DING (Journal of Genetics, 2013)

Design, synthesis and antidepressant activity evaluation 2′-hydroxy-4′,6′-diisoprenyloxychalcone derivatives - Li-Ping Guan; Dong-Hai Zhao; Yue Chang; Yu Sun; Xiao-Li Ding; Jing-Fei Jiang (Medicinal Chemistry Research, 2013)

Molecular characteristics and evolutionary analysis of field Marek’s disease virus prevalent in vaccinated chicken flocks in recent years in China - Zu-Hua Yu; Man Teng; Jun Luo; Xin-Wei Wang; Ke Ding; Le-Le Yu; Jing-Wei Su; Jia-Qi Chi; Pu Zhao; Bo Hu; Gai-Ping Zhang; Ju-Xiong Liu (Virus Genes, 2013)

Region-specific role of Rac in nucleus accumbens core and basolateral amygdala in consolidation and reconsolidation of cocaine-associated cue memory in rats - Zeng-Bo Ding; Ping Wu; Yi-Xiao Luo; Hai-Shui Shi; Hao-Wei Shen; Shen-Jun Wang; Lin Lu (Psychopharmacology, 2013)

Dynamic analysis for gene expression profiles of endothelial colony forming cells under hypoxia - De-Cai Yu; Wen-Du Feng; Xian-Biao Shi; Zhi-Yong Wang; Wei Ge; Chun-Ping Jiang; Xi-Tai Sun; Yi-Tao Ding (Genes & Genomics, 2013)

Interstitial cells of Cajal mediate excitatory sympathetic neurotransmission in guinea pig prostate - Jiang-ping Wang; Guo-fu Ding; Qin-zhang Wang (Cell and Tissue Research, 2013)

Host plant genus‐level diversity is the best predictor of ectomycorrhizal fungal diversity in a Chinese subtropical forest - Cheng Gao; Nan‐Nan Shi; Yue‐Xing Liu; Kabir G. Peay; Yong Zheng; Qiong Ding; Xiang‐Cheng Mi; Ke‐Ping Ma; Tesfaye Wubet; François Buscot; Liang‐Dong Guo (Molecular Ecology, 2013)
Microbial diversity is generally far higher than plant diversity, but the relationship between microbial diversity and plant diversity remains enigmatic. To shed light on this problem, we examined the diversity of a key guild of root‐associated microbes, that is, ectomycorrhizal ( EM ) fungi along a plant diversity gradient in a Chinese subtropical forest. The results indicated that EM fungal diversity was positively correlated with host plant diversity. Furthermore, this relationship was best predicted by host genus‐level diversity, rather than species‐level diversity or family‐level diversity. The generality of this finding was extended beyond our study system through the analyses of 100 additional studies of EM fungal communities from tropical and temperate forests. Here as well, EM fungal lineage composition was significantly affected by EM plant diversity levels, and some EM fungal lineages were co‐associated with some host plant genera. These results suggest a general diversity maintenance mechanism for host‐specific microbes based on higher order host plant phylogenetic diversity.

A comparison of the larval overwintering biology of the striped stem borer, Chilo suppressalis (Lepidoptera: Crambidae), in rice and water-oat fields - Nan Ding; Peter Dalin; Qing-Hua Zhu; Wei-Hua Ma; Fen Zhu; Xiao-Ping Wang (Applied Entomology and Zoology, 2013)

Perifosine Induces Cell Apoptosis in Human Osteosarcoma Cells: New Implication for Osteosarcoma Therapy? - Chen Yao; Jian-jun Wei; Zu-yu Wang; Hui-min ding; Dong Li; Shi-chang Yan; Yong-jiang Yang; Zhang-ping Gu (Cell Biochemistry and Biophysics, 2013)

Phylogenetic resolution and systematics of the Asian tree frogs, Rhacophorus (Rhacophoridae, Amphibia) - Jia‐Tang Li; Yang Li; Robert W. Murphy; Ding‐Qi Rao; Ya‐Ping Zhang (Zoologica Scripta, 2012)
Li, J.T., Li, Y., Murphy, R.W., Rao, D.‐Q. & Zhang, Y.‐P. (2012). Phylogenetic resolution and systematics of the Asian tree frogs, Rhacophorus (Rhacophoridae, Amphibia). — Zoologica Scripta , 41 , 557–570. The treefrog genus Rhacophorus , a large genus with 80 species, has a wide range, occurring eastward from India to China, Japan, South‐east Asia, the Greater Sunda Islands and the Philippines. The phylogenetic relationships and taxonomic recognition of many species are very controversial. To stabilize the taxonomy, the phylogenetic relationships among about 52 species are investigated from 96 samples using mtDNA sequence data. Matrilineal relationships based on maximum likelihood and Bayesian inference methods resolve three well‐supported lineages (A, B and C), although the phylogenetic relationships among three lineages remain ambiguous. Analyses support recognition of two previously assigned subgenera, Leptomantis and Rhacophorus , and these correspond to lineages A and B, respectively. Given that we have three strongly supported lineages, that these lineages are morphologically distinct, and the constrained geographic distributions of these groups, we recognize each lineage as a taxon. Subgenus Leptomantis includes species mainly from Malaysia, Indonesia and the Philippines. Subgenus Rhacophorus contains a mix of species occurring in India, Indochina and southern China. Lineage C accommodates species distributed mostly in East Asia, including Japan and China. Based on genetic and morphological data from type localities, the taxonomic recognition of some species needs to be reconsidered. Rhacophorus pingbianensis and Polypedates spinus are considered as junior synonyms of Rhacophorus duboisi . Specimens of Rhacophorus rhodopus from Vietnam and Hainan, China likely represent an undescribed, cryptic species.

The impact of E-cadherin expression on non-small cell lung cancer survival: a meta-analysis - Ying Wu; Hong-Bing Liu; Ming Ding; Jian-Nan Liu; Ping Zhan; Xiao-Su Fu; Gan Lu (Molecular Biology Reports, 2012)

Fluid Flow-Induced Calcium Response in Early or Late Differentiated Osteoclasts - Ping Li; Man Hu; Shujin Sun; Yan Zhang; Yuxin Gao; Mian Long; Bo Huo; Ding Zhang (Annals of Biomedical Engineering, 2012)

Pseudolaric acid B-driven phosphorylation of c-Jun impairs its role in stabilizing HIF-1alpha: a novel function-converter model - Bing Yu; Mei-Hong Li; Wei Wang; Ying-Qing Wang; Yi Jiang; Sheng-Ping Yang; Jian-Min Yue; Jian Ding; Ze-Hong Miao (Journal of Molecular Medicine, 2012)

Callose deposition in the phloem plasmodesmata and inhibition of phloem transport in citrus leaves infected with “Candidatus Liberibacter asiaticus” - Eun-Ji Koh; Lijuan Zhou; Donna S. Williams; Jiyoung Park; Ningyuan Ding; Yong-Ping Duan; Byung-Ho Kang (Protoplasma, 2012)

Interleukin-17 contributes to cardiovascular diseases - Hua-Sheng Ding; Jun Yang; Jian Yang; Jia-Wang Ding; Ping Chen; Ping Zhu (Molecular Biology Reports, 2012)

Degradation of mouse NTE-related esterase by macroautophagy and the proteasome - Ping-An Chang; Yu-Ying Chen; Ding-Xin Long; Wen-Zhen Qin; Xiao-Ling Mou (Molecular Biology Reports, 2012)

Richness and composition of plants and birds on land‐bridge islands: effects of island attributes and differential responses of species groups - Mingjian Yu; Guang Hu; Kenneth J. Feeley; Jianguo Wu; Ping Ding (Journal of Biogeography, 2012)
Aim To test relationships between the richness and composition of vascular plants and birds and attributes of habitat fragments using a model land‐bridge island system, and to investigate whether the effects of fragmentation differ depending on species natural history traits. Location Thousand Island Lake, China. Methods We compiled presence/absence data of vascular plant and bird species through exhaustive surveys of 41 islands. Plant species were assigned to two categories: shade‐intolerant and shade‐tolerant species; bird species were assigned to three categories: edge, interior, and generalist species. We analysed the relationships between island attributes (area, isolation, elevation, shape complexity, and perimeter to area ratio) and species richness using generalized linear models (GLMs). We also investigated patterns of composition in relation to island attributes using ordination (redundancy analysis). Results We found that island area explained a high degree of variation in the species richness of all species groups. The slope of the species–area relationship ( z ) was 0.16 for all plant species and 0.11 for all bird species. The lowest z ‐value was for generalist birds (0.04). The species richness of the three plant species groups was associated with island area per se , while that of all, generalist, and interior birds was explained mainly by elevation, and that of edge bird species was associated primarily with island shape. Patterns of species composition were most strongly related to elevation, island shape complexity, and perimeter to area ratio rather than to island area per se. Species richness had no significant relationship with isolation, but species composition did. We also found differential responses among the species groups to changes in island attributes. Main conclusions Within the Thousand Island Lake system, the effects of fragmentation on both bird and plant species appear to be scale‐dependent and taxon‐specific. The number of plant species occurring on an island is strongly correlated with island area, and the richness of birds and the species composition of plants and birds are associated with variables related to habitat heterogeneity. We conclude that the effects of fragmentation on species diversity and composition depend not only on the degree of habitat loss but also on the specific patterns of habitat fragmentation.

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

Saline conducted electric coagulation (SCEC): original experience in experimental hepatectomy - Guo-ping Ding; Li-ping Cao; Da-ren Liu; Ri-sheng Que (Journal of Zhejiang University-SCIENCE B, 2012)

Application of multiplex reverse transcription-ligase detection reaction-polymerase chain reaction (MRLP) mediated universal DNA microarray for detecting potato viruses in field samples - Ping Wang; Yao Guo; Ju-Hui Cheng; Qin-Fang Dong; Xian-Feng Ding; Jiang-Feng Guo; Yong-Hou Jiang (European Journal of Plant Pathology, 2012)

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Parallel synthesis of novel antitumor agents: 1,2,3-triazoles bearing biologically active sulfonamide moiety and their 3D-QSAR - Lili Ou; Shuang Han; Wenbo Ding; Ping Jia; Bo Yang; Jose L. Medina-Franco; Marc A. Giulianotti; Jian-Zhong Chen; Yongping Yu (Molecular Diversity, 2011)

Diversity and composition of ectomycorrhizal community on seedling roots: the role of host preference and soil origin - Qiong Ding; Yu Liang; Pierre Legendre; Xin-hua He; Ke-quan Pei; Xiao-jun Du; Ke-ping Ma (Mycorrhiza, 2011)

Transumbilical single-port laparoscopic cholecystectomy using traditional laparoscopic instruments: a report of thirty-six cases - Li-ping Cao; Ri-sheng Que; Fan Zhou; Guo-ping Ding; De-xi Jing (Journal of Zhejiang University-SCIENCE B, 2011)

Mercury Biomagnification in the Aquaculture Pond Ecosystem in the Pearl River Delta - Zhang Cheng; Peng Liang; Ding-Ding Shao; Sheng-Chun Wu; Xiang-Ping Nie; Kun-Ci Chen; Kai-Bin Li; Ming-Hung Wong (Archives of Environmental Contamination and Toxicology, 2011)

Enhanced Gene Transduction into Skeletal Muscle of Mice In Vivo with Pluronic Block Copolymers and Ultrasound Exposure - Yun-Chao Chen; Li-Ping Jiang; Na-Xiang Liu; Lu Ding; Xiao-Ling Liu; Zhi-Hui Wang; Kai Hong; Qing-Ping Zhang (Cell Biochemistry and Biophysics, 2011)

Economic loss versus ecological gain: the outbreaks of invaded pinewood nematode in China - Mingjian Yu; Xuehong Xu; Ping Ding (Biological Invasions, 2011)

Seismic attribute extraction based on HHT and its application in a marine carbonate area - Ya-Ping Huang; Jian-Hua Geng; Guang-Fa Zhong; Tong-Lou Guo; Yong Pu; Kong-Yun Ding; Ji-Qiang Ma (Applied Geophysics, 2011)

A phylogeographic, demographic and historical analysis of the short‐tailed pit viper ( Gloydius brevicaudus ): evidence for early divergence and late expansion during the Pleistocene - LI DING; XIAO‐NI GAN; SHUN‐PING HE; ER‐MI ZHAO (Molecular Ecology, 2011)
The impact of quaternary glaciation in eastern China on local fanua and flora has been a topic of considerable interest. We used mitochondrial DNA (mtDNA) sequence data and coalescent simulations to test two general biogeographic hypothesis related to the effects of Pleistocene climatic fluctuations for a widespread ophidian species ( Gloydius brevicaudus ) in eastern China and Korean Peninsula. The phylogenetic analysis revealed three major lineages, the southeast Coastal, Yangtze and North Lineages. The latter two are closely related and jointly form a continental lineage. Divergence dating and coalescent simulations indicate a Late Pliocene to Early Pleistocene divergence between lineages from the southeast coast and continental interior, followed by a mid‐to‐late Pleistocene divergence between lineages from the north and the middle–lower Yangtze Valley across East China, suggesting that all these lineages predated the last glacial maximum. An overlapping range between the two lineages within the continental lineage and a secondary contact associated with ecological transition zones on the margins of the North China Plain were also observed. These results show that vicariance patterns dominated the history of G. brevicaudus . Though the climatic events of the Pleistocene have had a marked effect on the historical distribution and intra‐specific divergence of reptiles in China, coalescent and non‐coalescent demographic analyses indicate that all lineages of G. brevicaudus seem not to have been adversely affected by glacial cycles during the Late Pleistocene, presumably because of an increase in the amount of climatically mild habitat in East Asia due to a decline in elevation and the development of monsoons since the Mid‐End Pleistocene.

Gα13 is closely related to hematopoiesis in zebrafish - Ding Ye; Qiwen Yang; Yang Li; Xinyun Huang; Jiarui Hu; Shiguang Qian; Zheng Tan; Ping Song (Molecular Biology Reports, 2011)

Hepatic expression profile of forkhead transcription factor genes in normal Balb/c mice and their dynamic changes after bile duct ligation - Ping Yang; Shifeng Huang; Ding Liu; Qianyun Zhou; Yang-an Wen; Yu Xiang; Shan Sun; Xiaofei Lai; Yufang Dong; Liping Zhang (Molecular Biology Reports, 2011)

Increase of cytosolic calcium induced by trichosanthin suppresses cAMP/PKC levels through the inhibition of adenylyl cyclase activity in HeLa cells - Qingsong Jiang; Tumen Bai; Shunhua Shen; Lei Li; Haoliang Ding; Ping Wang (Molecular Biology Reports, 2011)

Identification of Differentially Expressed Sequence Tags in Rapidly Elongating Phyllostachys pubescens Internodes by Suppressive Subtractive Hybridization - Ming-bing Zhou; Ping Yang; Pei-jun Gao; Ding-Qin Tang (Plant Molecular Biology Reporter, 2011)

Synthesis, Crystal Structure, Interaction with BSA and Antibacterial Activity of La(III) and Sm(III) Complexes with Enrofloxacin - Yan-Jun Wang; Rui-Ding Hu; Dong-Hua Jiang; Ping-Hua Zhang; Qiu-Yue Lin; Yun-Yun Wang (Journal of Fluorescence, 2011)

The role of cell cycle-dependent neuropathy target esterase in cell proliferation - Ping-An Chang; Yu-ying Chen; Wen-zhen Qin; Ding-Xin Long; Yi-Jun Wu (Molecular Biology Reports, 2011)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

Determination of ocean tide loading displacements in Hong Kong using GPS technique - LinGuo Yuan; XiaoLi Ding; HePing Sun; Ping Zhong; Wu Chen (Science China Earth Sciences, 2010)

Validity and reliability testing of the Chinese (mainland) version of the 39-item Parkinson’s Disease Questionnaire (PDQ-39) - Wei Luo; Xiao-hong Gui; Bo Wang; Wen-ying Zhang; Zhi-yuan Ouyang; Yi Guo; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2010)

Alleviation of ovariectomy-induced osteoporosis in rats by Panax notoginseng saponins - Yang Shen; Yong-Qi Li; Shao-Ping Li; Lin Ma; Li-Ju Ding; Hui Ji (Journal of Natural Medicines, 2010)

Protein domains, catalytic activity, and subcellular distribution of mouse NTE-related esterase - Ping-an Chang; Zhan-xiang Wang; Ding-xin Long; Wen-zhen Qin; Yi-jun Wu (Molecular and Cellular Biochemistry, 2010)

Molecular analysis of grass carp (Ctenopharyngodon idella) by SRAP and SCAR molecular markers - Wei-dong Ding; Zhe-ming Cao; Li-ping Cao (Aquaculture International, 2010)

Unique evolutionary pattern of numbers of gramineous NBS–LRR genes - Jing Li; Jing Ding; Wen Zhang; Yuanli Zhang; Ping Tang; Jian-Qun Chen; Dacheng Tian; Sihai Yang (Molecular Genetics and Genomics, 2010)

Cosmogenic 21Ne concentrations and exposure ages of summit bedrocks in the Grove Mountains, Antarctica - Ping Kong; Lin Ding; QingZhou Lai; FeiXin Huang (Science China Earth Sciences, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

Identification and expression analysis of two zebrafish E2F5 genes during oogenesis and development - Qiwen Yang; Jiarui Hu; Ding Ye; Cailian Zhao; Shan Song; Wuming Gong; Zheng Tan; Ping Song (Molecular Biology Reports, 2010)

Mycophenolic acid inhibits albumin-induced MCP-1 expression in renal tubular epithelial cells through the p38 MAPK pathway - Hua Shui; Ping Gao; Xiaoyun Si; Guohua Ding (Molecular Biology Reports, 2010)

Sidereal filtering based on single differences for mitigating GPS multipath effects on short baselines - Ping Zhong; Xiaoli Ding; Linguo Yuan; Youlin Xu; Kenny Kwok; Yongqi Chen (Journal of Geodesy, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Synthesis, Characterization, DNA-Binding and Antiproliferative Activity of Nd(III) Complexes With N-(Nitrogen Heterocyclic) Norcantharidin Acylamide Acid - Wen-Zhong Zhu; Qiu-Yue Lin; Mei Lu; Rui-Ding Hu; Xiao-Liang Zheng; Jian-Ping Cheng; Yun-Yun Wang (Journal of Fluorescence, 2009)

Chemical constituents of the whole plants of Saussurea medusa - Zhuoma Dawa; Yang Bai; Yan Zhou; Suolang Gesang; Ping A; Lisheng Ding (Journal of Natural Medicines, 2009)

The effects of land use change on environmental quality in the red soil hilly region, China: A case study in Xianning County - Zhi-Hua Shi; Li-Ding Chen; Jun-Ping Hao; Tian-Wei Wang; Chong-Fa Cai (Environmental Monitoring and Assessment, 2009)

Sailing through the Late Pleistocene: unusual historical demography of an East Asian endemic, the Chinese Hwamei ( Leucodioptron canorum canorum ), during the last glacial period - SHOU‐HSIEN LI; CAROL K‐L. YEUNG; JULIE FEINSTEIN; LIANXIAN HAN; MANH HUNG LE; CHI‐XAN WANG; PING DING (Molecular Ecology, 2009)
Pleistocene climate fluctuations shaped the patterns of genetic diversity observed in extant species. In contrast to Europe and North America where the effects of recent glacial cycles on genetic diversity have been well studied, the genetic legacy of the Late Pleistocene for East Asia, a region of great topographical complexity and presumably milder historical climate, remains poorly understood. We analysed 3.86 kb of the mitochondrial genome of 186 Chinese Hwamei birds, Leucodioptron canorum canorum , and found that contrary to the conventional expectation of population decline during cold periods (stadials), the demographic history of this species shows continuous population growth since the penultimate glacial period (about 170 000 years ago). Refugia were identified in the south, coastal regions, and northern inland areas, implying that topographic complexity played a substantial role in providing suitable habitats for the Chinese Hwamei during cold periods. Intermittent gene flow between these refugia during the warmer periods (interstadials) might have resulted in a large effective population of this bird through the last glacial period.

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

N-demethylation of neonicotinoid insecticide acetamiprid by bacterium Stenotrophomonas maltophilia CGMCC 1.1788 - Ting Chen; Yi-Jun Dai; Juan-Fang Ding; Sheng Yuan; Jue-Ping Ni (Biodegradation, 2008)

Triptolide protects against 1-methyl-4-phenyl pyridinium-induced dopaminergic neurotoxicity in rats: Implication for immunosuppressive therapy in Parkinson’s disease - Jun-Peng Gao; Shan Sun; Wen-Wei Li; Yi-Ping Chen; Ding-Fang Cai (Neuroscience Bulletin, 2008)

An insulinoma with clinical and electroencephalographic features resembling complex partial seizures - Shuang Wang; Hai-tao Hu; Shu-qun Wen; Zhong-jin Wang; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2008)

Migraine as a sex-conditioned inherited disorder: evidences from China and the world - Xiao-Ping Wang; Hong-Liu Ding; Chang-Ming Geng; Yu-Mei Jiang (Neuroscience Bulletin, 2008)

Alzheimer’s disease: epidemiology, genetics, and beyond - Xiao-Ping Wang; Hong-Liu Ding (Neuroscience Bulletin, 2008)

Molecular cloning and expression of the C-terminal domain of mouse NTE-related esterase - Ping-An Chang; Ding-Xin Long; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2007)

Activation of p53 by Dishevelled independent of Wnt or planar polarity pathways - Vivianne W. Ding; Li-Ping Lin; Andrew L. Chiang; Frank McCormick (Journal of Molecular Medicine, 2007)

PaCDPK1, a gene encoding calcium-dependent protein kinase from orchid, Phalaenopsis amabilis, is induced by cold, wounding, and pathogen challenge - Tsung-Mu Tsai; Ying-Ru Chen; Tien-Wen Kao; Wen-Su Tsay; Chiou-Ping Wu; Ding-Ding Huang; Wen-Huei Chen; Ching-Chun Chang; Hao-Jen Huang (Plant Cell Reports, 2007)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Genetic Analysis of RET, EDNRB, and EDN3 Genes and Three SNPs in MCS + 9.7 in Chinese Patients with Isolated Hirschsprung Disease - Xian-Ning Zhang; Miao-Ni Zhou; Yun-Qing Qiu; Shi-Ping Ding; Ming Qi; Ji-Cheng Li (Biochemical Genetics, 2007)

Down-regulation of neuropathy target esterase by protein kinase C activation with PMA stimulation - Rui Chen; Ping-An Chang; Ding-Xin Long; Lin Yang; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2007)

Tannins and nitrogen dynamics in mangrove leaves at different age and decay stages (Jiulong River Estuary, China) - Yi Ming Lin; Jin Wen Liu; Ping Xiang; Peng Lin; Zhen Hua Ding; Leonel da Silveira Lobo Sternberg (Hydrobiologia, 2007)

Cloning and Characterization of a Rice Field Eel vasa-Like Gene cDNA and Its Expression in Gonads During Natural Sex Transformation - Ding Ye; Daoyuan Lv; Ping Song; Maoyu Peng; Yungui Chen; Ming Guo; Qiwen Yang; Yinchang Hu (Biochemical Genetics, 2007)

Effect of vinasse irrigation on the activity of three enzymes and agronomic characters at seedling stage of sugarcane - Wang Yi-Ding; Mo Yun-Chuan; Wang Wei-Hao; Li Yang-Rui; Ye Yan-Ping (Sugar Tech, 2006)

Morphogenesis and molecular basis on naked seed rice, a novel homeotic mutation of OsMADS1 regulating transcript level of AP3 homologue in rice - Zhi-Xiong Chen; Jian-Guo Wu; Wo-Na Ding; Han-Ming Chen; Ping Wu; Chun-Hai Shi (Planta, 2006)

Surgical results of pars plana vitrectomy combined with phacoemulsification - Chong-qing Yang; Jian-ping Tong; Ding-hua Lou (Journal of Zhejiang University-SCIENCE B, 2006)

Isolation and structure revision of 10-deacetyltaxinine from the seeds of the Chinese yew, Taxus mairei - Qing-Wen Shi; Zuo-Ping Li; Ding Zhao; Ji-Shun Gu; Hiromasa Kiyota (Natural Product Research, 2006)

Prognostic significance of bcl-2 and p53 expression in colorectal carcinoma - Dan-ping Zhao; Xiao-wen Ding; Jia-ping Peng; Yi-xiong Zheng; Su-zhan Zhang (Journal of Zhejiang University-SCIENCE B, 2005)

Evapotranspiration of low-lying prairie wetland in middle reaches of heihe river in northwest China - Jin-kui Wu; Yong-jian Ding; Gen-xu Wang; Yong-ping Shen; Yamazaki Yusuke; Kubota Jumpei (Chinese Geographical Science, 2005)

A simulation study on the Ca2+-independent but voltage-dependent exocytosis and endocytosis in dorsal root ganglion neurons - Hua Yang; Chen Zhang; Hui Zheng; Wei Xiong; Zhuan Zhou; Tao Xu; Jiu Ping Ding (European Biophysics Journal, 2005)

Population Genetic Structure of the Yangtze Finless Porpoise (Neophocaena phocaenoides asiaeorientalis): Implications for Management and Conservation - Jin-Song Zheng; Jun-Hong Xia; Shun-Ping He; Ding Wang (Biochemical Genetics, 2005)

A genetic diversity comparison between captive individuals and wild individuals of Elliot’s Pheasant (Syrmaticus ellioti) using mitochondrial DNA - Ping-ping Jiang; Qiu-lei Lang; Sheng-guo Fang; Ping Ding; Li-ming Chen (Journal of Zhejiang University-SCIENCE B, 2005)

Increased expression of aquaporin-4 in human traumatic brain injury and brain tumors - Hua Hu; Hong-tian Yao; Wei-ping Zhang; Lei Zhang; Wei Ding; Shi-hong Zhang; Zhong Chen; Er-qing Wei (Journal of Zhejiang University-SCIENCE B, 2005)

Use of oligonucleotide fingerprinting and faecal DNA in identifying the distribution of the Chinese tiger (Panthera tigris amoyensis Hilzheimer) - Qiu-Hong Wan; Sheng-Guo Fang; Guo-Fu Chen; Zhang-Ming Wang; Ping Ding; Mu-Yuan Zhu; Kong-Shou Chen; Jiu-Hua Yu; Yue-Ping Zhao (Biodiversity and Conservation, 2003)

Computational analysis of composite regulatory elements - Ping Qiu; Wei Ding; Ying Jiang; Jonathan R. Greene; Luquan Wang (Mammalian Genome, 2002)

Interdecadal fluctuation of dry and wet climate boundaries in China in the past 50 years - Yang Jian-ping; Ding Yong-jian; Chen Ren-sheng; Liu Lian-you (Journal of Geographical Sciences, 2002)

Genetic Diversity of Chinese Native Pigs Inferred from Protein Electrophoresis - Xiaoqiu Wu; Bo Ding; Ya-Ping Zhang (Biochemical Genetics, 1999)